Modeling and optimization of premix burner utilizing low calorific value gaseous fuels for industrial applications - Sujeetkumar P. Deore; Kiran Thammina; Sandeep Kumar; Sanjay M. Mahajani (Biomass and Bioenergy, 2027)

Formulation, Optimization, and Evaluation of Gastro-Retentive Floating Beads of Nelfinavir Mesylate Prepared by Emulsion Gelation Technique - Priyanka Rajput; Navinder Singh; Reena Kumari; Sandeep Kumar; Rachna Kumria; Ishrat Zahoor; Ramchander Khatri; Tanuj Hooda; Amit Lather (Journal of Pharmaceutical Innovation, 2027)

Performance optimisation of biomass ash and rice husk ash-based geopolymer concrete using response surface methodology for enhanced strength and durability - Sandeep Singh; Kartik Kumar A. Patel; Jagdeep Singh; Dasarathy A. K; Vanitha S; Priyadarshi Das (European Journal of Environmental and Civil Engineering, 2026)

Automating sustainable manufacturing: optimizing eco-friendly geopolymer bricks with plastic waste and curing conditions - Md. Zia Ul Haq; Shelesh Krishna Saraswat; Dasarathy A. K; Rakesh Kumar; Sandeep Singh; Sourabh Dhiman; Teku Kalyani; Laith H. Alzubaidi (European Journal of Environmental and Civil Engineering, 2026)

Integrating genomics, multi-omics, CRISPR and speed breeding for stress-resilient vegetable legume improvement - Sandeep Indurthi; Gurpreet Kaur; Rituraj Dutta; Saatu Madhu; Bhaskar Chodasani; Amul Yadav; Manpreet Singh; Tarun Kumar Meena; Gurjeet Singh (Functional & Integrative Genomics, 2026)

Soil health indicators as influenced by long-term tillage and crop rotations in Nebraska - Goutham Thotakuri; Anuoluwa O. Sangotayo; Jemila Chellappa; Sangeeta Bansal; Poulamee Chakraborty; Sutie Xu; Péter Kovács; Laila A. Puntel; Charles Shapiro; Sandeep Kumar; Sandeep Sharma; Javed Iqbal (Soil and Tillage Research, 2026)

Comprehensive assessment of seismic attenuation and local site effects along the Himalayan arc: implications for crustal heterogeneity - Parveen Kumar; Ashish Yadav; Monika; Sandeep; Narendra Kumar; Dilip K. Yadav; A. Joshi (Journal of Asian Earth Sciences, 2026)

Synergistic and comparative assessment of cold plasma and ozone treatments for chlorpyrifos reduction, cytotoxicity mitigation, and quality retention in chili - Neha Tanwar; Arpan Singha Deo; Madan Kumar Perumal; Sukumar Debnath; Sandeep N. Mudliar (Food Control, 2026)

Gamete co-incubation duration modulates blastocyst developmental competence in buffalo through regulation of growth factors, steroidogenesis and oxidative stress pathways - Garbhit Sharma; Anand Kumar Pandey; Hitesh Jangra; Sandeep Kumar; Pradeep Saini; Rajesh Kumar; Divya Choudhary (Molecular Biology Reports, 2026)

CRISPR/Cas‑driven biosensing: molecular mechanisms and advances in diagnostics - Qamar Abuhassan; Hamzeh J. Al-Ameer; Tushar B. Gajjar; Malathi Hanumanthayya; Sandeep Kumar Shukla; Rajashree Panigrahi; Neeraj Bainsal; Durdona Khaydarova (Molecular Biology Reports, 2026)

Prevalence of quorum sensing luxS gene in multidrug resistant uropathogens - Soham Ghosh; Shilpa Pradhan; Sandeep Kumar Kotturu; Swarajya Lakshmi; Sangita Mukhopadhyay (Molecular Biology Reports, 2026)

Unveiling the contemporary genetic diversity and population demography of the critically endangered northern river terrapin (Batagur baska) in the sundarbans - Ajit Kumar; Anand Sharma; Naveen Negi; Ruchi Badola; Syed Ainul Hussain; Sandeep Kumar Gupta (Molecular Biology Reports, 2026)

Computational Insights in Identification of Proficient Transient Receptor Potential Vanilloid 1 Inhibitors: A Pathway for Extenuating Chemotherapy-Induced Peripheral Neuropathy - Dinesh Kumar Chandanapalli; Shristi Arya; Shailesh Mani Tripathi; Ashish Kumar; Arbaz Sujat Shaikh; Venkata Rao Kaki; Sandeep Sundriyal; Pankaj Kumar Singh; Jitender Madan (Journal of Pharmaceutical Innovation, 2026)

Dynamical orbital evolution of collision induced asteroid debris: The formation and dispersal of asteroid families - Sandeep Sahijpal; Mahesh Kumar (Planetary and Space Science, 2026)

Comparative analysis of enzymatic, molecular and physiological defense responses of mungbean (Vigna radiata) cultivars under mungbean yellow mosaic India virus infection - H.M. Heena Kouser; Nagamani Sandra; Sandeep Kumar Lal; Gyan Prakash Mishra; Muraleedhar S. Aski; Anjali Anand (Physiological and Molecular Plant Pathology, 2026)

Ultraviolet-C treatment of spices and herbs: A critical review on microbial safety and quality retention - Sandeep Sarkar; Akshay H. Dasalkar; Sudheer Kumar Yannam (Food Research International, 2026)

Real-time estimation of earthquake early warning magnitude using a hybrid dataset of observed and simulated P-wave onsets for the Himachal Himalaya (Mw 4.0–8.5) - Suraj Kumar Pal; Sandeep; Parveen Kumar; Monika; Pragya Singh; Vikas Singh; Himanshu Mittal (Journal of Seismology, 2026)

Experimental analysis and Machine Learning-based prediction of temporal scour dynamics at the first spur dike in a series of repelling spur dikes - Sandeep Kumar; Prashanth Reddy Hanmaiahgari (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Boronic acid-functionalized materials in food and environmental safety: Progress in design, synthesis, and sensing applications - Suleiman Ibrahim Mohammad; Asokan Vasudevan; Feras Alnaimat; Mirza R. Baig; Shreedhar M. Rao; Gulnoza Djakhangirova; M.M. Rekha; Navin Kumar Tailor; Sandeep Kumar Shukla; Zyad Shaaban (Journal of Environmental Chemical Engineering, 2026)

Waste-valorized Punica granatum peel–mediated SnO₂: Precursor concentration control for rapid 4-nitrophenol reduction and HCT116 colorectal anticancer response - Nelson Ashem; Sanjeev Kumar; Anand Somvanshi; Roohul Abad Khan; Kasim Sakran Abass; Komal Malhan; Jyoti Gaur; Jasdeep Kaur; Changanamkandath Rajesh; Ramneet Kaur Rana; Gurjinder Singh; Sandeep Kaushal (Journal of Environmental Chemical Engineering, 2026)

Solar-driven ammonia production from nitrate using phase-engineered TiO2 nanorods - Ajith P. Varghese; Bernaurdshaw Neppolian; Sandeep Kumar Lakhera (Journal of Environmental Chemical Engineering, 2026)

Citrus cavaleriei phytochemical-assisted interfacial engineering of a phyto-hydrolysis nanoplatform with tunable nucleation kinetics for enhanced ROS catalysis and biomedicine - Bhavna Vidhani; Anand Somvanshi; Roohul Abad Khan; Sandeep Kaushal; Jyoti Gaur; Sanjeev Kumar (Journal of Environmental Chemical Engineering, 2026)

Bioplastics derived from microalgae: A new perspective on biorefinery development, challenges, opportunities, and sustainability assessment for a circular bioeconomy approach - Rahul Kumar Goswami; Sandeep Singh Shekhawat; Ismail Rawat; Pradeep Verma; Faizal Bux (Journal of Environmental Chemical Engineering, 2026)

Ensemble modelling of habitat suitability and potential range shifts of Betula utilis in the Western Himalaya under climate change scenarios - Amit Kumar Verma; Sai Pratik Ojha; Sandeep Kumar (Flora, 2026)

Association of intra-follicular melatonin with reduced oxidative DNA damage and improved oocyte quality in water buffalo: Effect of season and follicular size - Anand Kumar Pandey; Pankaj Gunwant; Sandeep Kumar; Gitesh Saini; Chandra Shekhar Patil; Rakesh Kumar (Domestic Animal Endocrinology, 2026)

Microphysical evolution of fog: Transition from haze to fog in Delhi - Prasanna Lonkar; Sandhya Jose; Sandeep Wagh; Pooja Pawar; Sumit Kumar; Suresh Gosavi; Akash S. Vispute; Sachin D. Ghude (Atmospheric Environment, 2026)

Author Correction: Stochastic ground-motion simulation using the EXtended SIMulation approach and synthetic aperture radar based damage assessment of the 2025 Myanmar earthquake - Monika; Ashwani Raju; Vikas Singh; Parveen Kumar; S. K. Pal; Saraah Imran; Sandeep (Journal of Seismology, 2026)

Diminution of Carbon Tetrachloride Induced Hepatic Damage by Liquiritin and Glabridin Via Nrf2/Keap1/p62 Pathway: In Vivo and Molecular Docking Studies - Sandeep Kaur; Vaseem Raja; Sheikh Showkat Ahmad; Simrandeep Kaur; Harjeet Singh; Arubhi Bansal; Prabhakar Chetti; Subheet Kumar Jain; Satwinderjeet Kaur; Khalid Rehman Hakeem (Journal of Pharmaceutical Innovation, 2026)

Formulation and Characterization of TPGS-Coated Cabazitaxel Liposomes: In-Vitro Cytotoxicity, Drug Release, and In-Silico Metabolic Modulation - Dnyaneshwar Dhole; Sandeep Jat; A Prabakaran; Ankita Nishad; Dnyaneshwar Maykar; Pratik Vilas Gore; Shahnawaz Ahmed; Amit Alexander; Vaibhav A. Dixit; Pramod Kumar (Journal of Pharmaceutical Innovation, 2026)

Evaluation of phytochemicals, antioxidant and antibacterial activities of Lasiococca comberi Haines leaf extracts - Sandeep Kumar Mohanta; Gyanajeet Parida; Bhaswatimayee Mahakur; Prabhat Kumar Das; Aryaputri Bedaprabha; Sanjay Kumar Madkami; Abanikanta Bhadra; Nihar Ranjan Singh; Durga Prasad Barik (Vegetos, 2026)

Convolution neural network-based estimation of high-resolution urban canopy parameters for urban climate modelling - Kshama Gupta; Kakali Deka; Surendra Kumar Sharma; Ashutosh Bhardwaj; Sandeep Maithani; Raghavendra Pratap Singh (Urban Climate, 2026)

100 m resolution projection of future urban heat Island of a tropical Coastal City - Song Chen; Anupam Kumar; Venkatraman Prasanna; Pratiman Patel; Kalli Furtado; Sandeep Sahany; Hugh Zhang; Aurel Moise (Urban Climate, 2026)

Multimodal disruption of the Pseudoperonospora cubensis biotrophic interface: From structural pangenomics to nanotherapeutic gene silencing - Rajat Sharma; Sandeep Kansal; Vinay Kumar; Sachin Bhardwaj (Physiological and Molecular Plant Pathology, 2026)

Phytogenic synthesis of cobalt oxide nanoparticles with Mallotus philippensis and their photocatalytic–antimicrobial efficiency - Sandeep Kumar; Pooja Kumari; Manish Kumar; Deepika Kaushal (Next Research, 2026)

Potentiating the germination kinetics and physiological vigour via microbial coating: A strategy for enhancing post-storage viability and shelf-life in green gram seed (Vigna radiata (L.) Wilczek) - Samrat Rej; Radha Prasanna; Sandeep Kumar Lal; Sudipta Basu; Priya Ranjan Kumar; Anjali Anand; Aditi Tayade (Journal of Stored Products Research, 2026)

Mangrove carbon dynamics: Sequestration potential and climate change resilience - Asha Kumari Kumawat; Sandeep Kumar; Supriya Vaish; Bhawana Pathak (Earth-Science Reviews, 2026)

Genome wide association studies and expression analyses identify candidate genes for spot blotch resistance in bread wheat - G. Mahendra Singh; Uttam Kumar; Bhagya Shree Acharya; Pradeep Bhati; Manish Vishwakarma; Dinesh Kumar Saini; Sundeep Kumar; Vinod K. Mishra; Arun K. Joshi; Sandeep Sharma (Theoretical and Applied Genetics, 2026)

A review of nutritional, ecological, and socio-economic aspects of chromatic rice varieties - Priyanka Mahajan; Sandeep Kaur; Meenakshi Gusain; Harvinder Singh; Vinod Balmiki; Sanjay Kumar; Nitin Kumar (Cereal Research Communications, 2026)

Grazing by livestock modifies the response of soil microbes to elevated atmospheric carbon dioxide - Freya Newton; Shengjing Shi; Natascha Lewe; Sandeep Kumar; Paul Maclean; Paul Newton; Julie Deslippe (Agriculture, Ecosystems & Environment, 2026)

Development of Rhizobium rhizogenes-induced hairy root cultures of Vitex negundo for vitexin production - Bhaswatimayee Mahakur; Aryaputri Bedaprabha; Sandeep Kumar Mohanta; Arpita Moharana; Swasti Swagatika Swain; Durga Prasad Barik (World Journal of Microbiology and Biotechnology, 2026)

Spatio-temporal analysis of coal mining impacts on land cover using remote sensing: a case study of Northern Coalfields, India - Sanyam Dadhich; Sandeep Kumar Asarapalli; Amrendra Kumar; A. Jamal; Suresh Sharma; Md. Muzzammil (Environmental Monitoring and Assessment, 2026)

ARF Gene Family: Expression Dynamics, Signalling, and Importance in Seed Development - Kumari Arpita; Sandhya Sharma; Anshika Tyagi; Arvind Yadav; Sandeep Kumar; Rupesh Deshmukh; Robert M Stupar; Kishor Gaikwad (Journal of Plant Growth Regulation, 2026)

Uppermost mantle velocity and geometry of the underthrusting Indian Moho beneath the Eastern Himachal Himalaya using regional earthquake travel time analysis - Vishal Singh Rawat; Sandeep Gupta; Sudesh Kumar; M Saidixith; B N V Prasad (Journal of Earth System Science, 2026)

Phytochemical profiling, antioxidant, DNA protective and antiproliferative potential of methanolic fraction of Hemidesmus indicus (L.) R. Br. roots: in vitro and in silico studies - Simrandeep Kaur; Rasdeep Kour; Majed Alrobaian; Ashish Kumar; Aman Agrawal; Sandeep Kaur; Vijai Malik; Satwinderjeet Kaur; Sheikh Showkat Ahmad (In vitro models, 2026)

Multi-process assessment of soil-water-erosion dynamics in coir geocell-reinforced steep slopes under extreme rainfall - Sandeep Kumar Namburu; Sreevalsa Kolathayar; Hasthi Venkateswarlu (Journal of Mountain Science, 2026)

Limited carbon storage in arid mangroves of the Kachchh Region, Western India - Asha Kumari Kumawat; Daniel M. Alongi; Sandeep Kumar; Bhawana Pathak (Regional Studies in Marine Science, 2026)

Modern catchment soil–lake sediment linkages: Proxy distribution patterns in a small lake in coastal Karnataka, southern India - A.S. Yamuna; Anish Kumar Warrier; Jyoti Srivastava; Anoop Ambili; Firoz Badesab; Mamilla Venkateshwarlu; K. Sandeep; Pranav Prakash; Soumyashree Behera; G.S. Joju; Diptimayee Behera (Quaternary International, 2026)

Microstructural modeling on cement mechanical properties under carbonation reactions and its implications to well integrity - Zhuang Sun; Rafael Salazar-Tio; Sandeep Kumar; Andrew Fager; Bernd Crouse (Fuel, 2026)

Assessment of carbon stocks and soil carbon pools in temperate oak forests of the Garhwal Himalaya, India - Pooja Uniyal; Vinod Prasad Khanduri; Deepa Rawat; Sandeep Kumar; Bhupendra Singh; Chatar Singh Dhanai; Taufiq Ahmad (Biomass and Bioenergy, 2026)

Can Micro-Irrigation in Canal Command Areas Increase Water Use Efficiency? A Feasibility Study for Sustainable Water Resources - Sandeep Kumar Chourasia; Sumit Kumar Vishwakarma; Ashish Pandey (Water Conservation Science and Engineering, 2026)

Comprehensive field-based hazard assessment and mitigation strategies of glacial lakes in the Eastern Himalaya - R. K. Sharma; Rajeev Rajak; Sandeep Tambe; Pranay Pradhan; Narpati Sharma; Baichung Lepcha; Priya Pradhan; Rajesh Kumar; Dhiren G. Shrestha; Dharmendra Lamsal; Sajan Poudyal; Tenzing D. Bhutia; et al. (Natural Hazards, 2026)

Stochastic ground-motion simulation using the EXtended SIMulation approach and synthetic aperture radar based damage assessment of the 2025 Myanmar earthquake - Monika; Ashwani Raju; Vikas Singh; Parveen Kumar; S. K. Pal; Saraah Imran; Sandeep (Journal of Seismology, 2026)

Evaluating graphite tailings and biomass ash as sustainable replacements in concrete: experimental and predictive assessment - Sandeep Singh; Kartik kumar A. Patel; Jagdeep Singh; A. K. Dasarathy; S. Vanitha; Priyadarshi Das (Innovative Infrastructure Solutions, 2026)

Correction to: Medicinal Plants and the Gastrointestinal Microbiota in Chronic Diseases Modulation: A Structured Mechanistic and Translational Review - Esther Ugo Alum; Daniel Ejim Uti; Okechukwu Paul-Chima Ugwu; Michael Ben Okon; Waheeb Sami Aggad; Hailah M. Almohaimeed; Neeraj Bainsal; Sandeep Kumar Shukla; Kranti Kiran Reddy Ealla (Current Microbiology, 2026)

DFruitNet: A Lightweight Dual-Attention Network with Feature Fusion for Explainable Dragon Fruit Disease Classification and Severity Assessment - Basab Nath; Sandeep Kumar; Yonis Gulzar; Mohannad Alkanan (Applied Fruit Science, 2026)

Evaluation of Shatpada Fruit Fly Traps Versus Conventional Fruit Fly Traps in Citrus in India - Sandeep Singh; Srinivas Reddy; Ranjit Kadu; Y. V. Ingle; Sikha Deka; Raaj Kumar Kokoti; L. Ranjith Kumar; Aayush Kaushal; Deepa Bhagat; S. Priya Devi; Guranshpaul Singh; Ashok Kumar; et al. (Applied Fruit Science, 2026)

Advancing Breeding Strategies for Late Blight Resistance in Potatoes - Zulfiqar Ali Sahito; Vikas Mangal; Oswald Nkurikiyimfura; Ibrahim M. Abouelgalagel; Sandeep Kumar Singh; Salej Sood; Zhijian Zhao; Jianming Bai; Zhechao Pan (American Journal of Potato Research, 2026)

Textural and mineralogical studies of sphalerite: constraints on the genesis of the Zn-Pb deposits of Zawar, India - Arkodeep Sengupta; Kamal Lochan Pruseth; Soumi Chattopadhaya; Mahimaa Dash; Sandeep Kumar Rajput (International Journal of Earth Sciences, 2026)

Assessment of Carbon and Phosphorus Stoichiometry in Different Land use Systems as a Tool for Future Planning in Agroecosystems in North Central India - Ram Swaroop Meena; Kundan Kumar Singh; Gourisankar Pradhan; Suchismita Satapathy; Sanjeev Kumar; Krishan Kant Mina; Sandeep Kumar; Cherukumalli Srinivasa Rao; Rattan Lal (Anthropocene Science, 2026)

Integrated screening of Indian slicing cucumber core genotypes for downy mildew resistance (Pseudoperonospora cubensis) and associated biochemical defence mechanisms - Kishor Varotariya; Mottaiyan Pitchaimuthu; D. C. Manjunatha Gowda; Budhavaram Varalakshmi; Kundapura V. Ravishankar; G. M. Sandeep Kumar; Vivek Hegde; Lingapatna T. Chaithra (Indian Phytopathology, 2026)

Diagnostic Classification of Autism Spectrum Disorder Using SD Maps of fMRI Data and Machine Learning - Epimack Michael; Sandeep Singh Sengar; Jac Fredo Agastinose Ronickom; Deepesh Kumar (Journal of Medical and Biological Engineering, 2026)

Catecholase activity, DNA cleavage and cytotoxicity of six Zn(II) complexes synthesized from designed Mannich ligands: higher reactivity of mononuclear over dinuclear - Ria Sanyal; Sandeep Kumar Dash; Sudhanshu Das; Sourav Chattopadhyay; Somenath Roy; Debasis Das (JBIC Journal of Biological Inorganic Chemistry, 2026)

Insilico study to unveil the characteristics of pseudoRab GTPases in pathogenic protozoan parasites: Entamoeba histolytica - Mrinalini Roy; Kinjal Desai; Zeel Parmar; Tarini Rajput; Jaikee Kumar Singh; Sanket Kaushik; Sandeep Kumar Srivastava; Anupam Jyoti; Vijay Kumar Srivastava (In Silico Pharmacology, 2026)

Effect of Boron on the Growth Performance, Biochemical Indices, Carcass, Intestinal and Bone Characteristics with Economics in Broiler Chickens - Jayant Kumar Kakwani; Dharmesh Tewari; S. Gautam; Pallavi Maurya; S. S. Kashyap; V. K. Singh; Shubham Tripathi; Manish Kumar Singh; Sandeep Kumar Chaudhary (Biological Trace Element Research, 2026)

Population structure and genetic diversity of Elwendia persica in the Western Himalayan region of India - Sangita Bansal; Parampara Joshi; Sabina Rana; Amit Kumar; Era V. Malhotra; Ajaz A. Lone; Narender Negi; Rahul Chandora; Sandeep Kumar; Rakesh Singh; G.P. Singh (Journal of Applied Research on Medicinal and Aromatic Plants, 2026)

Multi-step Daily Reservoir Inflow Prediction using Temporal Conventional Network Model Integrating time-Varying Filter-Based empirical mode Decomposition and Holt-Winters Algorithms - Atefeh Sadat Hosseini; Sultan K. Salamah; Ahmed Alkhayyat; Anupam Yadav; Abhinav Kumar; Marwan Kheimi; Sandeep Singh; KDV Prasad (Water Resources Management, 2026)

The effects of vitamin D supplementation on inflammatory biomarkers: an umbrella study of meta-analysis on randomized controlled trials - Chou-Yi Hsu; Hassan Youssef Hussein; Karam Akram Al-akkam; Tushar B. Gajjar; Hamad AlMohamadi; Nodir Khonturaev; Sandeep Kumar Shukla; Safa Hussien Radhi; Aseel Smerat; Muhammad Shahid Iqbal (Inflammopharmacology, 2026)

Application of machine learning tools for prediction of seed cotton yield in upland cotton (G. hirsutum L.) under irrigated ecosystem - Debashis Paul; Vinita Gotmare; M. Saravanan; Sandeep Bagri; Harish Kumbhalkar; Subhash Chandra; S. K. Verma; Rishi Kumar; Y. G. Prasad (Euphytica, 2026)

Bioinformatics-driven genome-wide identification of viral miRNAs in high spillover bat coronaviruses and their target genes in human - Siddhant Mazumder; Shreya Kapoor; Hargunjeet Kaur; Jasmine Thakur; Ritvika Hasija; Kiran Daroch; Harshil Walia; Shubham Kumar; Dikshant Saini; Chander Jyoti Thakur; Avneet Saini; Sandeep Saini (Archives of Microbiology, 2026)

The gut microbiome axis: how Lactobacillus-fermented soymilk orchestrates health - Vaishali Saini; Arpit Verma; Samlesh Kumari; Sandeep Chaudhary; Amit Mishra; Awanish Kumar; Hem Chandra Jha (Archives of Microbiology, 2026)

Probiotics as modulators of the gut-derived incretin peptide axis in type 2 diabetes: GLP-1, GLP-2, and microbial metabolite signaling - Ghaleb Oriquat; Waleed K. Abdulsahib; Wael Waleed Mustafa; Tushar B. Gajjar; Malathi Hanumanthayya; Sandeep Kumar Shukla; Rajashree Panigrahi; Neeraj Bainsal; Saodat Khaitova (Protoplasma, 2026)

Retraction Note: Surface modification minimizes the toxicity of silver nanoparticles: an in vitro and in vivo study - Balaram Das; Satyajit Tripathy; Jaydeep Adhikary; Sourav Chattopadhyay; Debasis Mandal; Sandeep Kumar Dash; Sabyasachi Das; Aditi Dey; Sankar Kumar Dey; Debasis Das; Somenath Roy (JBIC Journal of Biological Inorganic Chemistry, 2026)

Enhancing Forage Harvest, Digestibility and Nutrient Profiles in Forage Sorghum via Synergistic Application of Micronutrients and Plant Growth Regulators - Naveen Kumar; Sandeep Singh; R. K. Agrawal; Tarun Sharma; Shwetansh; Sukhchain Singh (Journal of Plant Growth Regulation, 2026)

Differential Responses of Humic Acid and Potassium Application on Physiology, Yield, and Quality Attributes of Dragon Fruit Under Sub-tropical Conditions - Sandeep Kumar; Priyanka Kumawat; Vishal Kaushal; Sunny Sharma; Vishal Singh Rana; Shubham Patidar (Journal of Soil Science and Plant Nutrition, 2026)

Electrochemical detection of esomeprazole in wastewater using Sm2HfZnO6@graphene oxide nanohybrid: A synergistic experimental-DFT study - Sahana Kamanna Metry; Sirisha Subbareddy; Santhosh Arehalli Shivamurthy; Kumar Venkatesan; Manickam Selvaraj; Nanjundaswamy Shanthappa; Sandeep Shadakshari (Journal of Environmental Chemical Engineering, 2026)

1‑monolinoleoylglycerol and 3,4‑dihydroxymandelic acids-mediated ZnO for antibiotic degradation and anticancer activity - Vijay Kumar; Sunil Kumar; Sanjeev Kumar; Khalid Mujasam Batoo; Ahmed Ahmed Ibrahim; Kasim Sakran Abass; Jyoti Gaur; Sandeep Kaushal (Journal of Environmental Chemical Engineering, 2026)

Trade-offs and synergies of conservation agriculture practices in the maize–wheat system: Improving yield, profitability, and soil resilience in a changing climate - Mohammad Hasanain; V.K. Singh; S.S. Rathore; Vijay Singh Meena; R.K. Singh; Kapila Shekhawat; B.S. Dwivedi; P.K. Upadhyay; Sunita Kumari Meena; Amit Kumar; Adarsh Kumar; Gaurav Verma; et al. (Field Crops Research, 2026)

Landscape-driven genetic structure of three mangrove species of western India inferred from SCoT markers - Asha Kumari Kumawat; Suman Kumar Jha; Sandeep Kumar; Bhawana Pathak (Ecological Genetics and Genomics, 2026)

Talaromyces atroroseus pigment-derived silver nanoparticles functionalized with 6-benzylaminopurine for enhanced in vitro growth of Musa acuminata cv. ‘Grand Nain’ - Kavyarathna; R. Aakash; M. Nithin Kumar; K.U. Minchitha; S. Swetha; Sandeep Suryan; G.S. Nagananda (Biocatalysis and Agricultural Biotechnology, 2026)

In vivo use of melatonin improves oocyte developmental competence and blastocyst development rate in indigenous donor cow during summer - Anupama Solanki; Anand Kumar Pandey; Hitesh Jangra; Pradeep Saini; Sandeep Kumar; Ramakant Kaushik; Vinay Ganeshrao Joshi; Rajesh Kumar; Satish Kognole (Tropical Animal Health and Production, 2026)

Haplo-pheno association for OsNRT1.1 paralog in rice reveals superior haplogroup with high nitrate uptake - Dharani Elangovan; Sandeep Sharma; Balaji Balamurugan; Neha Anand; Adhip Das; Tarun Kumar; Ranjith Kumar Ellur; Sanjay Kalia; Jagadish Rane; Renu Pandey (Plant Physiology Reports, 2026)

Bridging precision and practice: dual validation of a high-resolution detector array for beam profiling and patient QA in robotic radiosurgery - Sandeep Singh; Supratik Sen; Abhay Kumar Singh; Dipesh; Manindra Bhushan; Benoy Kumar Singh; Sarthak Tandon; Munish Gairola (Physical and Engineering Sciences in Medicine, 2026)

Augmenting the Elemental Sulphur–based Formulation with Pseudomonas Chloritidismutans Strain WH2 for Improved Sodic Soil Reclamation and Crop Performance - Arvind Kumar Rai; Nirmalendu Basak; Priyanka Chandra; Parul Sundha; Harshpreet Kaur; Sandeep Bedwal; Subedar Patel; Sanjay Kumar; Rameshwar Lal Meena; Parbodh Chander Sharma; Rajender Kumar Yadav (Journal of Soil Science and Plant Nutrition, 2026)

Use of coir geocells with coconut shell infills for improved performance of spread footings resting on sandy soils - Sandeep Kumar Namburu; Sreevalsa Kolathayar (Innovative Infrastructure Solutions, 2026)

Medicinal Plants and the Gastrointestinal Microbiota in Chronic Diseases Modulation: A Structured Mechanistic and Translational Review - Esther Ugo Alum; Daniel Ejim Uti; Okechukwu Paul-Chima Ugwu; Michael Ben Okon; Waheeb Sami Aggad; Hailah M. Almohaimeed; Neeraj Bainsal; Sandeep Kumar Shukla; Kranti Kiran Reddy Ealla (Current Microbiology, 2026)

Cyanobacteria-coated seeds for improved productivity and seed storability in direct-seeded and transplanted rice - Shreya Kumari; Aditi Tayade; Deepti Varsha; Yashbir Singh Shivay; Sudipta Basu; Sandeep Kumar Lal; Arun Kumar; Preeti Soni; Radha Prasanna (Cereal Research Communications, 2026)

Expanding geographical and genetic footprint of tobacco streak virus in Northern India: first documentation from cotton in Haryana - Anil Kumar Saini; Shubham Saini; Kishor Kumar; Pankhuri Singhal; Adesh Kumar; Karmal Singh; Anil Jakhar; Sandeep Kumar; Ankit Bishnoi; Satish Kumar Sain; Aniket Angira (Virus Genes, 2026)

Groundwater sustains the Gomati River in the Ganga Alluvial Plain: Implications for time-series analysis of environmental isotopes - Sonu Kumar; Shaifullah; Priyanka Singh; Sandeep Singh; Sudhir Kumar; Satyendra Singh; Ratan Kar; Munendra Singh (Applied Geochemistry, 2026)

Comprehensive Morphological and Molecular Characterization of Conopomorpha sinensis Bradley (Lepidoptera: Gracillariidae) on Litchi (Litchi chinensis) from India - Masrat Siraj; Sandeep Singh; Vikas Jindal; Rajwinder Kaur Sandhu; P. R. Shashank; Aayush Kaushal; Guranshpaul Singh; Sumanjit Kaur; Poonam Srivastava; Anamika Kar; Jaipal Singh Choudhary; M. K. Dhakar; et al. (Applied Fruit Science, 2026)

Engineering properties of Himalayan rocks: a comprehensive review across tectono-stratigraphic zones - Bikash Kumar Ram; Divyanshoo Singh; Hemant Kumar Singh; Vikram Gupta; Deepak Amban Mishra; Sandeep Kumar (Journal of Earth System Science, 2026)

Assessment of uranium levels and associated health risks in drinking water from various aquifers in northeastern Rajasthan, India - Sunil Kumar; Sandeep Kansal; Vikas Duggal; Navish Kataria (Isotopes in Environmental and Health Studies, 2026)

Boosting biohydrogen production from pretreated sugarcane bagasse dust via coupled dark fermentation and microbial electrolysis cell - Soumyajit Chandra; Soumya Pandit; Mohit Kumar; Sandeep Kumar Shukla; Srijoni Banerjee (Bioresource Technology, 2026)

Catalytic hydrothermal liquefaction of rice straw for production of high quality bio-oil - Bijoy Biswas; Mridusmita Dutta; Sandeep Kumar; Rawel Singh (Biomass and Bioenergy, 2026)

Sustainable energy-food-nutrient nexus: strategies for enhancing wheat production resilience in India - Mohammad Hasanain; V.K. Singh; S.S. Rathore; Vijay Singh Meena; R.K. Singh; Kapila Shekhawat; Sunita Kumari Meena; B.S. Dwivedi; P.K. Upadhyay; Rajendra P. Mishra; Gaurav Verma; Sandeep Kumar; et al. (Biomass and Bioenergy, 2026)

Field evaluation of fungicide and mineral-oil spray programmes for managing sooty mould in Bt cotton across different environments in Punjab, northern India - Rupesh Kumar Arora; Manpreet Singh; Sandeep Kumar Raheja; Jagdish Kumar Arora; Ashok Kumar (Journal of Plant Pathology, 2026)

Design, Synthesis, and Characterization of TEPE-Zn-MOF as a Turn-On Fluorescent Probe for Pb²⁺ Detection - Kinjal Modi; Dhruvi Kher; Bhavesh Dhumale; Nihal Patel; Keyur Bhatt; Chirag N. Patel; Vaibhav Bhatt; Mukesh Chaudhari; Hitesh Patel; Hasit Vaghani; Krunal Modi; Sandeep Kumar; et al. (Journal of Fluorescence, 2026)

Convection-permitting climate simulations using SINGV-RCM and WRF over the Maritime Continent - Venkatraman Prasanna; Srivatsan V. Raghavan; Anurag Dipankar; Jianyu Liu; Gerald Lim; Aurel Moise; Nguyen Ngoc Son; Bhenjamin Jordan Lozada Ona; Pavan Harika Raavi; Anupam Kumar; Jianjun Yu; Chen Chen; et al. (Climate Dynamics, 2026)

Comprehensive phytochemical profiling, antibacterial, antioxidant, and in-silico evaluation of Aster thomsonii C.B. Clarke essential oil from the Kumaun Himalaya Region, Uttarakhand - Asha; Sandeep Kumar; Mukesh Samant; Charu Chandra Pant; Pritee Pant; Aashish Kumar Sagar; Devendra Singh Dhami (Natural Product Research, 2026)

Extraction of PCR amplifiable DNA from oil, fat and meat samples of reticulated python (Malayopython reticulatus) for genetics and forensics applications - Tannu Balhara; Deepesh Saini; Velmurugan Kodeeswaran; Chinnasamy Ramesh; Sandeep Kumar Gupta (Conservation Genetics Resources, 2026)

Evaluation of MERRA-2 PM2.5 species at three locations in India and their historical (1999–2019) trends - Sandeep Devaliya; Sayak Patra; Prem Maheshwarkar; Ankur Bhardwaj; Diksha Haswani; Deeksha Shukla; Ramya Sunder Raman; Abisheg Dhandapani; R. Naresh Kumar; Jithin K. P.; Lokesh Kaggere (Environmental Monitoring and Assessment, 2026)

Ecological safety evaluation of antibiotics of aquaculture importance through microalgal bioassay with Chlorella marina - Satheesha Avunje; Cherian Tijo; Kizhakkekarammal Puthiyedathu Sandeep; Thangaraj Sathish Kumar; Priyadharshini Raju; Prasanna Kumar Patil (Aquaculture, 2026)

Immune impairments in the offspring following parental cadmium exposure in Drosophila melanogaster - Faiz Hanif Shaikh; Leonard Clinton D'Souza; Sandeep Kumar; Sneha Sujith; Anurag Sharma (Journal of Environmental Sciences, 2026)

Geospatial, geophysical & geotechnical investigation of glacial depositions in Sikkim Himalayas - Sandeep Kumar Mondal; Hrik Chaudhury; Deepali Anand; Rishikesh Bharti; Abhishek Kumar; Arindam Dey (Natural Hazards, 2026)

A Deep Learning Approach for Automated Building Footprint Extraction from Cartosat Imagery - Kakali Deka; Kshama Gupta; Surendra Kumar Sharma; Ashutosh Bhardwaj; Bhoomika Ghale; Sandeep Maithani (Journal of the Indian Society of Remote Sensing, 2026)

Assessing Soil Contamination and Modeling Trace Element Uptake in Seed Spices of Rajasthan - Chetan Kumar Jangir; O. P. Aishwath; P. S. Sangwan; Dheeraj Panghaal; Harendra Kumar Yadav; Sanjay Kumar; S. N. Saxena; Vasundhara Sharma; Sandeep Kumar; Ram Swaroop Meena (International Journal of Environmental Research, 2026)

Harnessing plant growth-promoting bacteria (PGPB) for the rehabilitation of metal-contaminated soil - Ravinder Singh; Sandeep Kumar; Sachchidanand Tripathi; Rajkumari Sanayaima Devi (Biodegradation, 2026)

Impact of Integrated Nutrient Management On the Agronomic Performance and Yield of Guava Cv. Hisar Safeda - Minakshi Kumari; Nikesh Chandra; Rohit Sharma; Sandeep Kumar Singh; Santosh Kumar; Praveen Kumar Yadav; Rupinder Kaur; Purvika; Amritpal Singh (Applied Fruit Science, 2026)

Proteomic Analysis gives Novel Insights into Candida Albicans Morphogenesis in the Wake of Ubiquitin Mutation UbEP42 - Sandeep Kumar Dantuslia; Bhoomi Prajapati; C. Ratna Prabha (Cell Biochemistry and Biophysics, 2026)

Persistence With Botulinum Neurotoxin Type A and Factors Associated With Discontinuation: A Retrospective Cohort Study - Michael Wainberg; Jinming Zhang; Simon Page; Nivedita Rangarajan; Sandeep Kumar; Jonathan Bouchard; Amandeep Mann; Mathieu Beneteau; Billie Schultz (Toxicon, 2026)

Development and evaluation of recombinant protective antigen (rPA)-based indirect-ELISA for sero-monitoring of anthrax-specific antibodies in sheep - Sripada Sairam; Roopa Anandamurthy Hemanth; Suresh Bindu; Mandrira Ramakrishna Namrutha; Anand Shirisha; Pillenahalli Sadashivappa Pooja; Awadhesh Prajapati; Revanaiah Yogisharadhya; Nihar Nalini Mohanty; Sandeep Kumar Singh; Mohammed Mudassar Chanda; Sathish Bhadravati Shivachandra (Research in Veterinary Science, 2026)

Excavating superior grain quality with aroma in doubled haploids derived from hybrid rice - Sudhansu Sekhar Bhuyan; Nupur Naik; Byomkesh Dash; Sandeep Kumar Singh; Prachitara Rout; Ramlakhan Verma; Jawahar Lal Katara; Chidambaranathan Parameswaran; Basavantraya Navadagi Devanna; Awadhesh Kumar; Sanghamitra Samantaray (Plant Gene, 2026)

Advances in carbon capture, conversion, and utilization: A review of sustainable chemical production pathways - Sandeep R. Sahu; Neetu Vishwakarma; Nancy Sharma; Prabal Pratap Singh; Karan Singh; Dinesh Kumar; Mukesh Kumar; Ajit Sharma (Journal of Environmental Management, 2026)

Exploring high-pressure CO2/CH4 separation performance with CALF-20: A Zn-based MOF - Sandeep Kumar; Sejin Park; Sungyeop Jung; Hyunchul Oh (Gas Science and Engineering, 2026)

High-performance, temperature retardant and hydrophobic BiCoO₃:PDMS piezoelectric nanogenerator for effective energy harvesting in harsh environments - Dhiraj Kumar Bharti; Sandeep Kumar; Jitendra Pratap Singh (Chemical Engineering Journal, 2026)

Carcinogenic and non-carcinogenic health risk assessment of river Ganges in different climatic conditions and regions of Uttarakhand, India - Prashant Kumar; Ashish Kothari; Shashi Ranjan Mani Yadav; Sandeep Kumar; Anindita Mandal; Garima Mamgain; Balram Ji Omar; Ajeet Singh Bhadoria; Bhupender Singh; Ankur Kumar; Anissa Atif Mirza (The Nucleus, 2026)

Effect of Reclamation Approaches on the Soil Properties and Performance of the Rice-Wheat Cropping System Under Alkali Irrigation - Anu Sehrawat; Nirmalendu Basak; Arvind Kumar Rai; Priyanka Chandra; Parul Sundha; Sandeep Bedwal; Devvrat Dhiman; Mukesh Yadav; Rajender Kumar Yadav (Journal of Soil Science and Plant Nutrition, 2026)

Melatonin Mediated Modulation of Antioxidant Defense Machinery, Nutrient Homeostasis and Cellular Viability in Hordeum vulgare L. Under Cadmium Stress - Sandeep Kumar Barwal; Sajad Hussain Shah; Md Atikur Rahman; Yerramilli Vimala (Journal of Soil Science and Plant Nutrition, 2026)

Waste to Wealth: Acidulated Organic Manures for Enhanced Productivity and Nutrient–Supplying Capacity of Alkaline Soils - Sandeep Bedwal; Nirmalendu Basak; Arvind Kumar Rai; Parul Sundha; Priyanka Chandra; Dev Raj; Anita Mann; Subedar Patel; Harspreet Kaur; Sanjay Kumar; Raksh Vir Jasra; Rajender Kumar Yadav (Journal of Soil Science and Plant Nutrition, 2026)

Rare Earth Elements geochemistry of Gomati river sediments: Implications of subsurface tectonism, Ganga Alluvial Plain, India - Jitendra Kumar Yadav; Mukul Raj Gupta; Munendra Singh; Sandeep Singh (Journal of Sedimentary Environments, 2026)

Correction: Plant Growth Promoters and Genotype: Strategies to Enhance Growth, Productivity and Profitability of Wheat in Semi-Arid Ecologies of India - Sunil Kumar Prajapati; V. K. Verma; Dinesh Kumar; Sandeep Gawdiya; Shivendra Singh; Gurwaan Singh; Nausad Khan; M. Z. Siddique; Nilutpal Saikia; Sk Asraful Ali; Deo Narayan Singh; Shikhar Verma; et al. (Journal of Plant Growth Regulation, 2026)

Plant Growth Promoters and Genotype: Strategies to Enhance Growth, Productivity and Profitability of Wheat in Semi-Arid Ecologies of India - Sunil Kumar Prajapati; V. K. Verma; Dinesh Kumar; Sandeep Gawdiya; Shivendra Singh; Gurwaan Singh; Nausad Khan; M. Z. Siddique; Nilutpal Saikia; Sk Asraful Ali; Deo Narayan Singh; Shikhar Verma; et al. (Journal of Plant Growth Regulation, 2026)

Pre-Treatment with Abscisic Acid Enhances Multi Pathogen Stress Tolerance in Piper Betle Through Extensive Gene Downregulation - Sandeep Kumar Chaurasia; Chinmayee Acharya; Jitendra Kumar Pandey (Journal of Plant Growth Regulation, 2026)

Agronomic performance, grain quality and water productivity of basmati rice (Oryza sativa L.) under sixteen years long-term organic production system - Anita Kumawat; Dinesh Kumar; Y. S. Shivay; Devideen Yadav; M. Madhu; Shakir Ali; Sandeep Gawdiya; Ashok Kumar; Rahul Sadhukhan; R. A. Jat (Paddy and Water Environment, 2026)

Resistance-based exercise restores muscle health in dialysis patients - Piush Srivastava; Sunil Kumar Singh; Rakesh Sathish Nair; Saket Jha; Navin Viswakarma; Deepti Srivastava; Greg Hachaj; Stephen T. Bartlett; Ilaria Santi; Aslam Ejaz; Robert W. Motl; Enrico Benedetti; et al. (Journal of Muscle Research and Cell Motility, 2026)
Chronic kidney disease (CKD) and end-stage renal disease (ESRD) are serious health concerns worldwide that require regular dialysis before a kidney transplant for a better quality of life. Due to aging and frailty, dialysis patients are often limited in physical activity, which can lead to multiple health complications and sometimes result in patient death. Therefore, maintaining muscle health is crucial for individuals undergoing dialysis. We recently reported that personalized resistance-based exercise can improve frailty in dialysis patients; however, the molecular mechanisms underlying its effects on muscle health remain unknown. RNA-Seq analysis revealed that exercise upregulates genes associated with muscle stemness, regeneration, and differentiation. Furthermore, our study demonstrated that exercise upregulates mitochondrial proteins involved in the oxidation of organic compounds and mitochondrial function in muscle. Moreover, we observed that exercise increased energy production via glucose uptake, glycogenesis, and fatty acid metabolism. These results suggest that personalized resistance-based muscle therapy in dialysis patients restores the expression of genes and proteins associated with muscle stemness, regeneration, differentiation, and energy generation.

Effects of salinity, sex ratio, tank colour and live feed regimes on the captive seed production of the ornamental tiger dwarf goby, Mugilogobius tigrinus (Larson 2001) - Geo Ben Kuriakose; Dani Thomas; Sandeep Kizhakkekarammal Puthiyedathu; Raymond Jani Angel Jesudhas; Ezhil Padmakumar; Meenakshi Sani; Thiagarajan Govindarajan; Kailasam Muniyandi; Kuldeep Kumar Lal (Aquaculture International, 2026)

Nature’s fury: The deadly landslides saga in Uttarakhand Himalaya - Yaspal Sundriyal; Sandeep Kumar; Anirudh Chouhan; Sameeksha Kaushik (Journal of Earth System Science, 2026)

Chlorine-UV hybrid disinfection: a review on mechanisms and efficiency towards emerging pollutants - Sandeep Singh Shekhawat; Rahul Kumar Goswami; Akhilendra Bhushan Gupta; Faizal Bux (Environmental Science and Pollution Research, 2026)
This review comprehensively evaluates the direct and indirect disinfection mechanisms and performance of chlorine-UV hybrid disinfection (CUV-HD) for the removal of microbial and emerging contaminants, including post-disinfection regrowth and formation potential of disinfection byproducts (DBPs), to ensure safe reuse of treated effluents. Direct disinfection reactions are mediated by HOCl and OCl⁻, as well as UV-induced photolytic damage. In contrast, indirect inactivation is driven by reactive oxygen species (ROS), particularly ∙OH, and reactive chlorine species (RCS) such as Cl∙, ClO∙, and Cl₂∙⁻. The order of reactive species generation indicates UV/chlorine > chlorine–UV > UV–chlorine, which is supported by the effective reduction potential and, consequently, the disinfection efficacy against microbial pollutants in treated wastewater. However, the water matrix, including pH, temperature, organic matter, and total suspended solids (TSS), significantly influences both the disinfection efficiency of these hybrid strategies and the potential formation of disinfection byproducts (DBPs). The formation potential of DBPs follows the order: UV/chlorine > UV–chlorine > chlorine–UV. Further studies quantifying reactive chlorine species (RCS) and elucidating their roles in CUV-HD are needed to fully understand the underlying indirect disinfection mechanisms.

Exploration of smart E-transportation system research aspects in the quantum realm - Monika; Sandeep Kumar Sood (Environment, Development and Sustainability, 2026)

Ascorbate formulation promotes wound healing in goat model: Insights into molecular dynamics through cytokine modulation and angiogenic marker expression - Ajay Kumar Sharma; Aman Kalonia; Amit Shukla; Priyanka Shaw; Soumen Choudhury; Drishiya Vats; Mukul Anand; Shyama N. Prabhu; Shalini Vaswani; Sandeep Kumar Shukla (Tissue and Cell, 2026)

Design and performance analysis of SPR sensor using black phosphorus and cadmium materials-based structure for real-time glucose detection in urine samples - Arun Karthik Lanka; Sandeep Boddu; Yesudasu Vasimalla; Balaji Ramachandran; Prabakaran N; Santosh Kumar (Next Research, 2026)

In vitro hepatoprotective effects of rutin on HepG2 cells, isolated from an unexplored species: Miliusa tomentosa (Roxb.) J. Sinclair - C Inchara Moodbagil; P Meghana; Jain R Sandeep Kumar; N Prashanth; R Sharath; N.D. Satyanarayana; B Manjunatha; H Raja Naika; M.S. Savinaya; Riaz Mahmood; H.M. Kumaraswamy (Next Research, 2026)

Immunomodulatory activity of proline rich polypeptides of indigenous cattle (Bos indicus family) and Holstein Friesian (Bos taurus) and their crossbred Karan Fries cattle: A comparative study - Vivek Kumawat; Gunjan Sadera; Satish Kumar; Shubhalaxmi Pande; N. Sandeep; Usha Devi; Suman Kapila; M.H. Sathish Kumar; S.A. Hussain (International Dairy Journal, 2026)

Biomass gasification in an industrial-scale entrained flow gasifier and effects of various parameters on gasification performance: An approach based on numerical models - Kuntalika Das; Sandeep Kumar; Sankar Bhattacharya (Fuel, 2026)

Understanding radon behaviour in traditional Indian dwellings: Insights from a validated CFD study of a representative mud test house - Rajat Parkash; Sandeep D. Kanse; Tarun Kumar Agarwal; Rosaline Mishra; Manish Joshi; R.P. Chauhan (Environmental Pollution, 2026)

Comparative metabolomics-based screening of fruit extracts of less-known melon ( Cucumis melo var . agrestis) accessions collected from dry terrain of North India by using HPLC–DAD - Chanchal Sharma; Jyoti Rani; Manish Kapoor; Navneet Kaur; Sandeep Gawdiya; Saroj Kumar Pradhan (Natural Product Research, 2026)

Outbreak of Hyposidra talaca Walker (Lepidoptera: Geometridae) as a new sporadic pest of mango in Northern India: Insights from morphological, molecular, and ecological studies - Snehasish Routray; H. S. Singh; R. Verma; Y. Kumar; Keerthi. M.C.; Sandeep Singh (Phytoparasitica, 2026)

Sustainable Approach for Oil Spill Cleanup Using Waste Coconut Husk-Based Oleophilic Nanogels - Kavita Devi; Kiran Kumar; Ghanshyam S. Chauhan; Sandeep Chauhan; Anamika Ramchaik (International Journal of Environmental Research, 2026)

Molecular Taxonomy Suggests Presence of Two Distinct Lineages of Blue Sheep (Pseudois nayaur) in Indian Himalayan Region - Deepesh Saini; Gaurav Sonker; Tushar Parab; Vishnupriya Kolipakam; Sambandam Sathyakumar; Salvador Lyngdoh; Sandeep Kumar Gupta (Biochemical Genetics, 2026)

Plant growth promoting rhizobacteria (PGPR) mediated amelioration of plant tolerance to abiotic stresses: Drought, salinity, and heavy metals - Indu Dhiman; Nandni; Vikram Poria; Shubham Kumar; Ravina Yadav; Tabasum Shaik; Sandeep Bedwal; Leela Wati (Archives of Microbiology, 2026)

Synergistic Application of Nano-micro and Macronutrients in Wheat Alleviated Drought Stress with Enhanced Physiological Response and Anti-oxidant Enzyme Activity - Garima Chauhan; Anil Kumar; Tarun Sharma; Akashdeep Singh; Bharat Bhushan Rana; Sandeep Manuja (Journal of Plant Growth Regulation, 2026)

Landscape factors and nesting structure influence productivity in a raptor on the eastern coast of India - Sakti P. Pattnayak; Biswajit Samantaray; Sandeep Rout; B. Anjan Kumar Prusty; Taej Mundkur (Journal for Nature Conservation, 2026)

Development of a visual assay for Mithun (Bos frontalis) meat authentication using polymerase spiral reaction (PSR) - Moon Moon Mech; Hanumant Singh Rathore; Arockiasamy Arun Prince Milton; Nagappa Karabasanavar; Kandhan Srinivas; Sabia Khan; Zakir Hussain; Vikram Ramesh; Harshit Kumar; Samir Das; Sandeep Ghatak; Girish Patil Shivanagowda (Food Control, 2026)

Retraction notice to ‘Hazardous heavy metals contamination of vegetables and food chain: Role of sustainable remediation approaches - A review’ [Environ. Res. Volume 179, Part A, December 2019, 108792] - Sandeep Kumar; Shiv Prasad; Krishna Kumar Yadav; Manoj Shrivastava; Neha Gupta; Shivani Nagar; Quang-Vu Bach; Hesam Kamyab; Shakeel A. Khan; Sunita Yadav; Lal Chand Malav (Environmental Research, 2026)

Do the adoption of crop residue management technologies have favourable economic and environmental outcomes? Some insights from Indo-Gangetic Plains of India - Parvender Sheoran; Kiran Kumara TM; Ashish S. Murai; Suresh Kumar; Arvind Kumar; Rajbir Singh; Vinita Kanwal; Sandeep Kumar; Har Narayan Meena; Jai Parkash Mishra; Santanu K. Dubey; KJ Raghavendra; et al. (European Journal of Agronomy, 2026)

Evaluation of ERA5 boundary layer height against radiosonde measurements: Regional drivers, spatiotemporal variability, and trends over the Indian Monsoon Region - Hemanth Kumar Alladi; A. Sandeep; Prasad P.; Balasundhar Bv (Atmospheric Research, 2026)

Assessing wind energy potential during monsoon deep depressions using WRF Multi-Physics Ensemble over Odisha - Shakti Sagar Srivastav; Sandeep Pattnaik; Deepak Kumar; Anshul Sisodiya (Theoretical and Applied Climatology, 2026)

Beyond nutrition: a two-decade systematic review of the ethnopharmacological potential and therapeutic promise of Amaranthus sp. - Suman Dutta; Rohan Sarkar; Nabanita Saha; Manish Kumar Suthar; Sandeep Gawdiya; Malini Roy Choudhury; Sourav Garai; Debashis Paul; Sumanta Das (Phytochemistry Reviews, 2026)

Hepatoprotective potential of Urochloa distachya (L.) ethanol extract against paracetamol and CCl4-induced liver injury in rats - Smrutiranjan Dash; Rajasekaran Sidhan; Sandeep Kumar Mishra; Santosh Kumar Prajapti (Inflammopharmacology, 2026)

Metagenomics and its impact on environmental and therapeutic microbiology - Sandeep Kaur Saggu; Manoj Kumar; Shiv Kumar (Archives of Microbiology, 2026)

Polystyrene nanoplastic exposure increases susceptibility of Pseudomonas aeruginosa infection in Caenorhabditis elegans model of host-pathogen interaction in p38-MAP Kinase dependent manner - Acharya Balkrishna; Saurabh Bhatti; Sandeep Kumar; Manisha Kabdwal; Kunal Bhattacharya; Savita Lochab; Rishabh Dev; Anurag Varshney (Chemosphere, 2025)

Synergistic control of Pseudomonas aeruginosa biofilms using Limosilactobacillus fermentum and preservation factors - Sayanti De; Priyadarshini P. Nayak; Ankita Nayak; Shradha Garnaik; Santosh Kumar; Sanjukta Das; Sethuraman Sivakumar Paramasivan; Raju Sasikumar; Sandeep K. Panda (Food Bioscience, 2025)

Extraction of gum from fenugreek seeds: Structural composition and rheological characterization - Navjot Kaur; Hamid; Rafeeya Shams; Kshirod Kumar Dash; Poonam Choudhary; Sandeep Mann; Pintu Choudhary (Food and Humanity, 2025)

Constructed wetlands as a sustainable solution for pesticide pollution mitigation - Jyoti Singh; Mahima Choudhary; Rajesh Singh; Sujata Kashyap; Vinay Kumar Tyagi; Kalzang Chhoden; Sandeep Singh (Current Opinion in Environmental Science & Health, 2025)

Comparative paddy straw degradation potential of Psychrotrophic Fungal Consortia and Pusa Decomposer at low temperatures - S.T.M. Aravindharajan; Livleen Shukla; D. Vijaysri; Sandeep Kumar Singh; Reetesh Kumar; Rajesh Kumar; Shalini Gaur Rudra; Gautam Chawla; Ajay Kumar (Bioresource Technology Reports, 2025)

Beneficial cyanobacteria as seed coatings to enhance the storability and viability indices of spinach seeds - Ravi Mourthy Nivedha; Radha Prasanna; Mujtahida Khatun; Deepti Varsha; Akanksha Bhardwaj; Sandeep Kumar Lal; Sudipta Basu; Samrat Rej; Awani Kumar Singh; Yashbir Singh Shivay (Biocatalysis and Agricultural Biotechnology, 2025)

Spatial and Temporal Variations in Ganga River Water Quality: Insights from GIS Analysis (2017–2021) - Bhupendra P. Singh; Priyanka Khichi; Preeti Sai; Sandeep Kumar Gautam; Seema Chahal; Jyotsana Gupta (Water, Air, & Soil Pollution, 2025)

3D CoAt U SegNet-enhanced deep learning framework for accurate segmentation of acute ischemic stroke lesions from non-contrast CT scans - Manas K. Nag; Anup K. Sadhu; Samiran Das; Chandan Kumar; Sandeep Choudhary (Physical and Engineering Sciences in Medicine, 2025)

Artemisinin’s molecular symphony: illuminating pathways for cancer therapy - Sandeep Kumar Jhade; Karthik Kalidoss; Poonam Kumari Pathak; Rahul Shrivastava (Molecular Biology Reports, 2025)

Motor imagery-based neural networks for assisting tetraplegic patients - Prabhakar Agarwal; Sandeep Kumar; Rishav Singh (Medical & Biological Engineering & Computing, 2025)

Landslide Susceptibility Analysis of a Part of Western Ghats in South-Western India Using Geospatial Techniques: A Comparison of AHP and Logistic Regression Methods - Rashmi Chandan; Kizhur Sandeep; Chandan Kumar Boraiaha (Journal of the Indian Society of Remote Sensing, 2025)

Spatio-temporal variation of microplastics during the past four decades in a lacustrine sedimentary environment in southern India - G. H. Aravind; R. S. Mahidev; A. K. Rafaz; K. Sandeep; A. V. Sijinkumar; Anish Kumar Warrier (Journal of Sedimentary Environments, 2025)

Activation of Induced Systemic Resistance in Cotton Plants Against Fusarium and Macrophomina by Microbial Antagonists - Vikram Poria; Prakriti Jhilta; Sandeep Kumar; Anuj Rana; Kumar Pranaw; Surender Singh (Journal of Plant Growth Regulation, 2025)

Unveiling genetic variation among Bharal (Pseudois nayaur) in the Indian Himalayas using nuclear markers - Deepesh Saini; Gaurav Sonker; Pooja Pant; Vishnupriya Kolipakam; Sambandam Sathyakumar; Salvador Lyngdoh; Sandeep Kumar Gupta (Genetica, 2025)

Eco-restoration potential of native metallophytes through multivariate assessment: a case study in Sukinda Chromite Mines, India - Ankita Das; Dharitri Mishra; B. S. Manisha Singh; Kalicharan Mandal; Sandeep Kumar Kabi; Nabin Kumar Dhal (Environmental Monitoring and Assessment, 2025)

Glycine betaine-induced tolerance in wheat plant under Cd and As stress by optimizing growth and biochemical profile - Sandeep Kumar; Jyoti Sharma; Sunder Singh Arya; Anju Ahlawat; Kirpa Ram (Cereal Research Communications, 2025)

Evaluation of antileukemic potentials of maslinic acid through targeting responsive proteins of human leukemia: a mechanistic perception on molecular modelling and dynamic stimulations - Jhimli Banerjee; Sovan Samanta; Michael Afiadenyo; Rubai Ahmed; Swarnali Das; Sk Nurul Hasan; Sandeep Kumar Dash (In Silico Pharmacology, 2025)

Enhancing sustainable concrete performance: dual treatment of recycled coarse aggregates for improved strength and durability - Harish Panghal; Sandeep Chaudhary; Awadhesh Kumar (European Journal of Environmental and Civil Engineering, 2025)

Improved dewatering behaviour of bauxite residue using calcium-magnesium-impregnated acid solution - Sandeep Kumar Jena; Baijayantimala Mohanty; Ranil Bahalia; Sapan Kumar Kandi (Environmental Science and Pollution Research, 2025)

Applications of artificial intelligence in the dairy Industry: From farm to product development - Anandu Chandra Khanashyam; Sandeep Jagtap; Tarun Kumar Agrawal; Priyamvada Thorakkattu; Om Prakash Malav; Hana Trollman; Abdo Hassoun; Bharathi Ramesh; Vishnu Manoj; Kaavya Rathnakumar; Alaa El-Din A. Bekhit; Nilesh Nirmal (Computers and Electronics in Agriculture, 2025)

Trade-offs between global warming potential, eco-efficiency and water use efficiency under different establishment methods and nitrogen management strategies for sustainable rice production - S.N. Sandeep; P.S. Fathima; S.B. Yogananda; R. Suma; K.V. Shivakumar; B.S. Sowmyalatha; P. Thimme Gowda; Hanamant M. Halli; Manjanagouda S. Sannagoudar; E. Senthamil; Vinay M. Gangana Gowdra; B. Raghavendra Goud; et al. (Science of The Total Environment, 2025)

Factors governing irrigation water productivity of rice in northwestern India: evidence from farmers’ fields - Proloy Deb; Anton Urfels; Virender Kumar; Prakashan Chellattan Veettil; Amit Kumar Srivastava; Swatantra Kumar Dubey; Panneerselvam Peramaiyan; Sudhanshu Singh; Sandeep Rawal; Satyendra Kumar; Rajbir Garg; Baldev Raj Kamboj; et al. (Journal of Environmental Management, 2025)

Natural alkaloid solasodine mitigates fibrotic lung injury caused by polyethylene microplastics through modulation of TGF-β1/Smad pathway - Nishant Singh; Rohit Kumar Gautam; Laltanpuia; Shivani Bhardwaj; Sandeep Saini; Itishree Dubey; Sree Vaishnavi Nalla; Sapana Kushwaha (Food Bioscience, 2025)

Is individual or combination of three Indian major carps (Catla catla, Labeo rohita, and Cirrhinus mrigala) preferable secondary co-species in semi-intensive polyculture with pabda (Ompok bimaculatus)? - Maibam Malemngamba Meitei; Arun Bhai Patel; Soibam Khogen Singh; Pradyut Biswas; Sandeep Kumar Behera; Anil Datt Upadhyay (Aquaculture International, 2025)

The Distribution and Dispersal of Large Haploblocks in a Superspecies - Darren Irwin; Staffan Bensch; Caleigh Charlebois; Gabriel David; Armando Geraldes; Sandeep Kumar Gupta; Bettina Harr; Paul Holt; Jessica H. Irwin; Vladimir V. Ivanitskii; Irina M. Marova; Yongchao Niu; et al. (Molecular Ecology, 2025)
Haploblocks are regions of the genome that coalesce to an ancestor as a single unit. Differentiated haplotypes in these regions can result from the accumulation of mutational differences in low‐recombination chromosomal regions, especially when selective sweeps occur within geographically structured populations. We introduce a method to identify large well‐differentiated haploblock regions (LHBRs), based on the variance in standardised heterozygosity (ViSHet) of single nucleotide polymorphism (SNP) genotypes among individuals, calculated across a genomic region (500 SNPs in our case). We apply this method to the greenish warbler ( Phylloscopus trochiloides ) ring species, using a newly assembled reference genome and genotypes at more than 1 million SNPs among 257 individuals. Most chromosomes carry a single distinctive LHBR, containing 4–6 distinct haplotypes that are associated with geography, enabling detection of hybridisation events and transition zones between differentiated populations. LHBRs have exceptionally low within‐haplotype nucleotide variation and moderately low between‐haplotype nucleotide distance, suggesting their establishment through recurrent selective sweeps at varying geographic scales. Meiotic drive is potentially a powerful mechanism of producing such selective sweeps, and the LHBRs are likely to often represent centromeric regions where recombination is restricted. Links between populations enable introgression of favoured haplotypes and we identify one haploblock showing a highly discordant distribution compared to most of the genome, being present in two distantly separated geographic regions that are at similar latitudes in both east and central Asia. Our results set the stage for detailed studies of haploblocks, including their genomic location, gene content and contribution to reproductive isolation.

Establishment of the Thyroid Reference Intervals for the Pediatric Population in the Coastal Karnataka: A Pilot Study - Sandeep Kumar; Inesh Vij; Monalisa Biswas; Vijetha Shenoy Belle; Krishnananda Prabhu (Indian Journal of Clinical Biochemistry, 2025)

Exogenous melatonin improves blastocyst developmental competence and levels of antioxidants in indigenous donor cattle under heat stress - Anupama Solanki; Anand Kumar Pandey; Hitesh Jangra; Pradeep Saini; Sandeep Kumar; Ramakant Kaushik; Meenakshi Virmani; Rajesh Kumar; Rahul Verma; Yogesh Bangar (Theriogenology, 2025)

Real-time earthquake magnitude estimation utilizing a mixed dataset set of observed and simulated P-wave onsets for the Kumaon Himalaya from Mw3.0–7.5 earthquakes - Suraj Kumar Pal; S. Devi; Sandeep; P. Kumar; A. Joshi; Monika; R. Kumar (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Sediment provenance of megaflood events in the Yarlung-Tsangpo-Brahmaputra: Integrating petrography, Sr-Nd geochemistry, and U-Pb zircon chronology - Sandeep Panda; Anil Kumar; Saurabh Singhal; Pradeep Srivastava; Satyabrata Das (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A worldwide aerosol phenomenology: Elemental and organic carbon in PM2.5 and PM10 - Jean-Philippe Putaud; Fabrizia Cavalli; Karl Espen Yttri; Judith C. Chow; John G. Watson; Baerbel Sinha; Chandra Venkataraman; Fumikazu Ikemori; Jean-Luc Jaffrezo; Gaelle Uzu; Isabel Moreno; Radovan Krejci; et al. (Atmospheric Environment, 2025)

QTL mapping using a high-density SNP map and development of KASP markers for MYMIV resistance in mungbean (Vigna radiata L.) - Chayanika Lahkar; Ranjit Kaur Gill; Sandeep Kaur Dhaliwal; Parteek Kumar; Deepika Narang; Dharminder Bhatia; Asmita Sirari; Satinder Kaur (Theoretical and Applied Genetics, 2025)

Observed changes in rainfall extremes and current trends in Gandhinagar district, Gujarat - Sandeep Kumar; Bhawana Pathak (Theoretical and Applied Climatology, 2025)

In silico studies on nicotinamide analogs as competitive inhibitors of nicotinamidase in methicillin-resistant Staphylococcus aureus - Jaikee Kumar Singh; Jai Singh; Ishita Jha; Tarini Rajput; Saurabh Srivastava; Sandeep Kumar Srivastava (Molecular Diversity, 2025)

Design, synthesis and evaluation of benzothiazole-derived phenyl thioacetamides as dual inhibitors of monoamine oxidases and cholinesterases - Sandeep Kumar; Rangan Mitra; Senthil Raja Ayyannan (Molecular Diversity, 2025)

Unveiling genetic differentiation of Tibetan argali (Ovis ammon hodgsoni) from other subspecies: insights into genetic diversity and phylogenetics of eastern Himalayan population - Deepesh Saini; Himanshi Upadhayay; Tushar Parab; Vishnupriya Kolipakam; Sandeep Kumar Gupta (Mammal Research, 2025)

Contamination profile and potential human health risks of radon in groundwater of southwest region of Punjab, India - Sandeep Singh; Sandeep K. Malyan; Kaptan Singh; Sujata Kashyap; Rajesh Singh; S. P. Rai; Sumant Kumar; Pradeep Kumar (Environmental Geochemistry and Health, 2025)

Mineralogical and geochemical proxies from sediment cores to understand paleoclimate and sea level changes along the southwest coast of India - S. Sreekesh; Meenakshi; Sreerama Naik S R; Pankaj Kumar; Sandeep Sarpal (Applied Geochemistry, 2025)

Chrysin, a glycolytic inhibitor, modulates redox homeostasis during aging via a potent calorie restriction mimetic effect in male wistar rats - Akanksha Singh; Sakshi Jaiswal; Raushan Kumar; Nitin Mishra; Sandeep Kumar Yadav; Syed Ibrahim Rizvi (Biogerontology, 2025)

Optimizing tree spacing and nutrient management for marigold cultivation under Mangifera indica-based agroforestry system in submontane low hill zone of the North-Western Himalaya - Sahil Chauhan; Vipan Guleria; Prem Prakash; Shreya Chauhan; Avinash Kumar Bhatia; Hitesh Gupta; Sandeep Kumar; Ankita Chauhan (Agroforestry Systems, 2025)

Mitigating dust deposition effects on solar panels: an experimental approach using hydrophobic coating and vibration - Himanshu Kumar; Sandeep Yadav; Abhilasha Chaudhary; Sumit Sharma; Anita Kuradiya (Environmental Science and Pollution Research, 2025)

Changing land use and land cover dynamics in Chhilchhila Wildlife Sanctuary, Haryana, India: a winter migratory bird study - Piyush Goyal; Deepak Rai; Sandeep Kumar (Environmental Monitoring and Assessment, 2025)

MicroRNAs associated with spot blotch in bread wheat (Triticum aestivum) - Neeraj Kumar Vasistha; Sandeep Sharma; Vinod Kumar Mishra; Tinku Gautam; Gautam Saripalli; Sunita Pal; Pushpendra Kumar Gupta (Physiological and Molecular Plant Pathology, 2025)

Investigation of the high frequency attenuation parameter kappa (κ) beneath the volcanic region of Kyushu using surface and borehole dataset - Sandeep; Sonia Devi; Pragya Singh; U.P. Singh; S.K. Pal; P. Kumar; Monika; A. Kumar; H. Mittal (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

QbD-driven extraction and purification of piceatannol from passion fruit seeds and its cubosomes development, characterization, and neuronal cellular analysis - Navratan Soni; Sandeep Jat; Ankaj Kumar; Arvind Gulbake; Manini Bhatt; Bodhisatwa Das; Ramkishore Matsa; Pratik Vilas Gore; Dnyaneshwar Maykar; Pramod Kumar (Food Bioscience, 2025)

Preparation, characterization and pharmacokinetic assessment of Diosmetin solid lipid nanoparticles: A bioanalytical approach using LC-MS/MS - Sachin Dattram Pawar; Swati Ramesh Pawar; Komal Gawali; Sandeep Jat; Pooja Singh; Shreyash S. Yadav; Ashok Kumar Datusalia; Hitesh Kulhari; Pramod Kumar (Food Bioscience, 2025)

Microsatellite Marker–Driven Genetic Diversity and Breeding Potential Assessment in Okra (Abelmoschus esculentus (L.) Moench): A Multi-parent Approach - N. Sandeep; B. M. Dushyantha Kumar; Anilkumar Lalasing Chavan (Plant Molecular Biology Reporter, 2025)

Phenotyping of diverse rice genotypes for low phosphorus stress tolerance under soil environment - Neha Anand; Sandeep Sharma; Monu Kumar; Tarun Kumar; Sanjay Kalia; Renu Pandey (Plant Physiology Reports, 2025)

Extraction optimization of bioactive compounds from Vitex negundo through RSM: GC–MS, FTIR, in silico analysis, and antibacterial activity - Eti Sharma; Nisha Gaur; Sandeep Singh; Kartavya Mathur; Krishan Kumar; Nitin Wahi; Gunjan Garg (Journal of Plant Biochemistry and Biotechnology, 2025)

A Highly Drug-Resistant Salmonella Enterica Serovar Weltevreden of Human Origin from India and Detection of its Virulence Factors - Sandeep Kumar; Yashwant Kumar; Gaurav Kumar; Gulshan Kumar; Dimple Kasana (Indian Journal of Microbiology, 2025)

Phytoplankton functional groups regulated by hydrological parameters in cascading reservoirs of the subtropical Ganga River, India - Jeetendra Kumar; Basanta Kumar Das; Asha Taterao Landge; Absar Alam; Ajoy Saha; Shashi Bhusan; Sandeep Kumar Mishra; Simanku Borah (Aquatic Ecology, 2025)

Molecular Subtyping and Classification of PIK3CA Mutations in Metastatic Breast Cancer - Amrit Kaur Kaler; Manish Jethani; Mandar Nadkarni; Yash Tiwarekar; Varsha Balaji; Tanmay Wairkar; Bijal Kulkarni; Nevitha Athikari; Shalaka Satpute; Ratika Agarwal; Shruthi Kumar; Vidhi Shah; et al. (Current Tissue Microenvironment Reports, 2025)

Adsorption kinetics and isotherm characteristics of phosphorus in the riverbed sediment of Ganga and Yamuna at Prayagraj, India - Shivangi Mishra; Vikas Kumar; Amitabh Chandra Dwivedi; Basanta Kumar Das; Anup Kumar; Ajoy Saha; Jeetendra Kumar; Dharm Nath Jha; Sandeep Kumar Mishra (Environmental Monitoring and Assessment, 2025)

Impact of corn stover hydrothermal liquefaction conditions on the chemical composition and aerobic fermentation of the aqueous phase - Meicen Liu; Isamu Umeda; Sandeep Kumar; Zhiwu Wang; Yi Zheng (Water Research, 2025)

Compositional characterisation of colostrum and proline rich polypeptides of indigenous cattle (Bos indicus family) and Holstein Friesian (Bos taurus) and their crossbred Karan Fries cattle - Mamta Kumari; Usha Devi; T.M. Amrutha; N. Sandeep; M.H. Sathish Kumar; Suman Kapila; Abdul S. Hussain; C.T. Manoj Kumar (International Dairy Journal, 2025)

Crop yield and resource use efficiency as influenced by crop establishment and conservation tillage in the rice-wheat cropping system - Bharat Bhushan Vashisht; Bijesh Maharjan; Sandeep Sharma; Arham Tater; Manish Yadav; Samanpreet Kaur; Surinder Kumar Jalota (Field Crops Research, 2025)

Optimized g-C3N4/TiO2 composites for visible-light-driven sonophotocatalysis in norfloxacin removal - Bharat Bhargawa; Tran Van Tam; Ashok Kumar; Sandeep Kumar Lakhera; Soon Ho Hong; Won Mook Choi; Ik-Keun Yoo (Environmental Research, 2025)

Presence of large trees and tree diversity enhances carbon storage in the Western Ghats - Nasla Najeeb; Karun Jose; K.A. Sreejith; Sandeep Pulla; H.S. Suresh; Jayashree Ratnam; H.V. Raghavendra; Dayani Chakravarthy; Rajiv Kumar Chaturvedi (Biological Conservation, 2025)

Circadian clock and its effect on aging and lifespan - Avnish Kumar Verma; Sandeep Singh; Syed Ibrahim Rizvi (Biogerontology, 2025)

Molecular Dissection of Constans (CO) Homologs and Their Regulatory Role in Floral Induction of Mango (Mangifera indica L.) - M. Muthukumar; Anju Bajpai; Kasim Khan; Yashi Bajpai; Sandeep Kumar; Sumit Kumar Soni; Laxmi; V. K. Singh; T. Damodaran (Applied Fruit Science, 2025)

Storage Stability Assessment of the Postharvest Quality of the Litchi Cultivar ‘Rose Scented’ Via Gamma Radiation and Surface Edible Coating - Nikesh Chandra; Satish Chand; Omveer Singh; Ranjan Kumar Srivastava; Ajay Singh; Bhawana Mamgain; Sandeep Kumar; Rohit Sharma (Applied Fruit Science, 2025)

A new species of Neanastatus (Hymenoptera: Chalcidoidea: Neanastatidae) from Uttarakhand, associated with stem galls of Indigofera heterantha Mill - Suman Upadhyay; Vishal Kumar; Sunaullah Bhat; Sangeeta Rawat; Sandeep Kumar (International Journal of Tropical Insect Science, 2025)

Nutritional, physicochemical and biochemical potentials of Indian cucurbit seed oils: a comparative study - Jyotsana Singh; Vinti Singh; Radha Kushwaha; Sandeep Kumar; A. K. Rai (Vegetos, 2025)

Plant's cellular response to biotic stress: A review - Sandeep Kumar Chaurasia; Chinmayee Acharya; Jitendra Kumar Pandey (Physiological and Molecular Plant Pathology, 2025)

Optimizing single and co-culture soymilk fermentation using weissella probiotics for improved nutritional and sensory quality - S.R. Arpitha; Minnu Sasi; Sandeep Kumar; Md Yeasin; Mohd Harun; Shruti Sethi; Sweta Kumari; Lata; D. Amirtham; Archana Sachdev; Anil Dahuja (Food Bioscience, 2025)

Optimization of Photocatalytic Degradation Conditions of Rose Bengal Dye Using Biomass-Derived Carbon Dots - Tripti Tripti; Arpita Arpita; Sandeep Kumar; Parmod Kumar (Water, Air, & Soil Pollution, 2025)

Estimation of the rapid intensification of tropical cyclones over the North Indian Ocean using attention-based deep learning models - Omveer Sharma; Hemant Kumar; Dhanajay Trivedi; Nikita Goswami; Sandeep Pattnaik; Niladri Bihari Puhan (Natural Hazards, 2025)

Polypharmacology and Neuroprotective Effects of Gingerol in Alzheimer’s Disease - Sakthi Priyadarshini; Keshav Goyal; Roopashree R; Saurabh Gupta; Aatreyi Roy; Ritabrata Biswas; Sandeep Patra; Payal Chauhan; Karan Wadhwa; Govind Singh; Mehnaz Kamal; Danish Iqbal; et al. (Molecular Neurobiology, 2025)

Modulation of Nitrogen (N) and Phosphorous (P) Supply Influence Arsenite [As (III)]-Induced Stress Responses in Developing Rice (Oryza sativa L.) Seedlings - Padmasri Ghosh; Seuj Priya Borah; Debojyoti Moulick; Sandeep Kumar Tata; Binaya Kumar Pattnaik; Sayak Das; Shuvasish Choudhury (Journal of Plant Growth Regulation, 2025)

Mining tailings as a frontier for sustainable nanomaterials: advancing circular economy and environmental innovation - Sukhpreet Singh; Pankaj Maurya; Amit Karmakar; Prakash Kumar Maurya; Nidhi Pandey; Sandeep Kumar; Tanish Gupta (Environmental Geochemistry and Health, 2025)

Acidulated composts govern the soil solution nutrient composition through changes in key functional bacterial community of alkaline soils - Sandeep Bedwal; Arvind Kumar Rai; Nirmalendu Basak; Priyanka Chandra; Parul Sundha; Amresh Chaudhary; Harshpreet Kaur; Subedar Patel; Sanjay Kumar; Rajender Kumar Yadav (Applied Soil Ecology, 2025)

Evolutionary Triggers of Plant Speciation in the Himalaya‐Tibet‐Hengduan Biodiversity Epicentre - Maharaj K. Pandit; Kumar Manish; Sandeep Sen; Kamaljit S. Bawa; Andrew H. Knoll; A. Alexander G. Webb; Peter D. Clift; Fabien L. Condamine; Carina Hoorn (Journal of Biogeography, 2025)
Background Past studies linking geologic and climatic controls on speciation in the Himalaya, Tibet and Hengduan (HTH) regions do not fully capture the mechanisms underlying patterns of plant diversity and endemism in hyperdiverse mountain ecosystems. Aims This study sheds new light on the orogenic and climatic drivers of plant endemism and diversity in the HTH region and unravels the mechanisms behind plant speciation and assembly. Materials & Methods We re‐examine the past findings on geo‐climatic controls on speciation in the HTH. We also analyse new datasets on the elevational patterns of endemic species richness in the HTH regions and correlate these with the hypsometric profiles based on digital elevation models of these regions. Results We discover that the phased evolution of HTH mountain‐building and climate oscillations, and species radiations were not exactly synchronous, but were interspersed with periods of inactivity. We find an inverse yet overlapping relationship between elevation‐area troughs (EATs) of hypsometric profiles and peaks of endemic plant richness in the HTH, indicating that most endemic species occupy the higher elevational belts with the least geographic areas. These elevational belts comprise geographically and biologically isolated habitats. Discussion and Conclusions We infer that orogeny, monsoon and glaciations have shaped the highly dissected HTH landscapes, characterised by high‐relief topography, leading to population isolation, speciation and endemism, albeit with temporal lags. Glacial–interglacial cycles have further promoted isolation, co‐habitation, hybridisation and polyploidy among plant populations, generating and accelerating endemic radiations. Our results provide crucial evidence linking mountain‐building, climatic events and landform development with plant species richness and endemism in the HTH regions and potentially in other mountain ecosystems.

A Computational and In Vitro Appraisal of Ostarine to Target Androgen Receptor in Glioma C6 Cells - Satvika Sharma; Sandeep Saini; Vijayta Dani Chadha; Avneet Saini; Devinder Kumar Dhawan (Cell Biochemistry and Biophysics, 2025)

Molecular docking and molecular dynamics simulation studies of thiazole-coumarin and thiazole-triazole conjugates against Mpro and ACE2 receptor for SARS COV-2 - Deepak Mishra; Ram Singh; Nupur S. Munjal; Naresh Kumar; Prashant Kumar; Poonam; Sandeep Sharma (In Silico Pharmacology, 2025)

High-resolution dynamically downscaled projections of future extreme temperatures, heatwaves and exposure in Southeast Asia - Jianjun Yu; Aurel F. Moise; Sandeep Sahany; Venkatraman Prasanna; Xin Rong Chua; Chen Chen; Muhammad E.E. Hassim; Gerald Lim; Fei Luo; Anupam Kumar; Puyang Liu; Pavan Harika Raavi (Science of The Total Environment, 2025)

First record of Mystus cavasius (Hamilton, 1822) with DNA barcoding confirmation from the upper reaches of the Beas River - Kushal Thakur; Amit Kumar Sharma; Sandeep Kumar; Dixit Sharma; Sunil Kumar; Rakesh Kumar (Ecological Genetics and Genomics, 2025)

India’s Earthquake Early Warning Systems: A Review of Developments and Challenges - Himanshu Mittal; Shanker Pal; Rajiv Kumar; Atul Saini; Yih-Min Wu; Ambikapathy Ammani; R. C. Patel; Sandeep; O. P. Mishra (Surveys in Geophysics, 2025)

Drone thermal imaging for assessing water status response of variable nitrogen and water application in wheat - Supriyo Dhara; Rajeev Ranjan; Rabi N. Sahoo; Monalisha Pramanik; Joydeep Mukherjee; Mahesh Kumar; Pravin Kumar Upadhyay; Sandeep Kumar (Plant Physiology Reports, 2025)

Inhibition of monoamine oxidases and neuroprotective effects: chalcones vs. chromones - Reshma Ipe; Jong Min Oh; Sunil Kumar; Iqrar Ahmad; Lekshmi R. Nath; Sandeep Bindra; Harun Patel; Krishna Yallappa Kolachi; Prabitha Prabhakaran; Prashant Gahtori; Asad Syed; Abdallah M. Elgorbanh; et al. (Molecular Diversity, 2025)

Mitigating Salinity Stress in Crops using Talaromyces sp.: Impacts on Phosphorus Solubilization, Growth and P Nutrition - Priyanka Chandra; Arvind Kumar Rai; Nirmalendu Basak; Parul Sundha; Sandeep Bedwal; Kailash Prajapat; Rajender Kumar Yadav (Journal of Soil Science and Plant Nutrition, 2025)

The potential of glycine betaine application to combat Cd and As toxicity in wheat plants by altering photosynthetic, physiological, and antioxidant enzyme indices - Sandeep Kumar; Jyoti Sharma; Sunder Singh Arya; Anju Ahlawat; Kirpa Ram (Cereal Research Communications, 2025)

Deep Learning in Analyzing Carbon Flux Patterns for Environmental Health: Remote Sensing Insights for Climate Mitigation Strategies - Hariharan Subramani; M. Neela Harish; Selva kumar S; P. Radhakrishnan; L. N. K. Sai Madupu; Kasturi Sai Sandeep; Divya Nimma (Remote Sensing in Earth Systems Sciences, 2025)

Buzzing for Broccoli (Brassica oleracea var. italica): Exploring Insect Pollinators, Their Behaviour, Single-Visit Efficiency and the Significance of Honey Bees in Yield Enhancement - Sunaullah Bhat; Johnson Stanley; A. R. N. S. Subbanna; Amit Umesh Paschapur; Jaiprakash Gupta; Sandeep Kumar (Agricultural Research, 2025)

Quantitative Analysis on Expression of Insecticidal Crystal Proteins in Different Plant Parts of BG-II Cotton Hybrids at Various Phenological Stages - Debashis Paul; Rishi Kumar; G. Balasubhramani; Sandeep Bagri; Subhash Chandra; S. Manickam; Satpal Singh; A. H. Prakash; Y. G. Prasad (Agricultural Research, 2025)

Cassia siamea-Derived Silver Nanoparticles: Synthesis and Their Impact on Male Fertility Through Biochemical and Histopathological Insights in Rats - Neha Bharti; Prity Yadav; Sandeep Kumar Choudhary; Rajeev Kumar Dhaked; Pratap Chand Mali (Biological Trace Element Research, 2025)

Determination of Arias intensity and modified Mercalli intensity scale for future scenario earthquake in the Uttarakhand Himalaya, India - Parveen Kumar; Sandeep; Sandeep Kumar; Monika; Narendra Kumar (Journal of Earth System Science, 2025)

Influence of Ubiquitin Mutations over Molecular Markers Contributing to Pathogenesis of Candida albicans - Sandeep Kumar Dantuslia; Ankita Doshi; Bhoomi Prajapati; C. Ratna Prabha (Cell Biochemistry and Biophysics, 2025)

Retraction Note: An update on pathophysiology and treatment of sports-mediated brain injury - Sunishtha Kalra; Rittu Banderwal; Kaushal Arora; Sandeep Kumar; Govind Singh; Pooja A. Chawla; Tapan Behl; Aayush Sehgal; Sukhbir Singh; Saurabh Bhatia; Ahmed Al-Harrasi; Lotfi Aleya; et al. (Environmental Science and Pollution Research, 2025)

Characterization and sustainable management of vector-borne viral pathogens in okra (Abelmoschus esculentus L.) - Swapnalisha Mohapatra; Sandeep Kumar; Jayaraj Padhi; Jyoti Prakash Sahoo; Satyapriya Singh; Nandini Sahu (Crop Protection, 2025)

Synthesis of Thermally Stable Psyllium Husk/4,4´-Diphenylmethane Diisocyanate-Based Polyurethanes for Effective and Selective Removal of Cationic Dyes - Kriti; Kiran Kumar; Sunita Ranote; Ghanshyam S. Chauhan; Sandeep Chauhan; Sapna Sharma (Water, Air, & Soil Pollution, 2025)

Dapagliflozin Ameliorate Type-2 Diabetes Associated Neuropathy via Regulation of IGF-1R Signaling - Prabhsimran Kaur; Tashvinder Singh; Laxmipriya Jena; Tanya Gupta; Manjit Kaur Rana; Sandeep Singh; Randhir Singh; Puneet Kumar; Anjana Munshi (Journal of Neuroimmune Pharmacology, 2025)

Synthesis of sea urchin calcium copper oxide/halloysite nanotubes nanocomposites for electrochemical detection of promethazine hydrochloride in environmental samples - Gagankumar Sakleshpur Kumar; Bhuvan Lokesh Marenahalli; Sanjay Ballur Prasanna; A.S. Santhosh; S. Nandini; Jothi Ramalingam Rajabathar; Hamad Al-Lohedan; B.M. Nagaraja; S. Sandeep (Journal of Environmental Chemical Engineering, 2025)

Multigenerational immunotoxicity assessment: A three-generation study in Drosophila melanogaster upon developmental exposure to triclosan - Sandeep Kumar; Leonard Clinton D'Souza; Faiz Hanif Shaikh; Priya Rathor; C.H. Ratnasekhar; Anurag Sharma (Environmental Pollution, 2025)

Interaction Modeling of Surface Water and Groundwater: An Evaluation of Current and Future Issues - Noureen Khurshid; Rohitashw Kumar; Dinesh Kumar Vishwakarma; Sandeep Kumar; B. A. Pandit; Imran Khan; M. S. Pukhta; Krishna Kumar Yadav (Water Conservation Science and Engineering, 2025)

Thunderstorm prediction over Eastern state of India during pre-monsoon season in 2018 using artificial neural network model - Nagaraju Vanganuru; P. Sardar Maran; L. Lakshmanan; Anoop Kumar Mishra; Araveti Sandeep (Theoretical and Applied Climatology, 2025)

Probiogenomics of Leuconostoc Mesenteroides Strains F-21 and F-22 Isolated from Human Breast Milk Reveal Beneficial Properties - Juan Carlos Ariute; Nina Dias Coelho-Rocha; Carlos Willian Dias Dantas; Larissa Amorim Tourinho de Vasconcelos; Rodrigo Profeta; Thiago de Jesus Sousa; Ane de Souza Novaes; Bruno Galotti; Lucas Gabriel Gomes; Enrico Giovanelli Toccani Gimenez; Carlos Diniz; Mariana Vieira Dias; et al. (Probiotics and Antimicrobial Proteins, 2025)

Assessing the influence of fish waste hydrolysate, a byproduct of fish post-harvest, processing and fish markets, on the production performance of Penaeus monodon across diverse culture systems - K. P. Sandeep; Debasis De; R. Ananda Raja; T. Sivaramakrishnan; Sujeet Kumar; J. Raymond Jani Angel; S. Suvana; P. Mahalakshmi; K. Ambasankar; K. K. Vijayan (Aquaculture International, 2025)

Molecular Epidemiology and Genotypic Diversity of Theileria annulata among Bovines Based Upon Tams1 Gene in India - Rashmi Malik; Biswa Ranjan Maharana; Anita Ganguly; Sukhdeep Vohra; Binod Kumar; Ankit Kumar; Harpreet Singh; Sandeep Potliya; Sujoy Khanna; Subhasish Sahu (Acta Parasitologica, 2025)

Habitat-dependent dietary pattern of white-bellied sea-eagle: a cross-regional meta-analysis - Sakti Prasad Pattnayak; Aditya K. Panda; B. Anjan Kumar Prusty; Sandeep Rout; Priyanka Jena (Ornithology Research, 2025)

The occurrence of follicular cyst affects the embryonic developmental competences of buffalo oocytes under in vitro culture conditions - Pradeep Saini; Sandeep Kumar; Hitesh Jangra; Anupama Solanki; Rahul Verma; Rajesh Kumar; Ramakant Kaushik; Kushal Grakh; Gitesh Saini; Yogesh Bangar; Anand Kumar Pandey (Theriogenology, 2025)

Energy flow, eco-efficiency, and economic circulation with recycled industrial waste compost application in wheat and subsequent rice farming - Ram Swaroop Meena; Gourisankar Pradhan; Sandeep Kumar (Science of The Total Environment, 2025)

Identifying the causal agent of floral malformation as Fusarium complex using metagenomic and metabolomic approaches - M. Muthukumar; Anju Bajpai; Sumit K. Soni; Sanjay Kumar Singh; Yashi Bajpai; Sandeep Kumar; Laxmi (Physiological and Molecular Plant Pathology, 2025)

Assessment of seasonal variation in PM2.5 concentration using low-cost sensors: A case study of Jaipur city, India - Sandeep Kumar Chaudhry; Sachchida Nand Tripathi; Tondapu Venkata Ramesh Reddy; Sandeep Madhwal; Amit Kumar Yadav; Ravi Sahu; Pranav Kumar Pradhan (Atmospheric Environment, 2025)

Analysis of soybean cultivars response to mosaic and mottle disease caused by soybean yellow mottle mosaic virus - M. Srikant; Nagamani Sandra; Atul Kumar; Sandeep Kumar Lal; Sanjay Kumar Lal; Bikash Mandal (VirusDisease, 2025)

Phylogeography and genetic structure of domestic pigs in Uttarakhand and Jharkhand: a mitochondrial DNA perspective - Khusbu Sahu; Sandeep Kumar Gupta (Tropical Animal Health and Production, 2025)

Dual-nutrient stress tolerance in wheat is regulated by nitrogen and phosphorus uptake, assimilation, reutilization, and differential expression of candidate genes - Renu Pandey; Sandeep Sharma; Ankita Mishra; Akshay Sureshrao Sakhare; Surendra Kumar Meena; Krishnapriya Vengavasi (Plant and Soil, 2025)

Nano-interventions for dengue: a comprehensive review of control, detection and treatment strategies - Samia Shaikh; Padakanti Sandeep Chary; Neelesh Kumar Mehra (Inflammopharmacology, 2025)

A Mini Review on Electrochemical Nano-biosensors in Detection of Drugs/Pesticides - Anirudh Pratap Singh Raman; Vaibhav Kumar Mishra; Sandeep Yadav; Pallavi Jain; Prashant Singh; Kamlesh Kumari (Indian Journal of Microbiology, 2025)

A review on genetic resources, breeding status and strategies of dragon fruit - Ashok Yadav; Sandeep Garg; Sushil Kumar; Badre Alam; Ayyanadar Arunachalam (Genetic Resources and Crop Evolution, 2025)

Novel Damage Quantification and Strength Degradation of Thermally Treated Bundelkhand Granite: An Indian Heritage Stone - Rahul Rooplal Katre; Shivani Verma; Rishabh Dwivedi; Sandeep Panchal; Nikhil Ninad Sirdesai; Kumar Hemant Singh; Trilok Nath Singh (Geoheritage, 2025)

Nanotechnological interventions in bacteriocin formulations – advances, and scope for challenging food spoilage bacteria and drug-resistant foodborne pathogens - Debapriya Mohanty; Mrutyunjay Suar; Sandeep Kumar Panda (Critical Reviews in Food Science and Nutrition, 2025)

Virtual perspectives of sanguinarine on cancer prevention and treatment through molecular dynamic study - Vikas Sharma; Arti Gupta; Anshul Singh; Shivani Tyagi; Hrithika Panday; Saurabh Srivastava; Sathvik Belagodu Sridhar; Safia Obaidur Rab; Sandeep Kumar Shukla (In Silico Pharmacology, 2025)

Water quality assessment of river Ganga, India using water quality index and multivariate statistical techniques - Sandeep Kumar Mishra; Vikas Kumar; Jeetendra Kumar; Dharm Nath Jha; Absar Alam; Venkatesh Ramrao Thakur; Sushil kumar Verma; Upendra Singh; Basanta Kumar Das (Environmental Monitoring and Assessment, 2025)

Poly(hydroxamic acid) ligand from cornstalk cellulose for heavy metal recovery from electroplating wastewater - Md Lutfor Rahman; Umi Aisyah Mahani; Kalsum Ahmad Mustamin; Mohd Sani Sarjadi; Sazmal Effendi Arsad; Shaheen M. Sarkar; Sandeep Kumar (Sustainable Chemistry and Pharmacy, 2025)

Thermodynamic assessment and optimization of a solar and diesel engine exhaust-driven ORC-VCR system - Sandeep Kumar; B.B. Arora; Akhilesh Arora (International Journal of Refrigeration, 2025)

Conservation Agriculture offers system optimization for legume intensification: An on-farm study of western Indo-Gangetic Plains - Radheshyam; Shankar Lal Jat; Aditya Kumar Singh; Hanuman Sahay Jat; D.K. Sharma; M.C. Meena; Sandeep Gawdiya; Anup Kumar; Rakesh Kumar; Rajbir Singh; Mangi Lal Jat (Field Crops Research, 2025)

Sustainable biodegradation of malachite green dye by novel non-pathogenic Pseudomonas aeruginosa ED24 - Akanksha Pandey; Sachin Kumar; Navneet Bithel; Sandeep Kumar; M. Amin Mir (World Journal of Microbiology and Biotechnology, 2025)

An insight for the inhibition of anxiolytic and anti-convulsant effects in zebrafish using the curcumins via exploring molecular docking and molecular dynamics simulations - Iona Massey; Sandeep Yadav; Durgesh Kumar; Ram Swaroop Maharia; Kamlesh Kumari; Prashant Singh (Molecular Diversity, 2025)

Synthesis of metallic nanoparticles using biometabolites: mechanisms and applications - Chinmayee Acharya; Sonam Mishra; Sandeep Kumar Chaurasia; Bishnu Kumar Pandey; Ravindra Dhar; Jitendra Kumar Pandey (BioMetals, 2025)

Designing and analyses of mathematical models for sustainable agriculture in India: comparative study on the universal desiccant solar dryer and trapezoidal vertical solar dryer - Chandrashekhar N. Sakhale; Shrikrishna A. Dhale; Ajit V. Harde; Sagar D. Shelare; Shubham Sharma; Abhinav Kumar; Sandeep Kumar; Yashwant Singh Bisht; Mohamed Abbas (Environment, Development and Sustainability, 2025)

Transcriptome analysis for the identification of spot blotch responsive genes and miRNAs in wheat - Neeraj Kumar Vasistha; Archita Tandon; Sunita Pal; Sandeep Sharma; Vinod Kumar Mishra; Pushpendra Kumar Gupta (Physiological and Molecular Plant Pathology, 2025)

Biomass to electricity: A comparative techno-economic and feasibility study of decentralized air and oxy-steam gasification power technologies - Harmanpreet Singh; Nishant Ranjan; Sandeep Kumar (Journal of Cleaner Production, 2025)

Estimation of land surface temperature and LULC changes impact on groundwater resources in the semi-arid region of Madhya Pradesh, India - Kanak N. Moharir; Chaitanya Baliram Pande; Vinay Kumar Gautam; Sonam Sandeep Dash; Arun Pratap Mishra; Krishna Kumar Yadav; Hany W. Darwish; Malay Pramanik; Mohamed Elsahabi (Advances in Space Research, 2025)

Soil temperature estimation at different depths using machine learning paradigms based on meteorological data - Anurag Malik; Gadug Sudhamsu; Manjinder Kaur Wratch; Sandeep Singh; Srinadh Raju Sagiraju; Lamjed Mansour; Priya Rai; Rawshan Ali; Alban Kuriqi; Krishna Kumar Yadav (Environmental Monitoring and Assessment, 2024)

Flash flood dynamics in the foothills of the NW Himalayas: insights into hydrological and morphological controls - Sumit Sagwal; Sandeep Panda; Dipanwita Sengupta; Mohd Shahrukh; Sohan Kumar; Anil Kumar; Som Dutt (Environmental Monitoring and Assessment, 2024)

Enhancing spatial resolution of Landsat derived land surface temperature: A novel downscaling approach using an extreme learning machine - Jidnyasa Patil; Sandeep Maithani; Surendra Kumar Sharma (Journal of Earth System Science, 2024)

Evaluation of boron toxicity in soil and influencing factors: A case study of sodic soils of Panipat, India - Seema Chahal; Paulraj R; Bhupendra P. Singh; Sandeep Kumar Gautam (Environmental Monitoring and Assessment, 2024)

Exosomes: A new perspective for radiation combined injury as biomarker and therapeutics - Kirti; Ajay Kumar Sharma; M.H. Yashavarddhan; Rishav Kumar; Priyanka Shaw; Aman Kalonia; Sandeep Kumar Shukla (Tissue and Cell, 2024)

Green chemistry revolutionizing sustainability in the food industry: A comprehensive review and call to action - Arun Kumar Gupta; Tridip Boruah; Payel Ghosh; Ali Ikram; Sandeep Singh Rana; Anjaly Shanker M; Archana Bachetti; Avinash Kumar Jha; Bindu Naik; Vijay Kumar; Sarvesh Rustagi (Sustainable Chemistry and Pharmacy, 2024)

Hibernation changes tissue specific lipophilic profile of Chilo partellus (Swinhoe) - Ashok K. Sau; Mukesh K. Dhillon; Sandeep Kumar; Aditya K. Tanwar (Journal of Asia-Pacific Entomology, 2024)

Exploring the potential of metallic and metal oxide nanoparticles for reinforced disease management in agricultural systems: A comprehensive review - Adnan Raza; Krisha Khandelwal; Soumya Pandit; Mohini Singh; Sandeep Kumar; Sarvesh Rustagi; Nishant Ranjan; Rajan Verma; Kanu Priya; Ram Prasad (Environmental Nanotechnology, Monitoring & Management, 2024)

Ameliorated Morpho-Physiological Response of Stevia Under the Influence of Variable LEDs Inside Plant Factory System - Sandeep Kumar Verma; Tsama Subrahmanyeswari; Saikat Gantait (Sugar Tech, 2024)

Frequency-dependent Layered Q Model and Attenuation Tomography of the Himachal North-West Himalaya, India: Insight to Explore Crustal Variation - Parveen Kumar; V. J. Sahakian; Monika; Sandeep (Pure and Applied Geophysics, 2024)

Deciphering phenomics approaches for understanding plant–microbe interactions in nutrient absorption and utilization - Milan Kumar Lal; Rahul Kumar Tiwari; Sandeep B. Adavi; Awadhesh Kumar; Ibragim Bamatov; Ekaterina Ivanova; Laxmipriya Behera; Rupak Jena; Ravinder Kumar (Plant Physiology Reports, 2024)

Unique among high passes: Insights into the genetic uniqueness among butterflies of Ladakh Trans-Himalaya through DNA barcoding - Mohd Ali; Rushati Dey; Moumita Das; Vikas Kumar; Kailash Chandra; Virendra Prasad Uniyal; Sandeep Kumar Gupta (Molecular Biology Reports, 2024)

Genetic diversity, spatial connectivity, and population structure of Asian silurid catfish Wallago attu (Bloch and Schneider, 1801) in the Ganga River System: insights from mitochondrial DNA analysis - Ajit Kumar; Naveen Negi; Neha Yadav; Ruchi Badola; Syed Ainul Hussain; Sandeep Kumar Gupta (Molecular Biology Reports, 2024)

Identification and characterization of potential sources of waterlogging tolerance in Vigna species as revealed by physiological, biochemical and gene expression profiling - Sandeep Kumar; Chandra Mohan Singh; Mukul Kumar; Shalini Purwar; Hitesh Kumar; Anuj Mishra; Ashutosh Rai; Vaishali Gangwar; Ramkrishanan M. Nair; Aditya Pratap (Journal of Plant Biochemistry and Biotechnology, 2024)

Genetic diversity and population structure analysis in Job's tears (Coix lacryma-jobi L.) collections from northeastern Himalayan region - Amit Kumar; S. P. Das; Avinash Pandey; Shiv Poojan Singh; Simardeep Kaur; Sandeep Jaiswal; W. S. Philanim; Letngam Touthang; Veerendra Kumar Verma; Binay K. Singh; V. K. Mishra (Genetic Resources and Crop Evolution, 2024)

Influence of seasonal variation on spatial distribution of PM2.5 concentration using low-cost sensors - Sandeep Kumar Chaudhry; Sachchida Nand Tripathi; Tondapu Venkata Ramesh Reddy; Anil Kumar; Sandeep Madhwal; Amit Kumar Yadav; Pranav Kumar Pradhan (Environmental Monitoring and Assessment, 2024)

Evaluation of yield and quality attributes of barley cultivars with foliar spray of glycine betaine under lead toxicity - Jyoti Sharma; Sandeep Kumar; Naveen Kumar; Neha Yadav; Pradeep Khyalia; Asha Sharma (Cereal Research Communications, 2024)

Pollen Preservation Approaches in Date Palm Cultivation: Assessing Effects on Viability, Fruit Quality, and Yield in ‘Mundra Selection-3’ - Priyanka Kumawat; Rajendra Singh Rathore; Sandeep Kumar; Sunny Sharma; Pramod Kumar Yadav; Kumari Lata (Applied Fruit Science, 2024)

Understanding the role of topography, climate, and sediment transport dynamics in flash flood hazards along the Dhauli Ganga River of northwest Himalaya, India - Sameeksha Kaushik; Dhirendra Singh Bagri; Yaspal Sundriyal; Sandeep Kumar; Neha Chauhan; Naresh Rana (Journal of Earth System Science, 2024)

NIR Light-triggered Green Emitting Perovskite-based Phosphor for Optical Thermometry and Future Molecular Logic Gate Applications - Ishant Kumar; Avinash Kumar; Sandeep Kumar; Govind B. Nair; H. C. Swart; Arvind K. Gathania (Journal of Fluorescence, 2024)

Laboratory studies on cloud electrification during ice crystal-graupel collisions: New parametrization scheme - Pallath Pradeep Kumar; Rajan Pulakeshi; Sandeep Wagh (Journal of Earth System Science, 2024)

Evaluating landslide hazard, vulnerability, and risk using machine learning; A case study from the Alaknanda Valley, NW Himalaya - Yaspal Sundriyal; Sandeep Kumar; Sameeksha Kaushik; Neha Chauhan; Robert Wasson; Shravi Agarwal; Sanjeev Kumar; Vipin Kumar; Dhirendra Singh Bagri; Naresh Rana; Anirudh Chouhan (Environment, Development and Sustainability, 2024)

Green synthesis of N-doped-carbon dots/ZnO for enhanced photocatalytic degradation of methylene blue dye: optimization of reaction parameters - Neeru Rani; Sandeep Kumar; Krishan Kumar (Environmental Science and Pollution Research, 2024)

Techno-economics of high ash coal gasification: A machine learning approach using CatBoost model - Dharmendra Kumar Singh; Sandeep Kumar (Journal of Cleaner Production, 2024)

From orchard to table: Significance of fruit microbiota in postharvest diseases management of citrus fruits - Manoj Kumar Solanki; Zhen Wang; Amit Kaushik; Vipin Kumar Singh; Rajib Roychowdhury; Manish Kumar; Dharmendra Kumar; Joginder Singh; Sandeep Kumar Singh; Bhavana Dixit; Ajay Kumar (Food Control, 2024)

Crop establishment and nutrient management options: Optimizing productivity, maximize profitability and mitigating adverse climatic conditions in the maize-based production system of Northwest India - Mohammad Hasanain; V.K. Singh; S.S. Rathore; Vijay Singh Meena; Sunita Kumari Meena; Kapila Shekhawat; R.K. Singh; B.S. Dwivedi; Raghavendra Singh; Subhash Babu; P.K. Upadhyay; Amit Kumar; et al. (Field Crops Research, 2024)

Rose-like structure of calcium molybdate decorated on halloysite nanotubes as an electrocatalyst: Highly sensitive and selective electrochemical determination of promethazine hydrochloride in biological and environmental samples: Density functional theory studies - Bhuvan Lokesh Marenahalli; Sanjay Ballur Prasanna; Gagankumar Sakleshpur Kumar; Santhosh Arehalli Shivamurthy; Hema Mylnahalli Krishnegowda; Kumar Venkatesan; Manickam Selvaraj; Ren-Jei Chung; Yu-Jui Fan; Sandeep Shadakshari (Chemical Engineering Journal, 2024)

Insights into the mechanisms forging seismic anisotropy in the upper mantle beneath India - Sunil K. Roy; M. Ravi Kumar; Jyotima Kanaujia; Sandeep Gupta; Bhoopendra Singh; Prantik Mandal; D. Srinagesh (Tectonophysics, 2024)

Increasing frequency of extreme climatic events in southern India during the Late Holocene: Evidence from lake sediments - A.S. Yamuna; P. Vyshnav; Anish Kumar Warrier; M.C. Manoj; K. Sandeep; M. Kawsar; G.S. Joju; Rajveer Sharma (Quaternary International, 2024)

Biochemical and gene expression profiling of oxalate biosynthesis in cherry tomato (Solanum lycopersicum var. cerasiforme) in Indo-Gangetic Plains of India - Simarjot Kaur; Neena Chawla; Salesh Kumar Jindal; Prashant Mohanpuria; Sandeep Jain; Urvashi Sharma (Food Bioscience, 2024)

Comparative analysis of modified partial least squares regression and hybrid deep learning models for predicting protein content in Perilla (Perilla frutescens L.) seed meal using NIR spectroscopy - Simardeep Kaur; Naseeb Singh; Preety Dagar; Amit Kumar; Sandeep Jaiswal; Binay K. Singh; Rakesh Bhardwaj; Jai Chand Rana; Amritbir Riar (Food Bioscience, 2024)

Precision nutrient management influences the productivity, nutrients use efficiency, N2O fluxes and soil enzymatic activity in zero-till wheat (Triticum aestivum L.) - Rahul Sadhukhan; Dinesh Kumar; Seema Sepat; Avijit Ghosh; Koushik Banerjee; Y.S. Shivay; Sandeep Gawdiya; MN Harish; Arti Bhatia; Anita Kumawat; Suman Dutta; Niraj Biswakarma; et al. (Field Crops Research, 2024)

Insights into the adsorption mechanism of the selenite ion in a cationic metal–organic framework - Hongbiao Huang; Zhonghang Chen; Pamarthi Amesh; Sandeep Kumar; Abhinandan Kumar; Shixuan Ma; Shuangshuang Li; Wei Shi; Xuemei Yang; Peng Ren (Chemical Engineering Journal, 2024)

Harnessing filamentous fungi and fungal-bacterial co-culture for biological treatment and valorization of hydrothermal liquefaction aqueous phase from corn stover - Meicen Liu; Jiefu Wang; Isamu Umeda; Zhiwu Wang; Sandeep Kumar; Yi Zheng (Bioresource Technology, 2024)

Role of solvent in selective hydrodeoxygenation of monomeric phenols - Randy L. Maglinao; Amos Taiswa; Evan T. Davison; Jessica M. Andriolo; Gary L. Succaw; Jack L. Skinner; Sandeep Kumar (Biomass and Bioenergy, 2024)

Co-metabolism of substrates by Pseudomonas aeruginosa NG4 regulates biosurfactant production - Shivangi Sankhyan; Prasun Kumar; Madan Sonkar; Sandeep Kumar; Soumya Pandit; Subhasree Ray (Biocatalysis and Agricultural Biotechnology, 2024)

Advancing COVID-19 poverty estimation with satellite imagery-based deep learning techniques: a systematic review - Shruti Mishra; Sandeep Kumar Satapathy; Sung-Bae Cho; Sachi Nandan Mohanty; Sweeti Sah; Shweta Sharma (Spatial Information Research, 2024)

Correction: Finger millet (Eleusine coracana L.): from staple to superfood—a comprehensive review on nutritional, bioactive, industrial, and climate resilience potential - Simardeep Kaur; Arti Kumari; Karishma Seem; Gurkanwal Kaur; Deepesh Kumar; Surbhi Verma; Naseeb Singh; Amit Kumar; Manish Kumar; Sandeep Jaiswal; Rakesh Bhardwaj; Binay Kumar Singh; et al. (Planta, 2024)

Lactic acid bacteria secreted proteins as potential Listeria monocytogenes quorum sensing inhibitors - Pedro Henrique Marques; Arun Kumar Jaiswal; Felipe Alves de Almeida; Uelinton Manoel Pinto; Alessandra Barbosa Ferreira-Machado; Sandeep Tiwari; Siomar de Castro Soares; Aline Dias Paiva (Molecular Diversity, 2024)

Design, synthesis and evaluation of sesamol-derived acetamides as dual inhibitors of monoamine oxidases and cholinesterases - Sandeep Kumar; Rangan Mitra; Senthil Raja Ayyannan (Medicinal Chemistry Research, 2024)

Cyanobacteria-based nutrimental strategy to enhance yield and quality of spinach - Ravi Mourthy Nivedha; Radha Prasanna; Akanksha Bhardwaj; Nallappa Reddy Bavana; Shalini Gaur Rudra; Awani Kumar Singh; Sandeep Kumar Lal; Sudipta Basu; Yashbir Singh Shivay (Journal of Applied Phycology, 2024)

Evaluating the need and feasibility of micro-irrigation systems for sustainable irrigation - Sandeep Kumar Chourasia; Suzan Karkee Chhetri; Ashish Pandey (Environmental Monitoring and Assessment, 2024)

Estimation of spatiotemporal dynamics of urban sprawl in Bengaluru Urban agglomeration using earth observation datasets - Pundoor Sandeep; Haritha Saju; Karikkathil C. Arun Kumar (Arabian Journal of Geosciences, 2024)

Fabrication of sulfur doped exfoliated gCN photocatalyst for enhanced visible light degradation of pernicious organic pollutants and their photocatalytic antibacterial activity - Prerna Attri; Moondeep Chauhan; Rajender Singh; Sandeep Kumar; Preeti Garg; Dong-Kwon Lim; Ganga Ram Chaudhary (Chemosphere, 2024)

Fabricating whole pine needles biomass with phenylhydrazine-4-sulphonic acid for effective removal of cationic dyes and heavy metal ions from wastewater - Babita Kumari; Sandeep Chauhan; Kiran Kumar; Sudershan Singh; Sunita Ranote; Rajesh Kumar; Ghanshyam S. Chauhan (Chemosphere, 2024)

Developing microbial seed coating for enhancing seed vigour and prolonging storability in chickpea - Mujtahida Khatun; Radha Prasanna; Akanksha Bhardwaj; Sayan Makur; Sandeep Kumar Lal; Sudipta Basu; Priya Ranjan Kumar (South African Journal of Botany, 2024)

Finger millet (Eleusine coracana L.): from staple to superfood—a comprehensive review on nutritional, bioactive, industrial, and climate resilience potential - Simardeep Kaur; Arti Kumari; Karishma Seem; Gurkanwal Kaur; Deepesh Kumar; Surbhi Verma; Naseeb Singh; Amit Kumar; Manish Kumar; Sandeep Jaiswal; Rakesh Bhardwaj; Binay Kumar Singh; et al. (Planta, 2024)
Main conclusion This review discusses the Finger millet's rich nutritional profile, bioactive potential, and industrial applications, combined with its climate resilience, which make it a promising crop for enhancing food security and promoting sustainable agriculture. This review also highlights its significant potential to address malnutrition and mitigate climate change impacts. Abstract The emergence of Finger millet from “poor man’s staple food” to “a nutrient rich cereal” has encouraged the need to explore this crop at a wider scale. It is a highly significant crop due to its rich nutritional and bioactive profile, diverse biological activities, and promising industrial applications, along with the high climate resilience. This comprehensive review evaluates its nutritional composition by comparing favorably with other cereals and millets and emphasizing its potential to address malnutrition and enhance food security. Furthermore, it explores the phytochemical/bioactive potential and strategies to enhance their bioavailability followed biological activities of Finger millet by highlighting its various health-promoting properties. The review also discusses industrial potential of finger millet including its role in nutraceutical and functional food production, as well as bioenergy generation. In addition, role of Finger millet as a climate-resilient crop; specifically, the available genetic resources and identification of genes and quantitative trait loci (QTLs) associated with major stress tolerance traits have also been discussed. By providing a comprehensive synthesis of existing knowledge, this study offers valuable insights for researchers, policymakers, and stakeholders engaged in efforts to promote sustainable agriculture, enhance food and nutrition security, and mitigate the impacts of climate change.

Comparison of surface adsorption efficacies of eco-sustainable agro/animal biomass-derived activated carbon for the removal of rhodamine B and hexavalent chromium - Parminder Kaur; Sandeep Kumar; Jyoti Rani; JNagendra Babu; Sunil Mittal (Environmental Science and Pollution Research, 2024)

Crop-livestock integration influenced soil profile organic carbon and hydro-physical properties in converted grasslands to row crops - Poulamee Chakraborty; Goutham Thotakuri; Navdeep Singh; Jashanjeet Kaur Dhaliwal; Sandeep Kumar (Soil and Tillage Research, 2024)

The emergence of digitalization to the manufacturing sector in the sustainability context: A multi-stakeholder perspective analysis - M.S. Kiran Sankar; Sumit Gupta; Sunil Luthra; Sandeep Jagtap; Sanjeet Singh; Anil Kumar (Journal of Cleaner Production, 2024)

Characterizing genetic diversity of Sclerotium rolfsii isolates by biomapping of mycelial compatibility groupings and multilocus sequence analysis - C. Shanmugaraj; Deeba Kamil; Robin Gogoi; Amrita Das; G. M. Sandeep Kumar; Zakir Hussain; Praveen Kumar Singh; M. A. Iquebal (World Journal of Microbiology and Biotechnology, 2024)

Development of novel faba bean (Vicia faba L.) for release as a new cultivar with high yield and protein content - Rajesh K. Arya; Gajraj S. Dahiya; Ravi Kumar; Ranjeet K. Gill; Jitender K. Tiwari; Chander B. Yadav; Hanuman L. Raiger; Sandeep Kumar; Surya Kant (Genetic Resources and Crop Evolution, 2024)

Harnessing the potential of microbial keratinases for bioconversion of keratin waste - Sandeep Das; Ankita Das; Nandita Das; Tamanna Nath; Mrinalini Langthasa; Prisha Pandey; Vijay Kumar; Kamlesh Choure; Sanjeev Kumar; Piyush Pandey (Environmental Science and Pollution Research, 2024)

3D attenuation tomography of the Uttarakhand, NW Himalaya: Linkage to fluid or partial melt zones - Seismic hazard - Monika; Parveen Kumar; Sandeep; A. Joshi; S.K. Pal (Soil Dynamics and Earthquake Engineering, 2024)

EV charging and fuel cell vehicle refuelling with distributed energy resources using hybrid approach - M. Senthilkumar; Sandeep Prabhu; U. Arun Kumar; R. Krishnakumar (Environment, Development and Sustainability, 2024)

Agriculture models for restoring degraded land to enhance CO2 biosequestration and carbon credits in the Vindhyan region of India - Ram Swaroop Meena; Gourisankar Pradhan; Kanchan Singh; Sandeep Kumar; Ambuj Kumar Singh; K.S. Shashidhar; Krishan Kant Mina; Ch. Srinivasa Rao (Science of The Total Environment, 2024)

Molecular detection and characterization of prevailing Theileria equi genotype in equine from northern India - Biswa Ranjan Maharana; Anita Ganguly; Sandeep Potliya; Binod Kumar; Harpreet Singh; Aishwarya Dash; Sujoy Khanna (Research in Veterinary Science, 2024)

An approach towards different techniques for detection of heavy metal ions and their removal from waste water - Anoop Singh; Shahid Shafi Shah; Chandan Sharma; Vinay Gupta; Ashok K. Sundramoorthy; Pawan Kumar; Sandeep Arya (Journal of Environmental Chemical Engineering, 2024)

Flake-like structure of SrTiO3 nanoparticles dispersed on graphene oxide: A selective and sensitive electrochemical sensor for determination of chloramphenicol in milk and honey samples - Gagankumar Sakaleshpur Kumar; Sanjay Ballur Prasanna; Bhuvan Lokesh Marenahalli; Sandeep Shadakshari; Santhosh Arehalli Shivamurthy; Jothi Ramalingam Rajabathar; Karthik Chimatahalli Shanthakumar; Young-Kyu Han (Food Chemistry, 2024)

Industrial importance seed kernel of Buchanania lanzan in contributing antioxidant, antidiabetic, and anticholinesterase activities - Neelam Meher; Bikash Kisan; Sandeep Kumar Swain; Atish Kumar Sahoo (Food Bioscience, 2024)

Unveiling the genetic structure of pig population in a Himalayan state Uttarakhand through microsatellite and mitochondrial DNA analyses - Khusbu Sahu; Govindan Veeraswamy Gopi; Sandeep Kumar Gupta (Tropical Animal Health and Production, 2024)

Plant population mapping and quantitative assessment of peri-urban vegetation of Ranchi, eastern India - Purabi Saikia; Sandeep Kumar; Amit Kumar (Tropical Ecology, 2024)

On the Identity of a rare Morphologically Abnormal Butterfly ray from the east Coast of India Resolved Through Molecular tool - Rajesh Kumar Behera; Swarup Ranjan Mohanty; Smrutirekha Acharya; Sandeep Kumar Mohapatra; Subhrendu Sekhar Mishra; K. K Bineesh; Anil Mohapatra (Thalassas: An International Journal of Marine Sciences, 2024)

Substitution of Inorganic Nitrogen with Organic Amendments for Improvement of Soil Properties, Microbial Community, and Enzymatic Activity in Maize-Wheat Cropping System Under Sub-temperate Ecology - Sukhchain Singh; Naveen Kumar; Sandeep Manuja; Pardeep Kumar; Sandeep; Sandeep Singh; Shwetansh; Arvind Chahal (Journal of Soil Science and Plant Nutrition, 2024)

Industrial and C&D waste as precursor material in geopolymers: a state-of-the-art review - Mohammed Rihan Maaze; Nikhil Garg; Sourav Kumar Das; Sandeep Shrivastava (Innovative Infrastructure Solutions, 2024)

Antibacterial Activity of Sustainable Thymol Nanoemulsion Formulations Against the Bacterial Blight Disease on Cluster Bean Caused by Xanthomonas axonopodis - Pooja Choudhary; Gaurav Bhanjana; Sandeep Kumar; Neeraj Dilbaghi (Indian Journal of Microbiology, 2024)

Key physiological traits for drought tolerance identified through phenotyping a large set of slicing cucumber (Cucumis sativus L.) genotypes under field and water-stress conditions - Anjan Das; A. D. Munshi; Dhandapani Raju; Sudhir Kumar; Dharmendara Singh; Akshay Talukdar; Dhananjay Hongal; Mir Asif Iquebal; Sandeep Kumar; R. C. Bhattacharya; Pragya Ranjan; Oula Ghannoum; et al. (Genetic Resources and Crop Evolution, 2024)

Synthesized Gold Nanoparticles with Moringa Oleifera leaf Extract Induce Mitotic Arrest (G2/M phase) and Apoptosis in Dalton’s Lymphoma Cells - Sandeep Kumar; Alok Shukla; Surya Pratap Singh; Rishi Kant Singh; Anand Kumar Patel; Praveen Kumar Verma; Sanjay Kumar; Naveen Kumar; Varsha Singh; Kirti Wasnik; Arbind Acharya (Cell Biochemistry and Biophysics, 2024)

Pharmacological Insights: Mitochondrial ROS Generation by FNC (Azvudine) in Dalton’s Lymphoma Cells Revealed by Super Resolution Imaging - Naveen Kumar; Vikram Delu; Ilya Ulasov; Sanjay Kumar; Rishi Kant Singh; Sandeep Kumar; Alok Shukla; Anand Kumar Patel; Lokesh Yadav; Ruchi Tiwari; Kumari Rachana; Shivashish Priyadarshi Mohanta; et al. (Cell Biochemistry and Biophysics, 2024)

FNC (4′-azido-2′-deoxy-2′-fluoro(arbino)cytidine) as an Effective Therapeutic Agent for NHL: ROS Generation, Cell Cycle Arrest, and Mitochondrial-Mediated Apoptosis - Naveen Kumar; Alok Shukla; Sanjay Kumar; Ilya Ulasov; Rishi Kant Singh; Sandeep Kumar; Anand Patel; Lokesh Yadav; Ruchi Tiwari; Rachana Paswan; Shivashish Priyadarshi Mohanta; Kaushalendra; et al. (Cell Biochemistry and Biophysics, 2024)

Development of region specific earthquake early warning scaling relations for the Garhwal region using observed and simulated datasets: a step forward to disaster mitigation - Suraj Kumar Pal; Sandeep; Shubham Gangajali; Parveen Kumar; Himanshu Mittal (Bulletin of Earthquake Engineering, 2024)

Emerging role of osmoprotectant glycine betaine to mitigate heavy metals toxicity in plants: a systematic review - Jyoti Sharma; Sandeep Kumar; Pooja Singh; Vikram Kumar; Shivani Verma; Pradeep Khyalia; Asha Sharma (Biologia Futura, 2024)

Assessment of Long-term spatiotemporal soil moisture variation in the lower Mahanadi River basin: a hydrological modeling based approach - Mithlesh Kumar; A. P. Sahu; J. C. Paul; Sonam Sandeep Dash; B. C. Sahoo; Ajit Kumar Nayak; Lokesh Kumar Tinde (Environment, Development and Sustainability, 2024)

Enhancing soil quality and yield through microbial assisted in-situ residue management in rice-rice cropping system in Odisha, Eastern India - Periyasamy Panneerselvam; Ansuman Senapati; Debasis Mitra; Ankita Priyadarshini; Smriti Shadangi; Suchismita Behera; Upendra Kumar; Anjani Kumar; Mohammad Shahid; Sandeep Sharma; Rajendra Singh Garhwal; Indra Mani; et al. (Journal of Environmental Management, 2024)

Spatio-temporal evaluation of drought adaptation in wheat revealed NDVI and MTSI as powerful tools for selecting tolerant genotypes - S. Srinatha Reddy; G Mahendra Singh; Uttam Kumar; Pradeep Bhati; Manish Vishwakarma; Sudhir Navathe; K.J. Yashavanthakumar; Vinod K. Mishra; Sandeep Sharma; Arun K. Joshi (Field Crops Research, 2024)

Spatio-temporal expression of polyphenol oxidase unveils the dynamics of L-DOPA accumulation in faba bean (Vicia faba L.) - Sradhanjali Jena; Rajarshi Sanyal; Danish Md. Jawed; Kaustav Sengupta; Bhubaneswar Pradhan; Subodh Kumar Sinha; Biplab Sarkar; Sandeep Kumar; Sangram K. Lenka; Soumen Naskar; Vijai P. Bhadana; Sujit K. Bishi (Physiology and Molecular Biology of Plants, 2024)

Quality by design approach-based fabrication and evaluation of self-nanoemulsifying drug delivery system for improved delivery of venetoclax - Naveen Rajana; Padakanti Sandeep Chary; Yeruva Sri Pooja; Valamla Bhavana; Hoshiyar Singh; Santosh Kumar Guru; Shashi Bala Singh; Neelesh Kumar Mehra (Drug Delivery and Translational Research, 2024)

Exploring luminescent carbon dots derived from syrup bottle waste and curcumin for potential antimicrobial and bioimaging applications - Natesan Thirumalaivasan; Kuppusamy Kanagaraj; Kamaraj Logesh; Sridhar Chandrasekaran; Sandeep Kumar; Raghunandhakumar Subramanian; Nangan Senthilkumar; Ashok Kumar; V. Jagadeesha Angadi; Abdullah A. Al-Kahtani (Chemosphere, 2024)

Preface to the special issue 7th International Conference on Nanoscience and Nanotechnology – ICONN 2023 - Sandeep Kumar Lakhera (Chemosphere, 2024)

Fuzzy machine learning model to detect transition building footprints using multi-sensor multi-temporal images - Luvkesh Attri; Anil Kumar; Sandeep Maithani (Remote Sensing Applications: Society and Environment, 2024)

Review on biofuel production: Sustainable development scenario, environment, and climate change perspectives − A sustainable approach - Shiv Prasad; Krishna Kumar Yadav; Sandeep Kumar; Priti Pandita; Javed Khan Bhutto; Maha A. Alreshidi; Balasubramani Ravindran; Zaher Mundher Yaseen; Sameh M. Osman; Marina M.S. Cabral-Pinto (Journal of Environmental Chemical Engineering, 2024)

Sustainable basmati rice yield and quality enhancement through long-term organic nutrient management in the Indo-Gangetic Plains - Anita Kumawat; Dinesh Kumar; Y.S. Shivay; Devideen Yadav; Rahul Sadhukhan; Sandeep Gawdiya; Shakir Ali; M. Madhu; Kuldeep Kumar; I. Rashmi; R.A. Jat (Field Crops Research, 2024)

Anti-CRISPR proteins: a weapon of phage-bacterial arm race for genome editing - Sandeep Jaiswal; Lal Bahadur Singh; Kuldeep Kumar; Joshitha Vijayan; Nivedita Shettigar; Sudhir Kumar Jha; Khela Ram Soren (The Nucleus, 2024)

Exploring effect of scale dependency in LST downscaling – using convolution neural network-extreme learning machine (CNN-ELM) - Jidnyasa Patil; Sandeep Maithani; Surendra Kumar Sharma (Earth Science Informatics, 2024)

Differential biochemical and physiological responses to cotton leaf curl virus infection in contrasting cotton genotypes - Taranjeet Kaur; Shiwani Mandhania; Vikram Singh; Rashi Datten; Prakash Banakar; Karmal Malik; K. Sankaranarayanan; Minakshi Jattan; Sandeep Kumar; Anil Kumar Saini; Anil Jakhar (Acta Physiologiae Plantarum, 2024)

An experimental and prediction modeling study on water lettuce (Pistia stratiotes L.) assisted heavy metals removal from glass industry effluent - Jogendra Singh; Sadeq K. Alhag; Eman A. Al-Shahari; Laila A. Al-Shuraym; Ibtisam M. Alsudays; Mohamed T. Ahmed; Ebrahem M. Eid; Sami Abou Fayssal; Pankaj Kumar; Sandeep Kumar Malyan; Om Singh; Vinod Kumar (Environmental Science and Pollution Research, 2024)

Nicotine promotes epithelial to mesenchymal transition and gemcitabine resistance via hENT1/RRM1 signalling in pancreatic cancer and chemosensitizing effects of Embelin-a naturally occurring benzoquinone - Prashanth N; Meghana P; Sandeep Kumar Jain R; Pooja S Rajaput; Satyanarayan N D; Raja Naika H; Kumaraswamy H M (Science of The Total Environment, 2024)

X-ray computed tomography – Measured pore characteristics and hydro-physical properties of soil profile as influenced by long-term tillage and rotation systems - Goutham Thotakuri; Poulamee Chakraborty; Jasdeep Singh; Sutie Xu; Péter Kovács; Javed Iqbal; Sandeep Kumar (CATENA, 2024)

Phytochemical analysis and enhanced production of alkaloids in non-dormant corm-derived callus of Gloriosa superba (L.) using plant growth regulators and abiotic elicitors - Dexter Achu Mosoh; Ashok Kumar Khandel; Sandeep Kumar Verma; Wagner A. Vendrame (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

COVID-19 Virus Structural Details: Optical and Electrochemical Detection - Priyanka; Brij Mohan; Ekta Poonia; Sandeep Kumar; Virender; Charan Singh; Jichuan Xiong; Xuefeng Liu; Armando J. L. Pombeiro; Gurjaspreet Singh (Journal of Fluorescence, 2024)

Enhancing Immunological Memory: Unveiling Booster Doses to Bolster Vaccine Efficacy Against Evolving SARS-CoV-2 Mutant Variants - Sovan Samanta; Jhimli Banerjee; Aparna Das; Sourav Das; Rubai Ahmed; Swarnali Das; Amitava Pal; Kazi Monjur Ali; Rupanjan Mukhopadhyay; Biplab Giri; Sandeep Kumar Dash (Current Microbiology, 2024)

Description of the Life Cycle Stages of the Parasitic Cymothoid, Cymothoa indica Schioedte and Meinert, 1884, and Its Prevalence in Commercial Fishes from Chilika Lagoon, India - Sanmitra Roy; Sandeep Kumar Mohapatra; Hemanta Kumar Sahu; Jaya Kishor Seth (Acta Parasitologica, 2024)

A two-in-one thiosemicarbazide and whole pine needle-based adsorbent for rapid and efficient adsorption of methylene blue dye and mercuric ions - Babita Kumari; Sandeep Chauhan; Ghanshyam S. Chauhan; Kiran Kumar; Pooja Jamwal; Sunita Ranote (Environmental Science and Pollution Research, 2024)

Application of apophyllite and thomsonite natural zeolite as modified adsorbents for the removal of zinc from acid mine drainage - Ravindra W. Gaikwad; Amol Vijay Sonawane; Vikas S. Hakke; Shirish H. Sonawane; Mahendra S. Gaikwad; Sandeep Kumar Lakhera; Venu Babu G; A.R. Warade; Ajay B. Urgunde; Vilas S. Sapkal (Chemosphere, 2024)

Recent progress in chromium removal from wastewater using covalent organic frameworks – A review - Soumita Samajdar; Shiny Golda A; Sandeep Kumar Lakhera; Srabanti Ghosh (Chemosphere, 2024)

ZIF-8 decorated cellulose acetate mixed matrix membrane: An efficient approach for textile effluent treatment - Surya Teja Malkapuram; Murali Mohan Seepana; Shirish H. Sonawane; Sandeep Kumar Lakhera; Edward Randviir (Chemosphere, 2024)

Selective vanadium etching and in-situ formation of -Bi2O3 on m-BiVO4 with g-C3N4 nanosheets for photocatalytic degradation of antibiotic tetracycline - Mriganki Singh; Rugma T P; Shiny Golda A; Bernaurdshaw Neppolian; Mu. Naushad; Sandeep Kumar Lakhera (Journal of Cleaner Production, 2024)

Unlocking the genetic enigma: A paradigm shift towards evidence-based conservation of Indian star tortoise (Geochelone elegans) - Subhashree Sahoo; Ajit Kumar; Jagdish Rai; Sandeep Kumar Gupta (Biological Conservation, 2024)

Evaluation of PM2.5 spatio-temporal variability and hotspot formation using low-cost sensors across urban-rural landscape in lucknow, India - Sandeep Madhwal; Sachchida Nand Tripathi; Michael Howard Bergin; Prakash Bhave; Benjamin de Foy; T.V. Ramesh Reddy; Sandeep Kumar Chaudhry; Vaishali Jain; Naresh Garg; Paresh Lalwani (Atmospheric Environment, 2024)

Catalytic applications of phosphorene: Computational design and experimental performance assessment - Monika Nehra; Neeraj Dilbaghi; Rajesh Kumar; Sunita Srivastava; K. Tankeshwar; Ki-Hyun Kim; Sandeep Kumar (Critical Reviews in Environmental Science and Technology, 2024)

Catalytic applications of phosphorene: Computational design and experimental performance assessment - Monika Nehra; Neeraj Dilbaghi; Rajesh Kumar; Sunita Srivastava; K. Tankeshwar; Ki-Hyun Kim; Sandeep Kumar (Critical Reviews in Environmental Science and Technology, 2024)

Proof-of-principle study using Saccharomyces cerevisiae for universal screening test for cancer through ultrasound-based size distinction of circulating tumor cell clusters - Saksham Rajan Saksena; Sandeep Kumar Rajan (Journal of Biosciences, 2024)

An integrated approach of machine learning and remote sensing for evaluating landslide hazards and risk hotspots, NW Himalaya - Yaspal Sundriyal; Sandeep Kumar; Neha Chauhan; Sameeksha Kaushik; Vipin Kumar; Naresh Rana; Robert Wasson (Remote Sensing Applications: Society and Environment, 2024)

Assessment of sustainable school transport policies on vehicular emissions using the IVE model - Sandeep Kumar Chaudhry; Suresh Pandian Elumalai (Journal of Cleaner Production, 2024)

Comparative exploration of biological treatment of hydrothermal liquefaction wastewater from sewage sludge: Effects of culture, fermentation conditions, and ammonia stripping - Meicen Liu; Chandan Mahata; Zhiwu Wang; Sandeep Kumar; Yi Zheng (Journal of Environmental Management, 2024)

Production of fungal phytases in solid state fermentation and potential biotechnological applications - Bijender Singh; Pragya; Santosh Kumar Tiwari; Davender Singh; Sandeep Kumar; Vinay Malik (World Journal of Microbiology and Biotechnology, 2024)

Imaging of Different Crustal and Mantle Discontinuities Below the Hyderabad Region on the Eastern Dharwar Craton - Prantik Mandal; Sandeep Gupta; K. Sivaram; Sanjay Kumar; Sudesh Kumar; Rahul Biswas; Raju Prathigadapa; B. N. V. Prasad; M. Saidixit (Pure and Applied Geophysics, 2024)

A Novel TPM1 Mutation Causes Familial Hypertrophic Cardiomyopathy in an Indian Family: Genetic and Clinical Correlation - Prabodh Kumar; Ganesh Paramasivam; Tom Devasia; Mukund Prabhu; Maneesh K. Rai; K. Prakashini; Sandeep Mallya; Dinesh Reghunathan; A. Megha; Krishnananda Nayak; Rajasekhar Moka (Indian Journal of Clinical Biochemistry, 2024)

Mapping of understorey invasive plant species clusters of Lantana camara and Chromolaena odorata using airborne hyperspectral remote sensing - Bodi Surya Pratap Chandra Kishore; Amit Kumar; Purabi Saikia; Nikhil Lele; Parul Srivastava; Sandeep Pulla; Hebbalalu Suresh; Bimal Kumar Bhattarcharya; Mohammed Latif Khan; Raman Sukumar (Advances in Space Research, 2024)

Stress-mitigating behavior of glycine betaine to enhance growth performance by suppressing the oxidative stress in Pb-stressed barley genotypes - Jyoti Sharma; Sandeep Kumar; Vikram Kumar; Pooja Singh; Pradeep Khyalia; Sakshi Saini; Priyanka Sharma; Ajay Kumar; Asha Sharma (Environmental Science and Pollution Research, 2023)

Carbon dots as potential candidate for photocatalytic treatment of dye wastewater - Tripti Tripti; Permender Singh; Neeru Rani; Sandeep Kumar; Krishan Kumar; Parmod Kumar (Environmental Science and Pollution Research, 2023)

Modelling of 1991 Uttarkashi and 2011 Indo-Nepal earthquakes using the modified semi-empirical technique by integrating site-specific quality factor - Monika; Sandeep; Parveen Kumar; Sonia Devi; A Joshi (Journal of Earth System Science, 2023)

Preparation of coated MgFe layered double hydroxide nanoparticles on cement kiln dust and intercalated with sodium dodecyl sulfate as an intermediate layer for the adsorption of estrogen from water - Mohammed B. Abdul-Kareem; Hayder M. Rashid; Waqed H. Hassan; Nadhir Al-Ansari; Sandeep Kumar Lakhera; Mohammad Rafe Hatshan; Ayad A.H. Faisal (Chemosphere, 2023)

Life cycle assessment of fermentative production of lactic acid from bread waste based on process modelling using pinch technology - Kumar Raja Vanapalli; Rajarshi Bhar; Sunil K. Maity; Brajesh K. Dubey; Sandeep Kumar; Vinod Kumar (Science of The Total Environment, 2023)

Potential role of hyperimmune milk as a source of passive immunotherapy against COVID-19: A review - Parminder Singh; Sandeep Ghatak; Pavan Kumar; Nitin Mehta (International Dairy Journal, 2023)

Cobalt ferrite/semiconducting single-walled carbon nanotubes based field-effect transistor for determination of carbamate pesticides - T.H. Vignesh Kumar; Jerome Rajendran; Raji Atchudan; Sandeep Arya; Mani Govindasamy; Mohamed A. Habila; Ashok K. Sundramoorthy (Environmental Research, 2023)

Evaluation of synergistic adsorption approach for terbinafine removal by cotton shell powder immobilized zerovalent copper: Adsorption kinetics and DFT simulation - Parminder Kaur; Khadim Hussain; Atul Kumar; Janpreet Singh; J. Nagendra Babu; Sandeep Kumar (Environmental Nanotechnology, Monitoring & Management, 2023)

Fabrication of CuO/ZnO heterojunction photocatalyst for efficient photocatalytic degradation of tetracycline and ciprofloxacin under direct sun light - Karina Bano; Sandeep Kaushal; Basant Lal; Sanjeev Kumar Joshi; Ranvijay Kumar; Prit Pal Singh (Environmental Nanotechnology, Monitoring & Management, 2023)

Electrochemiluminescent quantum dots as emerging next generation sensing platforms - Jyotsana Mehta; Neeraj Dilbaghi; Nitin Kumar Singhal; Giovanna Marrazza; Ajeet Kaushik; Sandeep Kumar (Chemical Engineering Journal, 2023)

Converting waste to resource: Utilisation of elemental S and consortia of halo–alkaliphilic S–oxidisers for preparation of acidified compost from organic wastes - Sandeep Bedwal; Nirmalendu Basak; Arvind Kumar Rai; Parul Sundha; Subedar Patel; Dev Raj; Anita Mann; Sanjay Kumar; Priyanka Chandra; Rajender Kumar Yadav (Bioresource Technology Reports, 2023)

A Comprehensive Review on Handling of Plastic Waste For Energy Generation—Current Status and Future Challenges - Abdul Sattar Jatoi; Jawad Ahmed; Nabisab Mujawar Mubarak; Muhammad Shuaib Shaikh; Sandeep Kumar; Muhammad Ismail Ahmed; Rama Rao Karri (Water, Air, & Soil Pollution, 2023)

Hydrogeochemical Characterization and Assessment of Water Suitability for Irrigation in Salt-Affected Area of Israna block, Haryana, India - Seema Chahal; Sandeep Kumar Gautam; Paulraj R (Water Conservation Science and Engineering, 2023)

Effect of supplementation of fennel seed powder on intake, growth performance, gut health and economics in goats - Amit Kumar Singh; Anil Kumar; Sandeep Kumar; Sanjay Kumar (Tropical Animal Health and Production, 2023)

A comparative analysis of root traits in diverse wheat seedlings screened under optimum and low nitrogen stress in hydroponics - Deepti Tiwari; Neha Anand; Sandeep Sharma; Tarun Kumar; Renu Pandey (Plant Physiology Reports, 2023)

Xylobiose treatment triggers a defense-related response and alters cell wall composition - Bhagwat Prasad Dewangan; Arunima Gupta; Rajan Kumar Sah; Shouvik Das; Sandeep Kumar; Saikat Bhattacharjee; Prashant Anupama-Mohan Pawar (Plant Molecular Biology, 2023)

Turtle and tortoise mitogenomes under contrasting positive selection pressure - Subhashree Sahoo; Ajit Kumar; Jagdish Rai; Sandeep Kumar Gupta (Organisms Diversity & Evolution, 2023)

Exploration of a library of piperonylic acid-derived hydrazones possessing variable aryl functionalities as potent dual cholinesterase and monoamine oxidase inhibitors - V. Pavan Kumar; M. S. Vishnu; Sandeep Kumar; Shivani Jaiswal; Senthil Raja Ayyannan (Molecular Diversity, 2023)

Europium-doped cerium oxide nanoparticles: investigating oxygen vacancies and their role in enhanced photocatalytic and magnetic properties - Ankita Ankita; Surjeet Chahal; Saurabh Singh; Sandeep Kumar; Parmod Kumar (Environmental Science and Pollution Research, 2023)

Persistence and dissipation kinetics of novaluron 9.45% + lambda-cyhalothrin 1.9% ZC insecticides in tomato crop under semi-arid region - Abdul Rashid Khan Pathan; Bhanwar Lal Jakhar; Shish Ram Dhaka; Mukesh Nitharwal; Hanuman Singh Jatav; Ram Gopal Dudwal; Amit Kumar Yadav; Sandeep Kumar Choudhary; Vishnu Gauttam; Vishnu D. Rajput; Tatiana Minkina (Environmental Geochemistry and Health, 2023)

Genetic evaluation and characterization of anatomical and physicochemical properties in Grevillea robusta: an alternative commercial agroforestry species - Maneesh S. Bhandari; Aman Dabral; Sandeep Maikhuri; Anchal Bisht; Garima Thapliyal; Rama Kant; Rajendra K. Meena; Dheerendra Kumar; Vikas Rana (Journal of the Indian Academy of Wood Science, 2023)

Effects of sterilization methods and plant growth regulators on in vitro regeneration and tuberization in Gloriosa superba (L.) - Dexter Achu Mosoh; Ashok Kumar Khandel; Sandeep Kumar Verma; Wagner A. Vendrame (In Vitro Cellular & Developmental Biology - Plant, 2023)

Utilizing industrial wastes as compost in wheat-rice production to improve the above and below-ground ecosystem services - Gourisankar Pradhan; Ram Swaroop Meena; Sandeep Kumar; Rattan Lal (Agriculture, Ecosystems & Environment, 2023)

Investigation of indoor air pollutants in different environmental settings and their health impact: a case study of Dehradun, India - Abhishek Nandan; Prasenjit Mondal; Sandeep Kumar; Nihal Anwar Siddiqui; Shambhavi Sinha; Sudalai Subramani; Akshi Kunwar Singh; Sivashankar Raja; Chaudhery Mustansar Hussain (Air Quality, Atmosphere & Health, 2023)

Carbon-based nanomaterials: systematic enumeration and proficient template for detection and remediation of hazardous pollutants - Navish Kataria; Vinod Kumar Garg; Parmod Kumar; Changseok Han; Ioannis Anastopoulos; Sandeep Kumar (Environmental Science and Pollution Research, 2023)

Current trends in the development of soy-based foods containing probiotics and paving the path for soy-synbiotics - Minnu Sasi; Sandeep Kumar; Muzaffar Hasan; Arpitha S. R.; Enriqueta Garcia-Gutierrez; Sweta Kumari; Om Prakash; Lata Nain; Archana Sachdev; Anil Dahuja (Critical Reviews in Food Science and Nutrition, 2023)

Understanding farmer views of precision agriculture profitability in the U.S. Midwest - Tong Wang; Hailong Jin; Heidi Sieverding; Sandeep Kumar; Yuxin Miao; Xudong Rao; Oladipo Obembe; Ali Mirzakhani Nafchi; Daren Redfearn; Stephen Cheye (Ecological Economics, 2023)

Snow/Ice Melt, Precipitation, and Groundwater Contribute to the Sutlej River System - Suneel Kumar Joshi; Somil Swarnkar; Sandeep Shukla; Sudhir Kumar; Sanjay Jain; Sneha Gautam (Water, Air, & Soil Pollution, 2023)

Fishery, growth, mortality, and stock assessment of endangered Tor putitora from Tehri dam reservoir, Uttarakhand, Himalayan foothills of India in relation to environmental variables - Dibakar Bhakta; Basanta Kumar Das; Upendra Singh; Archisman Ray; Canciyal Johnson; Venkatesh Ramrao Thakur; Sandeep Kumar Mishra; Sushil Kumar Verma; Absar Alam; Dharam Nath Jha (Environmental Monitoring and Assessment, 2023)

A comparative study on the mechanical and acid resistance characteristics of ambient temperature-cured glass waste and fly ash-based geopolymeric masonry mortars - Sourav Kumar Das; Sandeep Shrivastava (Environment, Development and Sustainability, 2023)

A network pharmacology approach to explore pharmacological mechanisms of Asparagus racemosus for ameliorative effect in epilepsy and comorbid progressive memory dysfunction - Baldeep Kaur; Sandeep Kumar; Arvinder Kaur; Rajesh Kumar Goel (In Silico Pharmacology, 2023)

Subsurface flow constructed wetlands for treating of simulated cadmium ions-wastewater with presence of Canna indica and Typha domingensis - Ayad A.H. Faisal; Duaa S. Taha; Waqed H. Hassan; Sandeep Kumar Lakhera; Sabah Ansar; Samjhana Pradhan (Chemosphere, 2023)

Salicylic acid alleviates salt-induced phytotoxicity by modulating physiochemical attributes and upregulating the AsA-GSH cycle and glyoxalase system in Capsicum annuum L. seedlings - Sandeep Kumar Barwal; Chanchal Goutam; Chandrika Chauhan; Yerramilli Vimala; Mohammed Nasser Alyemeni; Parvaiz Ahmad; Kadambot H.M. Siddique (South African Journal of Botany, 2023)

Precursor-dependent fabrication of exfoliated graphitic carbon nitride (gCN) for enhanced photocatalytic and antimicrobial activity under visible light irradiation - Prerna Attri; Preeti Garg; Pallavi Sharma; Rajender Singh; Moondeep Chauhan; Dong-Kwon Lim; Sandeep Kumar; Ganga Ram Chaudhary (Journal of Cleaner Production, 2023)

Exploring the role of microbes for the management of persistent organic pollutants - Manoj Kumar; Sandeep Kaur Saggu; Pritu Pratibha; Sunil Kumar Singh; Shiv Kumar (Journal of Environmental Management, 2023)

Recent advancement in nanomaterials for the detection and removal of uranium: A review - Neeru Rani; Permender Singh; Sandeep Kumar; Parmod Kumar; Vinita Bhankar; Nisha Kamra; Krishan Kumar (Environmental Research, 2023)

Taxonomy and genesis of soils in contrasting ecosystems of Southern Western Ghats, India - P.S. Vishnu; S. Sandeep; K.S. Anil Kumar (CATENA, 2023)

India's renewable energy research and policies to phase down coal: Success after Paris agreement and possibilities post-Glasgow Climate Pact - Kripal Singh; Ram Swaroop Meena; Sandeep Kumar; Shalini Dhyani; Seema Sheoran; Har Mohan Singh; Vinayak V. Pathak; Zaira Khalid; Anita Singh; Kapil Chopra; Somvir Bajar; Faiz Ahmad Ansari; et al. (Biomass and Bioenergy, 2023)

The flower of Hypericum perforatum L.: A traditional source of bioactives for new food and pharmaceutical applications - Surbhi Kapoor; Rajat Chandel; Ramandeep Kaur; Satish Kumar; Raj Kumar; Sandeep Janghu; Amarjeet Kaur; Vikas Kumar (Biochemical Systematics and Ecology, 2023)

Heterologous expression and characterization of ToxA1 haplotype from India and its interaction with Tsn1 for spot blotch susceptibility in spring wheat - Ranjan Kumar Chaubey; Dharamsheela Thakur; Sudhir Navathe; Sandeep Sharma; Vinod Kumar Mishra; Pawan Kumar Singh; Ramesh Chand (Molecular Biology Reports, 2023)

Maximizing soil organic carbon stocks under cover cropping: insights from long-term agricultural experiments in North America - Yajun Peng; Elizabeth L. Rieke; Inderjot Chahal; Charlotte E. Norris; Ken Janovicek; Jeffrey P. Mitchell; Kraig L. Roozeboom; Zachary D. Hayden; Jeffrey S. Strock; Stephen Machado; Virginia R. Sykes; Bill Deen; et al. (Agriculture, Ecosystems & Environment, 2023)

The impact of different fertiliser management options and cultivars on nitrogen use efficiency and yield for rice cropping in the Indo-Gangetic Plain: Two seasons of methane, nitrous oxide and ammonia emissions - Arti Bhatia; Nicholas J. Cowan; Julia Drewer; Ritu Tomer; Vinod Kumar; Shikha Sharma; Ankita Paul; Niveta Jain; Sandeep Kumar; Girish Jha; Renu Singh; Radha Prasanna; et al. (Agriculture, Ecosystems & Environment, 2023)

Influence of dietary microalgal concentrates on growth, survival and health status of Penaeus vannamei - K. P. Sandeep; T. Sivaramakrishnan; S. Sudhin; J. A. J. Raymond; N. S. Sudheer; R. Ananda Raja; Sujeet Kumar; J. Syama Dayal; C. P. Balasubramanian; Paramita Banerjee Sawant; N. K. Chadha; K. Ambasankar (Aquaculture International, 2023)

Yield maximization in wheat through nutrient management and plant growth regulators - Ishavjot Singh Mandian; Sandeep Manuja; Surinder Singh Rana; Navjot Rana; Sarwan Kumar; Gurpreet Singh (Environment, Development and Sustainability, 2023)

Magnetic graphene oxide carbon dot nanocomposites as an efficient quantification tool against parabens in water and cosmetic samples - Sandeep Kumar; Shikha Bhogal; Ashok Kumar Malik; Jatinder Singh Aulakh (Environmental Science and Pollution Research, 2023)

Lithospheric architecture beneath the Amsterdam-St. Paul plateau, Southern Indian Ocean using the integrated gravity, magnetic and seismological study - Pankaj Kumar; Pabitra Singha; Dibakar Ghosal; Jensen Jacob; Sandeep Gupta (Tectonophysics, 2023)

Microplastics in landfill leachate: Occurrence, health concerns, and removal strategies - Sandeep Singh; Sandeep K. Malyan; Chinmay Maithani; Sujata Kashyap; Vinay Kumar Tyagi; Rajesh Singh; Sarthak Malhotra; Manish Sharma; Amit Kumar; Bijay K. Panday; R.P. Pandey (Journal of Environmental Management, 2023)

Comparative Evaluation of Low- and Medium-Pressure UV Lamps for Photo-degradation of RDX Wastewater - Pallvi Bhanot; S. Mary Celin; Praveen Sharma; Sandeep Kumar Sahai; Anchita Kalsi (Water, Air, & Soil Pollution, 2023)

Growth Stage-Dependent Foliar Application of Iron Improves its Mobilisation Towards Grain and Enhances Fe Use Efficiency in Rice - Sandeep Sharma; Renu Pandey; Christian O. Dimkpa; Arun Kumar; Prem S. Bindraban (Journal of Plant Growth Regulation, 2023)

Efficacy of nanoparticles against purple blotch (Alternaria porri) of onion - G. Chaithanya; Atul Kumar; D. Vijay; Praveen Kumar Singh; Zakir Hussain; Sudipta Basu; Sandeep Kumar Lal (Indian Phytopathology, 2023)

Oral delivery of RNAi for cancer therapy - Humayra Afrin; Renu Geetha Bai; Raj Kumar; Sheikh Shafin Ahmad; Sandeep K. Agarwal; Md Nurunnabi (Cancer and Metastasis Reviews, 2023)

Characterization of plant growth-promoting, antifungal, and enzymatic properties of beneficial bacterial strains associated with pulses rhizosphere from Bundelkhand region of India - Raj K. Mishra; Sonika Pandey; U. S. Rathore; Monika Mishra; Krishna Kumar; Sandeep Kumar; L. Manjunatha (Brazilian Journal of Microbiology, 2023)

Screening of ridge gourd genotypes for resistance to downy mildew (Pseudoperonospora cubensis) - H N Lavanya; B Varalakshmi; M Pitchaimuthu; S Sriram; R Venugopalan; G M Sandeep kumar (Australasian Plant Pathology, 2023)

Assessing the biomass-based carbon dots and their composites for photocatalytic treatment of wastewater - Permender Singh; Neeru Rani; Sandeep Kumar; Parmod Kumar; Brij Mohan; Pallavi; Vinita Bhankar; Navish Kataria; Ravi Kumar; Krishan Kumar (Journal of Cleaner Production, 2023)

Insights into the evolution of the Dharwar craton, South India through three dimensional P-wave velocity imaging of upper mantle - Sudesh Kumar; Sandeep Gupta (Journal of Asian Earth Sciences, 2023)

Phenolic fingerprint, proximate analysis and nutraceutical effects of Garcinia talbotii, an under-utilized functional food endemic to Western Ghats - R. Sandeep Kumar Jain; P. Meghana; N. Prashanth; J.U. Santhosh Kumar; N.D. Satyanarayan; R. Sharath; H. Raja Naika; H.M. Kumaraswamy (Food Bioscience, 2023)

Functionalization of Pristine Coconut Husk (Cocos nucifera) with Sodium Vinyl Sulfonate for Removal of Toxic Hg2+ Ions from Wastewater - Kavita Devi; Anamika Ramchaik; Ghanshyam S. Chauhan; Sunita Ranote; Sandeep Chauhan; Kiran Kumar (Water, Air, & Soil Pollution, 2023)

Indian summer monsoon simulations in successive generations of the NCAR Community Atmosphere Model - Ravi Kumar; Raju Pathak; Sandeep Sahany; Saroj K. Mishra (Theoretical and Applied Climatology, 2023)

Study of the effectiveness of wavelet genetic programming model for water quality analysis in the Uttar Pradesh region - Bhawna Saxena; Mansi Gaonkar; Sandeep Kumar Singh (Environmental Monitoring and Assessment, 2023)

Evaluation of growth, yield, economics and soil properties of agri-horticulture systems in mid-hill situations of Himalayas - Abhishek Pratap Singh; Arvind Bijalwan; Tejpal Singh Bisht; Bhupendra Singh; Sandeep Kumar; Naveen Tariyal (Agroforestry Systems, 2023)

Transferability and reproducibility of exposed air-liquid interface co-culture lung models - Hedwig M. Braakhuis; Eric R. Gremmer; Anne Bannuscher; Barbara Drasler; Sandeep Keshavan; Barbara Rothen-Rutishauser; Barbara Birk; Andreas Verlohner; Robert Landsiedel; Kirsty Meldrum; Shareen H. Doak; Martin J.D. Clift; et al. (NanoImpact, 2023)

Involvement of type-1 pathway in phototoxicity of benzo[ghi]perylenean ingredient of tattoo ink at ambient exposure of UVR and sunlight - Sandeep Negi; Deepti Chopra; Saumya Shukla; Apeksha Vikram; Sunil Kumar Patel; Lakshmi Bala; Ashish Dwivedi; Ratan Singh Ray (Journal of Photochemistry and Photobiology B: Biology, 2023)

Benzo(ghi)perylene (BgP) a black tattoo ingredient induced skin toxicity via direct and indirect mode of DNA damage under UVA irradiation - Sandeep Negi; Saumya Shukla; Sunil Kumar Patel; Apeksha Vikram; Prakriti Gaur; Mohd Danish Kamar; Diksha Pathania; Sumana Y. Kotian; Madhu Bala; Priyanka Rana; Lakshmi Bala; Akhilesh K. Yadav; et al. (Chemico-Biological Interactions, 2023)

Black Carbon Characteristics over a Semi-urban Environment in the Garhwal Himalayas - A. S. Panicker; K. Sandeep; A. S. Gautam; S. Kumar; G. Beig; R. Latha; B. S. Murthy (Pure and Applied Geophysics, 2023)

Influence of temperature on insecticidal toxicity and detoxifying enzymes to Spodoptera frugiperda - Sandeep Kumar; S. B. Suby; Pashupat Vasmatkar; Suresh M. Nebapure; Naveen Kumar; Gagana Kumar Mahapatro (Phytoparasitica, 2023)

Effects of dietary ascorbic acid on growth, hematology, intestinal histology, and resistance to Vibrio harveyi in early life stage of milkfish - Thirugnanamurthy Sivaramakrishnan; Thangaraj Sathish kumar; Kizhakkekarammal Puthiyedathu Sandeep; Aritra Bera; Ramalingam Ananda Raja; Sujeet kumar; Muniyandi Kailasam; Nathan Felix; Kondusamy Ambasankar (Fisheries Science, 2023)

Spatio-temporal variations in oxygen and deuterium isotope of different water sources in Sikkim Himalayas: An understanding towards regional scale basin hydrology - Sandeep Kumar Mondal; Rishikesh Bharti; Sudhir Kumar (Journal of Hydrology, 2023)

Enablers to achieve zero hunger through IoT and blockchain technology and transform the green food supply chain systems - Mukesh Kumar; Vikas Kumar Choubey; Rakesh D. Raut; Sandeep Jagtap (Journal of Cleaner Production, 2023)

Adsorption of harmful dyes and antimicrobial studies utilizing recyclable ZnO, its composites with conventionally used activated carbon, and waste orange peel as a greener approach - Wandit Ahlawat; Neeraj Dilbaghi; Rajesh Kumar; Nitin Kumar Singhal; Ajeet Kaushik; Sandeep Kumar (Journal of Environmental Chemical Engineering, 2023)

A simple protocol to functionalize whole pine needles biowaste for effective and selective methylene blue adsorption - Sunita Ranote; Sandeep Chauhan; Kiran Kumar; Ghanshyam S. Chauhan (Bioresource Technology Reports, 2023)

Comparative performance and 16S amplicon sequencing analysis of deep and shallow cells of a full scale HFCW having sequentially decreasing depths reveals vast enhancement potential - Saurabh Singh; Chinmay Maithani; Sandeep K. Malyan; Abhishek Soti; Niha Mohan Kulshreshtha; Rajesh Singh; Urmila Brighu; Akhilendra Bhushan Gupta; Jhalesh Kumar; Shweta Yadav; Omkar Singh; V.C. Goyal (Bioresource Technology Reports, 2023)

A Review on Photocatalysis Used For Wastewater Treatment: Dye Degradation - Harita Kumari; Sonia; Suman; Rohit Ranga; Surjeet Chahal; Seema Devi; Sourabh Sharma; Sandeep Kumar; Parmod Kumar; Suresh Kumar; Ashok Kumar; Rajesh Parmar (Water, Air, & Soil Pollution, 2023)

Deciphering the melatonin-mediated response and signalling in the regulation of heavy metal stress in plants - Muhammad Ahsan Altaf; Nitin Sharma; Dipali Srivastava; Sayanti Mandal; Sandeep Adavi; Rupak Jena; Rakesh Kumar Bairwa; Abilash Valsala Gopalakrishnan; Awadhesh Kumar; Abhijit Dey; Milan Kumar Lal; Rahul Kumar Tiwari; et al. (Planta, 2023)

Evidence of biotic recovery through the Cretaceous/Palaeogene transition from the Mahadeo-Cherrapunji succession in the Meghalaya shelf, India - Sucharita Pal; Kalpana Munnuru Singamshetty; Jaya Prakash Shrivastava; Sanjay Kumar Mukhopadhyay; Sandeep Hamilton (Palaeobiodiversity and Palaeoenvironments, 2023)

Sorption behavior studies of Cs and its migration in soil samples around Visakhapatnam, India - Sukanta Maity; P. Sandeep; S. Mishra; C. B. Dusane; D. K. Chaudhary; P. Padma Savitri; J. Sudhakar; Anilkumar S. Pillai; A. Vinod Kumar (Environmental Monitoring and Assessment, 2023)

Plastic Waste-Derived Carbon Dots: Insights of Recycling Valuable Materials Towards Environmental Sustainability - Arpita; Parmod Kumar; Navish Kataria; Nishita Narwal; Sandeep Kumar; Ravi Kumar; Kuan Shiong Khoo; Pau Loke Show (Current Pollution Reports, 2023)

A first report on the spatial and temporal variability of microplastics in coastal soils of an urban town in south-western India: Pre- and post-COVID scenario - M. Reethu; R. Biswajit; G.H. Aravind; A.K. Rafaz; K. Sandeep; A.V. Sijinkumar; Anish Kumar Warrier (Marine Pollution Bulletin, 2023)

A study in the synthesis of new Pinus wallichiana derived spherical nanocellulose hydrogel and its evaluation as malachite green adsorbent - Pooja Jamwal; Ghanshyam S. Chauhan; Puneet Kumar; Babita Kumari; Kiran Kumar; Sandeep Chauhan (Sustainable Chemistry and Pharmacy, 2023)

Global distribution of pesticides in freshwater resources and their remediation approaches - Sandeep Singh; Meenakshi Rawat; Sandeep K. Malyan; Rajesh Singh; Vinay Kumar Tyagi; Kaptan Singh; Sujata Kashyap; Sumant Kumar; Manish Sharma; B.K. Panday; R.P. Pandey (Environmental Research, 2023)

Highly customized porous TiO2-PANI nanoparticles with excellent photocatalytic efficiency for dye degradation - Harpreet Kaur; Sanjeev Kumar; Sandeep Kaushal; Rahul Badru; Prit Pal Singh; Arivalagan Pugazhendhi (Environmental Research, 2023)

Tailoring crops with superior product quality through genome editing: an update - K. T. Ravikiran; R. Thribhuvan; Seema Sheoran; Sandeep Kumar; Amar Kant Kushwaha; T. V. Vineeth; Manisha Saini (Planta, 2023)

Sensitivity of WRF/Chem simulated PM2.5 to initial/boundary conditions and planetary boundary layer parameterization schemes over the Indo-Gangetic Plain - Preeti Gunwani; Gaurav Govardhan; Chinmay Jena; Prafull Yadav; Santosh Kulkarni; Sreyashi Debnath; Pooja V. Pawar; Manoj Khare; Akshara Kaginalkar; Rajesh Kumar; Sandeep Wagh; Dilip Chate; et al. (Environmental Monitoring and Assessment, 2023)

Brain Tumor Classification Using Deep Neural Network and Transfer Learning - Sandeep Kumar; Shilpa Choudhary; Arpit Jain; Karan Singh; Ali Ahmadian; Mohd Yazid Bajuri (Brain Topography, 2023)

Sex-specific alteration in human muscle transcriptome with age - Mohini Gharpure; Jie Chen; Resheek Nerella; Sagar Vyavahare; Sandeep Kumar; Carlos M. Isales; Mark Hamrick; Satish Adusumilli; Sadanand Fulzele (GeroScience, 2023)

Correction to: Greenhouse gas emissions from hydroelectric reservoirs: mechanistic understanding of influencing factors and future prospect - Amit Kumar; Amit Kumar; Ashish K. Chaturvedi; Neeshu Joshi; Raju Mondal; Sandeep K. Malyan (Environmental Science and Pollution Research, 2023)

Greenhouse gas emissions from hydroelectric reservoirs: mechanistic understanding of influencing factors and future prospect - Amit Kumar; Amit Kumar; Ashish K. Chaturvedi; Neeshu Joshi; Raju Mondal; Sandeep K. Malyan (Environmental Science and Pollution Research, 2023)

Identification and validation of novel genomic SSR markers for molecular characterization of guava (Psidium guajava L.) - Sandeep Kumar; Anshuman Singh; Ashish Yadav; Anju Bajpai; Nitin Kumar Singh; Shailendra Rajan; Mala Trivedi; Muthukumar M (South African Journal of Botany, 2023)

Metal doped BiOCl nano-architectures (M-BiOCl, M = Ni, Mo, Cd, Co) for efficient visible light photocatalytic and antibacterial behaviour - Prerna Attri; Preeti Garg; Moondeep Chauhan; Rajender Singh; Ramesh K. Sharma; Sandeep Kumar; Dong-Kwon Lim; Ganga Ram Chaudhary (Journal of Environmental Chemical Engineering, 2023)

Editorial overview: Nanomaterials as materials for removal, extraction, sensing, and detection of environmental contaminants - Muhammad Sajid; Sandeep Kumar Verma (Current Opinion in Environmental Science & Health, 2023)

Food-grade xylitol production from corncob biomass with acute oral toxicity studies - Diptarka Dasgupta; Vishal Ahuja; Raghuvir Singh; Snehal More; Sandeep Mudliar; Madan Kumar (World Journal of Microbiology and Biotechnology, 2023)

Multi-omics assisted breeding for biotic stress resistance in soybean - Ashita Bisht; Dinesh Kumar Saini; Baljeet Kaur; Ritu Batra; Sandeep Kaur; Ishveen Kaur; Suruchi Jindal; Palvi Malik; Pawanjit Kaur Sandhu; Amandeep Kaur; Balwinder Singh Gill; Shabir Hussain Wani; et al. (Molecular Biology Reports, 2023)

Spatio-Temporal Variations in the Effective Snow/Glacier Coverage in the Sikkim Himalayas - Sandeep Kumar Mondal; Rishikesh Bharti (Journal of the Indian Society of Remote Sensing, 2023)

The loss of cardiac SIRT3 decreases metabolic flexibility and proteostasis in an age-dependent manner - Ping Li; Maria F. Newhardt; Satoshi Matsuzaki; Craig Eyster; Atul Pranay; Frederick F. Peelor; Albert Batushansky; Caroline Kinter; Kumar Subramani; Sandeep Subrahmanian; Jasimuddin Ahamed; Pengchun Yu; et al. (GeroScience, 2023)
SIRT3 is a longevity factor that acts as the primary deacetylase in mitochondria. Although ubiquitously expressed, previous global SIRT3 knockout studies have shown primarily a cardiac-specific phenotype. Here, we sought to determine how specifically knocking out SIRT3 in cardiomyocytes (SIRTcKO mice) temporally affects cardiac function and metabolism. Mice displayed an age-dependent increase in cardiac pathology, with 10-month-old mice exhibiting significant loss of systolic function, hypertrophy, and fibrosis. While mitochondrial function was maintained at 10 months, proteomics and metabolic phenotyping indicated SIRT3 hearts had increased reliance on glucose as an energy substrate. Additionally, there was a significant increase in branched-chain amino acids in SIRT3cKO hearts without concurrent increases in mTOR activity. Heavy water labeling experiments demonstrated that, by 3 months of age, there was an increase in protein synthesis that promoted hypertrophic growth with a potential loss of proteostasis in SIRT3cKO hearts. Cumulatively, these data show that the cardiomyocyte-specific loss of SIRT3 results in severe pathology with an accelerated aging phenotype.

Impact of tillage cum crop establishment methods and nutrient management strategies on wet rice (Oryza sativa L): crop productivity, water footprint, soil health and profitability in typic Ustochrept soils under semi-arid sub-tropical environment - Mandapelli Sharath Chandra; R. K. Naresh; Rajan Bhatt; Manisha; Papita H. Gourkhede; Rahul Kumar; Praveen V. Kadam; Sandeep Gawdiya (Paddy and Water Environment, 2023)

Therapeutic potential of melatonin and its derivatives in aging and neurodegenerative diseases - Avnish Kumar Verma; Sandeep Singh; Syed Ibrahim Rizvi (Biogerontology, 2023)

Recent Advancement in Nanotechnology for the Treatment of Pharmaceutical Wastewater: Sources, Toxicity, and Remediation Technology - Sandeep Kumar; Sangita Yadav; Navish Kataria; Amit Kumar Chauhan; Seema Joshi; Renuka Gupta; Parmod Kumar; Jun Wei Roy Chong; Kuan Shiong Khoo; Pau Loke Show (Current Pollution Reports, 2023)

Enhanced photocatalytic degradation of organic dye by CeO2/CNT/GO hybrid nanocomposites under UV light for wastewater treatment - Surjeet Chahal; Lakshita Phor; Ashok Kumar; Suresh Kumar; Sandeep Kumar; Ravi Kumar; Parmod Kumar (Environmental Science and Pollution Research, 2023)

Semen characteristics and artificial insemination in dromedary camels - Govind Narayan Purohit; Sumant Vyas; Vishal Yadav; Satish Nain; Ashok Kumar Chaudhary; Amit Kumar; Sandeep Dholpuria; Chandra Shekhar Saraswat (Small Ruminant Research, 2023)

Novel hybrids of quinoline with pyrazolylchalcones as potential antimalarial agents: Synthesis, biological evaluation, molecular docking and ADME prediction - Ajay Kumar; Sandeep Jain; Shilpi Chauhan; Shilpy Aggarwal; Deepika Saini (Chemico-Biological Interactions, 2023)

Docking Based Screening of Potent Flavonoids as CHK2 Inhibitors from Genus Miliusa - C. Inchara Moodbagil; Riaz Mahmood; R. Sandeep Kumar Jain; P. Meghana; N. Prashanth; H. M. Kumaraswamy; R. Sharath (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2023)

New Luminescent Pyridine-based Disc type Molecules: Synthesis, Photophysical, Electrochemical, and DFT studies - Deepak Devadiga; T. N. Ahipa; S. Vanishree Bhat; Sandeep Kumar (Journal of Fluorescence, 2023)

PKNNet: a novel feature learning architecture for vegetation mapping using remote sensing hyperspectral image classification - Pradeep Kumar Ladi; Murali Gopal Kakita; Ratnakar Dash; Sandeep Kumar Ladi (Earth Science Informatics, 2023)

Simulating crop yield estimation and prediction through geospatial data for specific regional analysis - Sandeep Kumar Mathivanan; Prabhu Jayagopal (Earth Science Informatics, 2023)

Estimation of Chlorophyll-a, TSM and salinity in mangrove dominated tropical estuarine areas of Hooghly River, North East Coast of Bay of Bengal, India using sentinel-3 data - Ismail Mondal; Aakash De; Subhanil Nandi; Sandeep Thakur; Mini Raman; Felix Jose; Tarun Kumar De (Acta Geophysica, 2023)

Identification of corticosteroids as potential inhibitor against glycolytic enzyme hexokinase II role in cancer glycolysis pathway: a molecular docking study - Abhishek Kumar Verma; Vijay Kumar Srivastava; Sandeep Kumar Srivastava (Vegetos, 2023)

Rice straw recycling: A sustainable approach for ensuring environmental quality and economic security - Anjani KUMAR; Amaresh Kumar NAYAK; Sandeep SHARMA; Ansuman SENAPATI; Debasis MITRA; Bipasa MOHANTY; Seenichamy Rathinam PRABHUKARTHIKEYAN; Kuttalingam Gopalasubramanian SABARINATHAN; Indra MANI; Rajendra Singh GARHWAL; Sugitha THANKAPPAN; Mahapatra Smruthi SAGARIKA; et al. (Pedosphere, 2023)

Carbon quantum dots@metal–organic framework based catalytic nucleic acid fluorescent system for highly sensitive and selective detection of Pb2+ in aqueous solutions - Shikha Jain; Neeraj Dilbaghi; Nitin Kumar Singhal; Ajeet Kaushik; Ki-Hyun Kim; Sandeep Kumar (Chemical Engineering Journal, 2023)

Presynchronization with simultaneous administration of GnRH and prostaglandin F2α (PGF2α) 7 days prior to Ovsynch improves reproductive profile in Hariana zebu cow - Gitesh Saini; Sandeep Kumar; Anand Kumar Pandey; Harender Singh; Meenakshi Virmani (Tropical Animal Health and Production, 2023)

Development and evaluation emulgel for effective management of the imiquimod-induced psoriasis - Safiya Sulthana; Padakanti Sandeep Chary; Valamla Bhavana; Ekta Pardhi; Shashi Bala Singh; Neelesh Kumar Mehra (Inflammopharmacology, 2023)

A comprehensive study of radon in drinking waters of Hanumangarh district and the assessment of resulting dose to local population - Amit Kumar Singla; Sandeep Kanse; Sandeep Kansal; Supriya Rani; Rohit Mehra (Environmental Geochemistry and Health, 2023)

Geological setup and physicochemical characteristics of Munger Groups of thermal springs along Munger–Saharsa Ridge Fault, Bihar, India: A conceptual hydrogeochemical model - Archisman Dutta; Ayodhaya Prasad Thapliyal; Pramod Kumar Singh; Sandeep Rohilla; Ramesh Kumar Gupta (Journal of Earth System Science, 2023)

Shrimp shell waste-derived astaxanthin in synergistic combination with its commercial variant augments gonadal maturation and upregulates vitellogenin gene expression of discus (Symphysodon aequifasciatus) - Ramjanul Haque; Paramita Banerjee Sawant; Parimal Sardar; Tincy Varghese; K.A. Martin Xavier; Narinder Kumar Chadha; Jitendra Kumar Sundaray; Chandan Haldar; Prasanta Jana; Sandeep Sankar Pattanaik (Aquaculture, 2023)

Landfill leachate valorization: A potential alternative to burden off resources and support energy systems - Smita S. Kumar; Amit Kumar; Sandeep K. Malyan; Pooja Ghosh; Madan Kumar; Rimika Kapoor; Ajay Kumar Agrawal; Sumit Kumar; Vivek Kumar; Lakhveer Singh (Fuel, 2023)

Hydrogeomorphic and Spatio-Temporal Analysis of Riverine Wetlands in the Interfluvial Zone of Ganga and Sai Rivers, Uttar Pradesh, India - Sandeep Kumar Maddheshiya; Medha Jha; Sanjay Tignath; Nikhilesh Singh (Wetlands, 2023)

Trend Analysis of Nitrogen dioxide (NO2) in Northern Part of India During Paddy Residue Burning Using a Contextual Approach - Sandeep Maithani; Surendra Kumar Sharma (Journal of the Indian Society of Remote Sensing, 2023)

Association of Angiotensin II Type 1 Receptor (AT1R) Gene Polymorphism with Angiotensin II Serum Levels in Patients with Essential Hypertension - M. Prasad; D. Rajarajeswari; K. Ramlingam; R. Viswakumar; B. Suneel; Jyothi Conjeevaram; P. Aruna; Nusrath Fathima; Sandeep Kumar Vishwakarma; Aleem Ahmed Khan (Indian Journal of Clinical Biochemistry, 2023)

Shedding light on taxonomic chaos: Diversity and distribution of South Asian skipper frogs (Anura, Dicroglossidae, Euphlyctis ) - Christophe Dufresnes; Stephen Mahony; Vishal Kumar Prasad; Rachunliu G. Kamei; Rafaqat Masroor; Muazzam Ali Khan; Awadh M. Al-Johany; Kumudani Bala Gautam; Sandeep Kumar Gupta; Leo J. Borkin; Daniel A. Melnikov; Juriy M. Rosanov; et al. (Systematics and Biodiversity, 2022)

Photocatalytic degradation of tetracycline antibiotic and organic dyes using biogenic synthesized CuO/Fe2O3 nanocomposite: pathways and mechanism insights - Sandeep Kaushal; Avdhesh Kumar; Himani Bains; Prit Pal Singh (Environmental Science and Pollution Research, 2022)

Thymoquinone-Loaded Essential Oil–Based Emulgel as an Armament for Anti-psoriatic Activity - Pratik Kharat; Padakanti Sandeep Chary; Valamla Bhavana; Naveen Rajana; Geetanjali Devabattula; Chandraiah Godugu; Shashi Bala Singh; Neelesh Kumar Mehra (AAPS PharmSciTech, 2022)

Lifestyle, Epstein-Barr virus infection, and other factors could impede nasopharyngeal cancer survivorship: a five-year cross-sectional study in North Eastern India - Koustav Chatterjee; Sankar Deb Roy; Koushik Chakraborty; Asmaul Haque; Sudipta Chakrabarti; Syamantak Mukherjee; Sudipa Mal; Nilanjana Das; Sushil Kumar Sahu; Nabanita Roy Chattopadhyay; Piyanki Das; R. Rajendra Reddy; et al. (VirusDisease, 2022)

Study the Effect of Different Pollination Techniques on Date Palm Production - Priyanka Kumawat; Rajendra Singh Rathore; Raksha Pal Singh; Sandeep Kumar (Sugar Tech, 2022)

Enhanced somatic embryogenesis, plant regeneration and total phenolic content estimation in Lycium barbarum L.: a highly nutritive and medicinal plant - Sandeep Kumar Verma; Saikat Gantait; Epsita Mukherjee; Ekrem Gurel (Journal of Crop Science and Biotechnology, 2022)

Morpho-pathological characterization of Sarocladium oryzae causing sheath rot in paddy - M. G. Venkatesh; Atul Kumar; Sandeep Kumar Lal; Bishnu Maya Bashyal; Prolay Kumar Bhowmick; S. C. Dubey; Dinesh Singh; Nagamani Sandra; Shaily Javeria (Indian Phytopathology, 2022)

ICT in disaster management context: a descriptive and critical review - Mandeep Kaur; Pankaj Deep Kaur; Sandeep Kumar Sood (Environmental Science and Pollution Research, 2022)

A novel strategy for classifying spectral-spatial shallow and deep hyperspectral image features using 1D-EWT and 3D-CNN - Sandeep Kumar Ladi; G K Panda; Ratnakar Dash; Pradeep Kumar Ladi (Earth Science Informatics, 2022)

Dietary interventions and molecular mechanisms for healthy musculoskeletal aging - Andrew Murphy; Sagar Vyavahare; Sandeep Kumar; Tae Jin Lee; Ashok Sharma; Satish Adusumilli; Mark Hamrick; Carlos M. Isales; Sadanand Fulzele (Biogerontology, 2022)

Conversion of open pasture to hardwood silvopasture enhanced soil health of an ultisol - Sanjok Poudel; Sangeeta Bansal; Swarup Podder; Bidur Paneru; Sangita Karki; John Fike; Sandeep Kumar (Agroforestry Systems, 2022)

Avian Haemosporidian (Plasmodium and Haemoproteus) Status in Two Bird Groups (Old-World Flycatchers and Thrushes) of India and Their Phylogenetic Relationships with Other Lineages of the World - Vipin; Ashutosh Singh; Vinita Sharma; Narinder Kumar Tripathi; Rajnikant Dixit; Bhim Singh; Chandra Prakash Sharma; Sumit G. Gandhi; Dhananjai Mohan; Sandeep Kumar Gupta (Acta Parasitologica, 2022)

Clinical Diagnosis and Therapeutic Management of Trypanosoma theileri Infection Associated with Peritonitis in Crossbred Cow: A Rare Case Report - Maneesh Sharma; C. S. Patil; Sandeep Saharan; Akhil Kumar Gupta; Snehil Gupta; V. K. Jain (Acta Parasitologica, 2022)

From source to sink: mechanistic insight of photoassimilates synthesis and partitioning under high temperature and elevated [CO2] - Milan Kumar Lal; Nitin Sharma; Sandeep B. Adavi; Eshita Sharma; Muhammad Ahsan Altaf; Rahul Kumar Tiwari; Ravinder Kumar; Awadhesh Kumar; Abhijit Dey; Vijay Paul; Brajesh Singh; Madan Pal Singh (Plant Molecular Biology, 2022)

Design, Fabrication and Evaluation of Stabilized Polymeric mixed micelles for Effective Management in Cancer Therapy - Padakanti Sandeep Chary; Naveen Rajana; Geetanjali Devabattula; Valamla Bhavana; Hoshiyar Singh; Chandraiah Godugu; Santosh Kumar Guru; Shashi Bala Singh; Neelesh Kumar Mehra (Pharmaceutical Research, 2022)

Delineation of detailed crustal seismic velocity structure and Moho depths in the Hyderabad region, eastern Dharwar craton, India - Prantik Mandal; Sudesh Kumar; Sandeep Gupta; B. N. V. Prasad; M. Saidixit (Natural Hazards, 2022)

Simulation of Land Surface Temperature Patterns Over Future Urban Areas—A Machine Learning Approach - Sandeep Maithani; Garima Nautiyal; Archana Sharma; Surendra Kumar Sharma (Journal of the Indian Society of Remote Sensing, 2022)

Augmenting the productivity of tubular solar still using low-cost energy storage materials - Ritesh Krishna Sambare; Satish Kumar Dewangan; Pankaj Kumar Gupta; Sandeep Joshi (Environmental Science and Pollution Research, 2022)

Spatial analysis of soil quality using geospatial techniques in Botanic Garden of Indian Republic, Noida, Uttar Pradesh, India - Deepakshi Babbar; Sandeep Kr. Chauhan; Damini Sharma; Kusum Upadhyay; Mayank D. Dwivedi; Mehebub Sahana; Shailender Kumar (Environmental Sustainability, 2022)
Ex-situ conservation places such as botanical gardens require sufficient soil quality to support introduced species from various phytogeographical zones. The soil quality of the Botanic Garden of Indian Republic (BGIR), Noida, Uttar Pradesh, was evaluated to quantify soil nutrients. The dependency of one nutrient on the other nutrients was investigated using Pearson correlation and Multilinear regression analysis (MLRA). At the 0.05 level of significance, the nutrients Log10S and Log10EC ( r = 0.97), N and OC ( r = 0.98), Mn and OC ( r = 0.97), Mn and N ( r = 0.92), Ca and pH ( r = − 0.91), Cu and Fe ( r = 0.94) were found to be associated. Correspondence Analysis (C.A.) has been performed to find the association of soil elements with the soil type of study site. The spatial indices like NDVI (Normalized Difference Vegetation Index), EVI2 (Enhanced Vegetation Index), ARVI (Atmospherically Resistant Vegetation Index), NPCRI (Normalized Pigment Chlorophyll Index), RDVI (Renormalized Difference Vegetation Index) have shown significant correlation with the Log 10 S, Mg, Log 10 Zn, B and Fe respectively (with respective Pearson correlation coefficient r = 0.88, r = − 0.90, r = − 0.93, r = 0.91, r = 0.92 at P < 0.05). ARVI, along with other indices SCI (Soil Composition Index), NDMI (Normalized Difference Moisture Index), and MSAVI (Modified Soil Adjusted Vegetation Index), are also the predictor variables for Log 10 Zn ( r = − 0.89, r = − 0.88 r = 0.92 at P < 0.05 respectively). MAVI2 (Moisture Adjusted Vegetation Index) positively correlates with OC, Mn content ( r = 0.91, r = 0.93 respectively). MSAVI is negatively interrelated with Ca ( r = − 0.89), SCI is negatively interrelated with Log 10 K ( r = − 0.98), BSI (Bare Soil Index) is positively associated with pH ( r = 0.91), and negatively with Ca ( r = − 0.93). At the same time, other indices like SAVI (Soil Adjusted Vegetation Index), SATVI (Soil Adjusted Total Vegetation Index), NDWI (Normalized Difference Water Index), and DVI (Difference Vegetation Index) have failed to explain the presence of soil nutrients based on spectral reflectance. This study is important for understanding the changing nutrient status of soil at the conservation site for successfully establishing plants from different phytogeographical zones.

Optimization of Gibberellic Acid Production in Endophytic Bacillus cereus Using Response Surface Methodology and Its Use as Plant Growth Regulator in Chickpea - Nitin Baliyan; Sandhya Dhiman; Shrivardhan Dheeman; Sandeep Kumar; Naveen Kumar Arora; Dinesh Kumar Maheshwari (Journal of Plant Growth Regulation, 2022)

Nanomaterials photocatalytic activities for waste water treatment: a review - Permender Singh; Brij Mohan; Vasundhara Madaan; Rohit Ranga; Parveen Kumari; Sandeep Kumar; Vinita Bhankar; Parmod Kumar; Krishan Kumar (Environmental Science and Pollution Research, 2022)

Modeling the effect of climate change on the distribution of threatened medicinal orchid Satyrium nepalense D. Don in India - Devendra Kumar; Sandeep Rawat (Environmental Science and Pollution Research, 2022)

Alterations in bone metabolites with age in C57BL/6 mice model - Dhara Patel; Tae Jin Lee; Sandeep Kumar; Sagar Vyavahare; Alison Worth; William D. Hill; Mark Hamrick; Carlos M. Isales; Rahul S. Shinde; Sadanand Fulzele (Biogerontology, 2022)

Utilizing satellite and UAV data for crop yield prediction and monitoring through deep learning - Sandeep Kumar Mathivanan; Prabhu Jayagopal (Acta Geophysica, 2022)

Neuroprotective and Proneurogenic Effects of Glucosamine in an Internal Carotid Artery Occlusion Model of Ischemia - Priya Jhelum; Mydhili Radhakrishnan; A. R. Sam Paul; Sandeep K. Dey; Avijeet Kamle; Arvind Kumar; Abhay Sharma; Sumana Chakravarty (NeuroMolecular Medicine, 2022)

Unravelling the molecular mechanism of mutagenic factors impacting human health - Keshav Goyal; Harsh Goel; Pritika Baranwal; Aman Dixit; Fahad Khan; Niraj Kumar Jha; Kavindra Kumar Kesari; Pratibha Pandey; Avanish Pandey; Mercilena Benjamin; Ankit Maurya; Vandana Yadav; et al. (Environmental Science and Pollution Research, 2022)

Predicting the distributional range shifts of Rhizocarpon geographicum (L.) DC. in Indian Himalayan Region under future climate scenarios - Devendra Kumar; Aseesh Pandey; Sandeep Rawat; Mayank Joshi; Rajesh Bajpai; Dalip Kumar Upreti; Surendra Pratap Singh (Environmental Science and Pollution Research, 2022)

Fog-Cloud centric IoT-based cyber physical framework for panic oriented disaster evacuation in smart cities - Sahil; Sandeep Kumar Sood (Earth Science Informatics, 2022)

Salicylic acid ameliorates zinc and chromium-induced stress responses in wheat seedlings: a biochemical and computational analysis - Muhammed Khairujjaman Mazumder; Parul Sharma; Debojyoti Moulick; Sandeep Kumar Tata; Shuvasish Choudhury (Cereal Research Communications, 2022)

Self-Assembled Maslinic Acid Attenuates Doxorobucin Induced Cytotoxicity via Nrf2 Signaling Pathway: An In Vitro and In Silico Study in Human Healthy Cells - Jhimli Banerjee; Sk Nurul Hasan; Sovan Samanta; Biplab Giri; Braja Gopal Bag; Sandeep Kumar Dash (Cell Biochemistry and Biophysics, 2022)

Bacteriophage cocktails as antibacterial agents in crop protection - Nitin Baliyan; Sandhya Dhiman; Shrivardhan Dheeman; Vineet Kumar Vishnoi; Sandeep Kumar; Dinesh Kumar Maheshwari (Environmental Sustainability, 2022)

Earthquake Genesis and Earthquake Early Warning Systems: Challenges and a Way Forward - Roshan Kumar; Himanshu Mittal; Sandeep; Babita Sharma (Surveys in Geophysics, 2022)

Genomic insights of beta-lactamase producing Klebsiella quasipneumoniae subsp. similipneumoniae belonging to sequence type 1699 from retail market fish, India - Sudha Sajeev; Muneeb Hamza; Gopalan Krishnan Sivaraman; Sandeep Ghatak; Rakshit Ojha; Suresh Kumar Mendem; Devi Murugesan; Claire Raisen; Bibek R. Shome; Mark A. Holmes (Archives of Microbiology, 2022)

Weather-based maize yield forecast in Saudi Arabia using statistical analysis and machine learning - Prabhu Jayagopal; Venkatesan Muthukumaran; Manjula Sanjay Koti; Sampath Satheesh Kumar; Sukumar Rajendran; Sandeep Kumar Mathivanan (Acta Geophysica, 2022)

Characterization and ecotoxicological risk assessment of sewage sludge from industrial and non-industrial cities - Parul Sundha; Nirmalendu Basak; Arvind Kumar Rai; Priyanka Chandra; Sandeep Bedwal; Gajender Yadav; Rajender Kumar Yadav; Parbodh Chander Sharma (Environmental Science and Pollution Research, 2022)

Carbon Sequestration Potential of Agroforestry Systems and Its Potential in Climate Change Mitigation - Bhoomika Ghale; Esha Mitra; Harsimran Singh Sodhi; Amit Kumar Verma; Sandeep Kumar (Water, Air, & Soil Pollution, 2022)

Transcriptional profile of cumulus associated GJA1, PTX3, PRSS35, and SERPINE2 genes with oocytes and embryonic development in water buffalo - Lalit Mohan Jeena; Dharmendra Kumar; Sandeep Rahangdale; Ajit Pratap Singh; Bikash Chandra Sarkhel (Molecular Biology Reports, 2022)

Modified DLLME–GC-TQMS determination of pesticide residues in Gomti River, Lucknow, India: ecological risk assessment and multivariate statistical approach - Neha Gupta; Ravindra Singh Thakur; Sandeep Kumar; Gubbala Naga Venkata Satyanarayana; Priyanka Yadav; Swati Tripathi; Nasreen Ghazi Ansari; Devendra Kumar Patel (Environmental Science and Pollution Research, 2022)

Assessing the environmental impact of air pollution on crops by monitoring air pollution tolerance index (APTI) and anticipated performance index (API) - Lal Chand Malav; Sandeep Kumar; Sadikul Islam; Priya Chaudhary; Shakeel A. Khan (Environmental Science and Pollution Research, 2022)

Micro (mi) RNA and Diabetic Retinopathy - Sadashiv; Praveen Sharma; Shailendra Dwivedi; Sunita Tiwari; Pankaj Kumar Singh; Amit Pal; Sandeep Kumar (Indian Journal of Clinical Biochemistry, 2022)

Status of Vitamin D Receptor Gene Polymorphism and 25-Hydroxy Vitamin D Deficiency with Essential Hypertension - M. Prasad; D. Rajarajeswari; P. Aruna; K. Ramalingam; R. Viswakumar; Nusrath Fathima; Sandeep Kumar Vishwakarma; Aleem Ahmed Khan (Indian Journal of Clinical Biochemistry, 2022)

Identification of sources of resistance to an Indian isolate causing Gummy stem blight in watermelon - Sourav Mahapatra; Eguru Sreeenivasa Rao; Sandeep Kumar GM; Subbaraman Sriram; Budhavaram Varalakshmi; Dhoranalapalli Chinnappareddy Lakshmana Reddy (Australasian Plant Pathology, 2022)

First report on co-isolation and whole-genomic characterisation of mammalian orthorubulavirus 5 and mammalian orthoreovirus type 3 from domestic pigs in India - Fateh Singh; Katherukamem Rajukumar; Dhanapal Senthilkumar; Govindarajulu Venkatesh; Deepali Srivastava; Subbiah Kombiah; Sandeep Kumar Jhade; Vijendra Pal Singh (Archives of Virology, 2022)

Phylogeny of Neobursaridium reshapes the systematics of Paramecium (Oligohymenophorea, Ciliophora) - Valentina Serra; Sergei I. Fokin; Leandro Gammuto; Venkatamahesh Nitla; Michele Castelli; Charan Kumar Basuri; Adireddy Satyaveni; Bhagavatula Venkata Sandeep; Letizia Modeo; Giulio Petroni (Zoologica Scripta, 2022)

CO2 gas sensing properties of Na3BiO4-Bi2O3 mixed oxide nanostructures - Sandeep Gupta; Anoop Mampazhasseri Divakaran; Kamlendra Awasthi; Manoj Kumar (Environmental Science and Pollution Research, 2022)

Molecular Insights into Therapeutic Potentials of Hybrid Compounds Targeting Alzheimer’s Disease - Ankit Jana; Arkadyuti Bhattacharjee; Sabya Sachi Das; Avani Srivastava; Akshpita Choudhury; Rahul Bhattacharjee; Swagata De; Asma Perveen; Danish Iqbal; Piyush Kumar Gupta; Saurabh Kumar Jha; Shreesh Ojha; et al. (Molecular Neurobiology, 2022)
Alzheimer’s disease (AD) is one of the most complex progressive neurological disorders involving degeneration of neuronal connections in brain cells leading to cell death. AD is predominantly detected among elder people (> 65 years), mostly diagnosed with the symptoms of memory loss and cognitive dysfunctions. The multifarious pathogenesis of AD comprises the accumulation of pathogenic proteins, decreased neurotransmission, oxidative stress, and neuroinflammation. The conventional therapeutic approaches are limited to symptomatic benefits and are ineffective against disease progression. In recent years, researchers have shown immense interest in the designing and fabrication of various novel therapeutics comprised of naturally isolated hybrid molecules. Hybrid therapeutic compounds are developed from the combination of pharmacophores isolated from bioactive moieties which specifically target and block various AD-associated pathogenic pathways. The method of designing hybrid molecules has numerous advantages over conventional multitarget drug development methods. In comparison to in silico high throughput screening, hybrid molecules generate quicker results and are also less expensive than fragment-based drug development. Designing hybrid-multitargeted therapeutic compounds is thus a prospective approach in developing an effective treatment for AD. Nevertheless, several issues must be addressed, and additional researches should be conducted to develop hybrid therapeutic compounds for clinical usage while keeping other off-target adverse effects in mind. In this review, we have summarized the recent progress on synthesis of hybrid compounds, their molecular mechanism, and therapeutic potential in AD. Using synoptic tables, figures, and schemes, the review presents therapeutic promise and potential for the development of many disease-modifying hybrids into next-generation medicines for AD.

Inferring the factors for origin and diversifications of endemic Himalayan flora using phylogenetic models - Kumar Manish; Maharaj K. Pandit; Sandeep Sen (Modeling Earth Systems and Environment, 2022)

Geochemistry of bentonitized tuff band of outer NW Himalaya, Jammu and Kashmir, India - Som Nath Kundal; Nighat Chowdhary; Sandeep Kumar (Journal of Earth System Science, 2022)

Immunogenic and reactogenic efficacy of Covaxin and Covishield: a comparative review - Swarnali Das; Suvrendu Sankar Kar; Sovan Samanta; Jhimli Banerjee; Biplab Giri; Sandeep Kumar Dash (Immunologic Research, 2022)

Cobalt (III) complex exerts anti-cancer effects on T cell lymphoma through induction of cell cycle arrest and promotion of apoptosis - Praveen Kumar Verma; Rishi Kant Singh; Sandeep Kumar; Alok Shukla; Sanjay Kumar; Mannu Kumar Gond; Manoj Kumar Bharty; Arbind Acharya (DARU Journal of Pharmaceutical Sciences, 2022)

Indices-based assessment of vulnerability to agricultural drought in the tropical semi-arid ecosystem using time-series satellite and meteorological datasets - Karikkathil C. Arun Kumar; Gangalakunta P. Obi Reddy; Palanisamy Masilamani; Pundoor Sandeep (Arabian Journal of Geosciences, 2022)

Experimental and Theoretical Studies of the Pyrazoline Derivative 5-(4-methylphenyl)-3-(5-methylfuran-2-yl)-1-phenyl-4,5-dihydro-1H-Pyrazole and its Application for Selective Detection of Cd2+ ion as Fluorescent Sensor - Promila Sharma; Shikha Bhogal; Asnake Lealam; Sandeep Kumar; Mohamad Yusuf; Ashok Kumar Malik (Journal of Fluorescence, 2022)

Alantolactone modulates the production of quorum sensing mediated virulence factors and biofilm formation in Pseudomonas aeruginosa - V T Anju; Siddhardha Busi; Sandeep Kumar; Kitlangki Suchiang; Ranjith Kumavath; Sampathkumar Ranganathan; Dinakara Rao Ampasala; Madhu Dyavaiah (Biofouling, 2022)

Identifying region specific seasonal crop for leaf borne diseases by utilizing deep learning techniques - Prabhu Jayagopal; Sukumar Rajendran; Sandeep Kumar Mathivanan; Sree Dharinya Sathish Kumar; Kiruba Thangam Raja; Surekha Paneerselvam (Acta Geophysica, 2022)

Global-scale application of the RUSLE model: a comprehensive review - Mithlesh Kumar; Ambika Prasad Sahu; Narayan Sahoo; Sonam Sandeep Dash; Sanjay Kumar Raul; Balram Panigrahi (Hydrological Sciences Journal, 2022)

Exploring the influence of ventilation settings and fan strength on passenger car in-cabin particle number concentration - Sandeep Kumar Chaudhry; Suresh Pandian Elumalai (Air Quality, Atmosphere & Health, 2022)

COI gene‐based mitochondrial DNA variation of horseshoe crab ( Tachypleus gigas ) reveals high genetic variation and occurrence of distinct populations in the Bay of Bengal, India, and its comparison with other populations - Sanatan Tudu; Sandeep Kumar Gupta; Bisnu Prasad Dash (Marine Ecology, 2022)
Horseshoe crab ( Tachypleus gigas ) is an archaic group of marine species which plays a vital role in the saline ecosystem. We attempted to develop a baseline database about the ecology, phylogeography, and genetic variation among the horseshoe crab population from Odisha, India. We collected 152 samples of horseshoe crab from the coastal area of the Bay of Bengal. The generated cytochrome c oxidase subunit I gene ( COI ) sequences of T . gigas were compared with the GenBank sequences of five populations from Bangladesh, Thailand, Singapore, South China, and Malaysia. A total of 33 unique haplotypes were observed in six populations of T . gigas . Pairwise F ‐statistic distance ( F ST ) between South China‐India, Malaysia‐India, Singapore‐India, Thailand‐India, and Bangladesh‐India were 0.021, 0.020, 0.017, 0.015, and 0.008, respectively. It indicated that the Indian and Bangladesh populations were genetically close and distinct from the other four populations. Furthermore, the migrant per generation (Nm) was 0.16, which indicated a low gene flow among T . gigas populations. The haplotype diversity ( H d) and nucleotide diversity ( π ) were 0.7482 and 0.00313, respectively. It signifies the ecological importance of the Indian population that would help in formulating the future strategy for the conservation of horseshoe crab.

Optimization of growing conditions, substrate-types and their concentrations for acclimatization and post-acclimatization growth of in vitro-raised flame lily (Gloriosa superba L.) plantlets - Ashok Kumar Khandel; Saikat Gantait; Sandeep Kumar Verma (Vegetos, 2022)

Plant beneficial effects of Trichoderma spp. suppressing Fusarium wilt and enhancing growth in Tomato - Krishna Kumar; Parika Thakur; Utkarsh Singh Rathore; Sandeep Kumar; R. K. Mishra; N. Amaresan; Sonika Pandey; Monika Mishra (Vegetos, 2022)

Modelling of Moment Tensors and Source Parameters of the 25 July 2021 Rare Lower Crustal Hyderabad (India) Earthquake of Mw 3.9 - Prantik Mandal; Satish Saha; Sudesh Kumar; Sandeep Gupta; Rahul Biswas; Sanjay Kumar; K. Sivaram; B. N. V. Prasad; M. Saidixit; Raju Prathigadapa; Bhoopender Singh; S. Madhusudan (Pure and Applied Geophysics, 2022)

Optimization of an efficient and robust regeneration system for Sorghum bicolor: a vital step towards genetic engineering-based sorghum improvement - Neeraj Kumar; Sandeep Yadav; Smiriti Maithili; Ritika Prasad; Madan Pal; Manoj K. Sharma (Plant Physiology Reports, 2022)

Modelling of 2016 Kumamoto earthquake by integrating site effect in semi-empirical technique - Sonia Devi; Sandeep; Parveen Kumar; Monika; A. Joshi (Natural Hazards, 2022)

Lithosphere thickness variation across the Deccan Volcanic Province–Eastern Dharwar Craton, South India: Insight into evolution of the Deccan Volcanic Province - Sandeep Gupta; Sudesh Kumar (Journal of Earth System Science, 2022)

Regional-scale landslide susceptibility assessment for the hilly state of Uttarakhand, NW Himalaya, India - Vikram Gupta; Sandeep Kumar; Ramandeep Kaur; Ruchika S Tandon (Journal of Earth System Science, 2022)

Eco-friendly management of seed discolouration of paddy - Praveen S. Patted; Atul Kumar; Sandeep Kumar Lal; Shyamal K. Chakrabarty; Bishnu Maya Bashyal; Ranjit Ranjan Kumar; Prolay Kumar Bhaumick; Shaily Javeria (Indian Phytopathology, 2022)

Development of multiple disease resistant tomato lines through marker assisted breeding and their evaluation for horticultural traits - Ashish Kumar; S. K. Jindal; M. S. Dhaliwal; Abhishek Sharma; Sukhjeet Kaur; Sandeep Jain (Indian Phytopathology, 2022)

RETRACTED ARTICLE: An update on pathophysiology and treatment of sports-mediated brain injury - Sunishtha Kalra; Rittu Banderwal; Kaushal Arora; Sandeep Kumar; Govind Singh; Pooja A. Chawla; Tapan Behl; Aayush Sehgal; Sukhbir Singh; Saurabh Bhatia; Ahmed Al-Harrasi; Lotfi Aleya; et al. (Environmental Science and Pollution Research, 2022)

Multi-decadal groundwater variability analysis using geostatistical method for groundwater sustainability - Zubairul Islam; Muthukumarasamy Ranganathan; Murugesan Bagyaraj; Sudhir Kumar Singh; Sandeep Kumar Gautam (Environment, Development and Sustainability, 2022)

Rapid determination and optimisation of berberine from Himalayan Berberis lycium by soxhlet apparatus using CCD-RSM and its quality control as a potential candidate for COVID-19 - Anil Kumar Katare; Bikarma Singh; Pooja Shukla; Sandeep Gupta; Bishander Singh; Kavya Yalamanchili; Nitin Kulshrestha; Rajendra Bhanwaria; Ashok Kumar Sharma; Sarita Sharma; Sneha; Durga Prasad Mindala; et al. (Natural Product Research, 2022)

Strong Motion Modelling of the 1999 Izmit Earthquake Using Site Effect in a Semi-Empirical Technique: A More Realistic Approach - Sandeep; Sonia Devi; Parveen Kumar; Monika; Rohtash Kumar (Pure and Applied Geophysics, 2022)

In vitro mature embryo culture protocol of einkorn (Triticum monococcum ssp. monococcum) and bread (Triticum aestivum L.) wheat under boron stress - Ferdi Ağıl; Mehmet Örgeç; Fatma Pehlivan Karakaş; Sandeep Kumar Verma; Nusret Zencirci (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Determinants of high-density lipoprotein (HDL) functions beyond proteome in Asian Indians: exploring the fatty acid profile of HDL phospholipids - Himani Thakkar; Vinnyfred Vincent; Ambuj Roy; Ajay Kumar Gautam; Rintu Kutum; Lakshmy Ramakrishnan; Sandeep Singh; Archna Singh (Molecular and Cellular Biochemistry, 2022)

Arsenic Resistance Mechanisms in Pseudomonas mendocina SMSKVR-3 Strain Isolated from Khetri Copper Mines, Rajasthan, India - Shraddha Mishra; Sandeep Kumar; Sanjay Kumar Verma (Current Microbiology, 2022)

Late Pliocene–Early Pleistocene ichnofauna from bentonitized tuff band and associated mudstone horizons, Jammu and Kashmir, India, and their palaeoenvironmental implications - Som Nath Kundal; Pardeep Kundal; Sandeep Kumar; Nighat Chowdhary; Guntupalli Veera Raghavendra Prasad (Arabian Journal of Geosciences, 2022)

Agro-morphological variability and genetic diversity in linseed (Linum usitatissimum L.) germplasm accessions with emphasis on flowering and maturity time - Ankit Saroha; Deepa Pal; Vikender Kaur; Sandeep Kumar; Arti Bartwal; J. Aravind; J. Radhamani; S. Rajkumar; Rajesh Kumar; Sunil S. Gomashe; Abhishek Sengupta; Dhammaprakash Pandhari Wankhede (Genetic Resources and Crop Evolution, 2022)

Amelioration of oxidative stress by trans-Anethole via modulating phase I and phase II enzymes against hepatic damage induced by CCl4 in male Wistar rats - Kritika Pandit; Ajay Kumar; Sandeep Kaur; Vinod Kumar; Subheet Kumar Jain; Renu Bhardwaj; Satwinderjeet Kaur (Environmental Science and Pollution Research, 2022)

Impact of elevated CO2 and phosphorus nutrition on mineral composition and cooking quality of rice - Doddagatta Hanumanthappa Raviteja; Tarun Kumar; Sandeep Sharma; Arun Kumar; Madan Pal Singh; Renu Pandey (Plant Physiology Reports, 2021)

Evaluation of spatial probability of landslides using bivariate and multivariate approaches in the Goriganga valley, Kumaun Himalaya, India - Sandeep Kumar; Vikram Gupta (Natural Hazards, 2021)

Energy efficient IoT-based cloud framework for early flood prediction - Mandeep Kaur; Pankaj Deep Kaur; Sandeep Kumar Sood (Natural Hazards, 2021)

Characterization of shear wave attenuation and site effects in the Garhwal Himalaya, India from inversion of strong motion records - Parveen Kumar; Monika; Sandeep; Sushil Kumar; Richa Kumari; Dinesh Kumar; Narendra Kumar (Journal of Earth System Science, 2021)

Radiopharmaceuticals: An insight into the latest advances in medical uses and regulatory perspectives - Deepak Kaushik; Pooja Jangra; Ravinder Verma; Deepika Purohit; Parijat Pandey; Sandeep Sharma; Rakesh Kumar Sharma (Journal of Biosciences, 2021)

Radiological risk assessment to the public due to the presence of radon in water of Barnala district, Punjab, India - Supriya Rani; Sandeep Kansal; Amit Kumar Singla; Rohit Mehra (Environmental Geochemistry and Health, 2021)

A comparative analysis of different pixel and object-based classification algorithms using multi-source high spatial resolution satellite data for LULC mapping - Akanksha Balha; Javed Mallick; Suneel Pandey; Sandeep Gupta; Chander Kumar Singh (Earth Science Informatics, 2021)

Detection of novel sequence types and zoonotic transmission potentiality among strains of Shiga toxigenic Escherichia coli (STEC) from dairy calves, animal handlers and associated environments - Madesh Angappan; Sandeep Ghatak; Arockiasamy Arun Prince Milton; Asha Kumari Verma; Sophia Inbaraj; Abhishek; Pallab Chaudhuri; Rajesh Kumar Agarwal; Prasad Thomas (Brazilian Journal of Microbiology, 2021)

Crop Health Assessment Using Sentinel-1 SAR Time Series Data in a Part of Central India - Sandeep Kumar Kaushik; Varun Narayan Mishra; Milap Punia; Pranaya Diwate; Thota Sivasankar; Anil Kumar Soni (Remote Sensing in Earth Systems Sciences, 2021)

Evaluation of Productivity, Quality and Economics of Turmeric Under Different Moisture Regime and Integrated Nutrient Management at Eastern Indo-Gangetic Plains, India - Sandeep Kumar Tripathi; Babloo Sharma; Pratibha Kumari; Proloy Deb; Ratneswar Ray; Anjelo Francis Denis (Agricultural Research, 2021)

Influence of Tillage and Relay Cropping of Berseem in Mustard–Pearl millet System on Soil Quality, Productivity of Crops and Water - Y. P. Singh; Sandeep S. Tomar; Sudhir Singh; Anil Kumar Singh; Raj K. Gupta (Agricultural Research, 2021)

Temporal trends in frost occurrence and their prediction models using multivariate statistical techniques for two diverse locations of Northern India - Santanu Kumar Bal; Rajkumar Dhakar; P. Vijaya Kumar; Adita Mishra; V. P. Pramod; M. A. Sarath Chandran; V. M. Sandeep; A. V. M. Subba Rao; K. K. Gill; Rajendra Prasad (Theoretical and Applied Climatology, 2021)

Implications of Site Effects and Attenuation Properties for Estimation of Earthquake Source Characteristics in Kinnaur Himalaya, India - Richa Kumari; Parveen Kumar; Naresh Kumar; Sandeep (Pure and Applied Geophysics, 2021)

RETRACTED ARTICLE: Role of TLR2 and TLR4 Signaling in Parkinson’s Disease: An Insight into Associated Therapeutic Potential - Gagandeep Kaur; Tapan Behl; Aayush Sehgal; Sukhbir Singh; Neelam Sharma; Arun Kumar; Sandeep Arora; Simona Bungau (Journal of Molecular Neuroscience, 2021)

Evidence of Coronavirus (CoV) Pathogenesis and Emerging Pathogen SARS-CoV-2 in the Nervous System: A Review on Neurological Impairments and Manifestations - Niraj Kumar Jha; Shreesh Ojha; Saurabh Kumar Jha; Harish Dureja; Sachin Kumar Singh; Shakti D. Shukla; Dinesh Kumar Chellappan; Gaurav Gupta; Shanu Bhardwaj; Neeraj Kumar; Madhan Jeyaraman; Rashmi Jain; et al. (Journal of Molecular Neuroscience, 2021)

Synergistic effect of pistachio shell powder and nano-zerovalent copper for chromium remediation from aqueous solution - Sandeep Kumar; Ravinderdeep Singh Brar; J. Nagendra Babu; Amarjeet Dahiya; Sandip Saha; Avneesh Kumar (Environmental Science and Pollution Research, 2021)

Comparative analysis of forest canopy mapping methods for the Sundarban biosphere reserve, West Bengal, India - Ismail Mondal; Sandeep Thakur; Mukhiddin Juliev; Tarun Kumar De (Environment, Development and Sustainability, 2021)

Age-dependent effect of continuous ‘artificial light at night’ on circadian rhythm in male rats: neuroprotective role of melatonin - Avnish Kumar Verma; Sandeep Singh; Syed Ibrahim Rizvi (Biogerontology, 2021)

Amino and fatty acids contributing to antibiosis against Chilo partellus (Swinhoe) in maize - Yogesh Yele; Mukesh K. Dhillon; Aditya K. Tanwar; Sandeep Kumar (Arthropod-Plant Interactions, 2021)

Demonstration of the Temporal Evolution of Tropical Cyclone “Phailin” Using Gray-Zone Simulations and Decadal Variability of Cyclones over the Bay of Bengal in a Warming Climate - Prabodha Kumar Pradhan; Vinay Kumar; Sunilkumar Khadgarai; S. Vijaya Bhaskara Rao; Tushar Sinha; Vijaya Kumari Kattamanchi; Sandeep Pattnaik (Oceans, 2021)
The intensity and frequency variability of cyclones in the North Indian Ocean (NIO) have been amplified over the last few decades. The number of very severe cyclonic storms (VSCSs) over the North Indian Ocean has increased over recent decades. “Phailin”, an extreme severe cyclonic storm (ESCS), occurred during 8–13 October 2013 over the Bay of Bengal and made landfall near the Gopalpur coast of Odisha at 12 UTC on 12 October. It caused severe damage here, as well as in the coastal Odisha, Andhra Pradesh, and adjoining regions due to strong wind gusts (~115 knot/h), heavy precipitation, and devastating storm surges. The fidelity of the WRF model in simulating the track and intensity of tropical cyclones depends on different cloud microphysical parameterization schemes. Thus, four sensitivity simulations were conducted for Phailin using double-moment and single-moment microphysical (MP) parameterization schemes. The experiments were conducted to quantify and characterize the performance of such MP schemes for Phailin. The simulations were performed by the advanced weather research and forecasting (WRF-ARW) model. The model has two interactive domains covering the entire Bay of Bengal and adjoining coastal Odisha on 25 km and 8.333 km resolutions. Milbrandt–Yau (MY) double-moment and WRF single-moment microphysical schemes, with 6, 5, and 3 classes of hydrometeors, i.e., WSM6, WSM5, and WSM3, were used for the simulation. Experiments for Phailin were conducted for 126 h, starting from 00 UTC 08 October to 06 UTC 13 October 2013. It was found that the track, intensity, and structure of Phailin are highly sensitive to the different microphysical parameterization schemes. Further, the precipitation and cloud distribution were studied during the ESCS stage of Phailin. The microphysics schemes (MY, WSM3, WSM5, WSM6), along with Grell–Devenyi ensemble convection scheme predicted landfall of Phailin over the Odisha coast with significant track errors. Supply of moisture remains a more crucial component than SST and wind shear for rapid intensification of the Phailin 12 h before landfall over the Bay of Bengal. Finally, the comparison of cyclone formation between two decades 2001–2010 and 2011–2020 over the Bay of Bengal inferred that the increased numbers of VSCS are attributed to the supply of abundant moisture at low levels in the recent decade 2011–2020.

Comparison of Carbon Sequestration Potential of Quercus leucotrichophora–Based Agroforestry Systems and Natural Forest in Central Himalaya, India - Sandeep Kumar; Arvind Bijalwan; Bhupendra Singh; Deepa Rawat; Aalok G. Yewale; Manoj Kumar Riyal; Tarun Kumar Thakur (Water, Air, & Soil Pollution, 2021)

Cross tolerance to phosphorus deficiency and drought stress in mungbean is regulated by improved antioxidant capacity, biological N2-fixation, and differential transcript accumulation - Surendra Kumar Meena; Renu Pandey; Sandeep Sharma; Gayacharan; Krishnapriya Vengavasi; Harsh Kumar Dikshit; Kadambot H. M. Siddique; Madan Pal Singh (Plant and Soil, 2021)

Strong-Motion Simulation of the 1988 Indo-Burma and Scenario Earthquakes in NE India by Integrating Site Effects in a Semi-Empirical Technique - Sonia Devi; Sandeep; Parveen Kumar; Monika (Pure and Applied Geophysics, 2021)

Artificial intelligence as a fundamental tool in management of infectious diseases and its current implementation in COVID-19 pandemic - Ishnoor Kaur; Tapan Behl; Lotfi Aleya; Habibur Rahman; Arun Kumar; Sandeep Arora; Israt Jahan Bulbul (Environmental Science and Pollution Research, 2021)

Effect of the medicinal plant Withania somnifera on the development of a medico-veterinary pest Chrysomya megacephala (Diptera: Calliphoridae) - Sandeep Kumar Gaur; Krishna Kumar (Invertebrate Reproduction & Development, 2021)

Putative role of natural products as Protein Kinase C modulator in different disease conditions - Rishi Kant Singh; Sanjay Kumar; Munendra Singh Tomar; Praveen Kumar Verma; Amit Kumar; Sandeep Kumar; Naveen Kumar; Jai Prakash Singh; Arbind Acharya (DARU Journal of Pharmaceutical Sciences, 2021)

Coseismic landslide hazard assessment for the future scenario earthquakes in the Kumaun Himalaya, India - Sandeep Kumar; Vikram Gupta; Parveen Kumar; Y. P. Sundriyal (Bulletin of Engineering Geology and the Environment, 2021)

Spatial modelling for identification of groundwater potential zones in semi-arid ecosystem of southern India using Sentinel-2 data, GIS and bivariate statistical models - Karikkathil C. Arun Kumar; Gangalakunta P. Obi Reddy; Palanisamy Masilamani; Pundoor Sandeep (Arabian Journal of Geosciences, 2021)

Intrinsic Vulnerability Evaluation of Groundwater Nitrate Pollution Along a Course of the Subarnarekha River in Jharkhand, India - Sandeep Kumar Gautam; Sudhir Kumar Singh; Kishan Singh Rawat (Water Conservation Science and Engineering, 2021)

An elaborative NMR based plasma metabolomics study revealed metabolic derangements in patients with mild cognitive impairment: a study on north Indian population - Umesh Kumar; Abhai Kumar; Smita Singh; Payal Arya; Sandeep Kumar Singh; Rameshwar Nath Chaurasia; Anup Singh; Dinesh Kumar (Metabolic Brain Disease, 2021)

Epigenetic Regulation of Gut Microbial Dysbiosis - Shivani Srivastava; Archana Singh; Kumar Sandeep; Durgavati Yadav (Indian Journal of Microbiology, 2021)

Biotite as a geoindicator of rare earth element contamination in Gomati River Basin, Ganga Alluvial Plain, northern India - Priyanka Singh; Jitendra Kumar Yadav; Dharmendra Kumar Jigyasu; Sandeep Singh; Narendra Kumar; Indra Bir Singh; Munendra Singh (Environmental Monitoring and Assessment, 2021)

The therapeutic potential and the health benefits of Morus indica Linn.: a mini review - Hankhray Boro; Sandeep Das; Sushil Kumar Middha (Advances in Traditional Medicine, 2021)

Nitrogen fixation in maize: breeding opportunities - Seema Sheoran; Sandeep Kumar; Pradeep Kumar; Ram Swaroop Meena; Sujay Rakshit (Theoretical and Applied Genetics, 2021)

Detection of 40 bp tandem repeat motif and associated insertions and deletions (INDEL) in the mitochondrial DNA control region of Sambar deer (Rusa unicolor) - Mirza Ghazanfarullah Ghazi; Syed Ainul Hussain; Sandeep Kumar Gupta (Molecular Biology Reports, 2021)

A novel lincRNA identified in buffalo oocytes with protein binding characteristics could hold the key for oocyte competence - Sunny Dholpuria; Sandeep Kumar; Manish Kumar; Parul Sarwalia; Rakesh Kumar; Tirtha Kumar Datta (Molecular Biology Reports, 2021)

Designing of a nanoscale zerovalent iron@fly ash composite as efficient and sustainable adsorbents for hexavalent chromium (Cr(VI)) from water - Shubhangi Madan; Urvashi Thapa; Sangeeta Tiwari; Sandeep Kumar Tiwari; Suresh Kumar Jakka; Manuel Jorge Soares (Environmental Science and Pollution Research, 2021)

Effect of Elevated Temperatures on Sugarcane Bagasse Ash-Based Alkali-Activated Slag Concrete - D. S. Sandeep Kumar; K. Chethan; B. Chethan Kumar (Sugar Tech, 2021)

A scientometric analysis of ICT-assisted disaster management - Sandeep Kumar Sood; Keshav Singh Rawat (Natural Hazards, 2021)

Piperlongumine targets NF-κB and its downstream signaling pathways to suppress tumor growth and metastatic potential in experimental colon cancer - Sandeep Kumar; Navneet Agnihotri (Molecular and Cellular Biochemistry, 2021)

Modeling and Assessment of Land Degradation Vulnerability in Semi-arid Ecosystem of Southern India Using Temporal Satellite Data, AHP and GIS - P. Sandeep; G. P. Obi Reddy; R. Jegankumar; K. C. Arun Kumar (Environmental Modeling & Assessment, 2021)

Efficacy and Safety of New and Emerging Drugs for COVID-19: Favipiravir and Dexamethasone - Shivani Sood; Gurpreet Kaur Bhatia; Prachi Seth; Pawan Kumar; Jagjit Kaur; Vidisha Gupta; Sandeep Punia; Hardeep Singh Tuli (Current Pharmacology Reports, 2021)

Response of diverse bread wheat genotypes in terms of root architectural traits at seedling stage in response to low phosphorus stress - Preman R. Soumya; Sandeep Sharma; Mukesh Kumar Meena; Renu Pandey (Plant Physiology Reports, 2021)

Elucidation of underlying molecular mechanism of 5-Fluorouracil chemoresistance and its restoration using fish oil in experimental colon carcinoma - Isha Rani; Sandeep Kumar; Bhoomika Sharma; Rajendra Prasad; Satinder Kaur; Prerna Sharma; Navneet Agnihotri (Molecular and Cellular Biochemistry, 2021)

An Adaptive Technique to Detect and Remove Shadow from Drone Data - Ankush Agarwal; Sandeep Kumar; Dharmendra Singh (Journal of the Indian Society of Remote Sensing, 2021)

Onosma bracteata Wall. induces G0/G1 arrest and apoptosis in MG-63 human osteosarcoma cells via ROS generation and AKT/GSK3β/cyclin E pathway - Ajay Kumar; Sandeep Kaur; Kritika Pandit; Varinder Kaur; Sharad Thakur; Satwinderjeet Kaur (Environmental Science and Pollution Research, 2021)

Exploration of Anti-plasmodial Activity of Prunus cerasoides Buch.-Ham. ex D. Don (family: Rosaceae) and Its Wood Chromatographic Fractions - Cheryl Sachdeva; Sandeep Kumar; Naveen K. Kaushik (Acta Parasitologica, 2021)

Phylogeny of Neobursaridium reshapes the systematics of Paramecium (Oligohymenophorea, Ciliophora) - Valentina Serra; Sergei I. Fokin; Leandro Gammuto; Venkatamahesh Nitla; Michele Castelli; Charan Kumar Basuri; Adireddy Satyaveni; Bhagavatula Venkata Sandeep; Letizia Modeo; Giulio Petroni (Zoologica Scripta, 2021)
The subclass Peniculia (Oligohymenophorea, Intramacronucleata) is one of the most known groups of the phylum Ciliophora, being composed by very notorious representatives, such as Paramecium and Frontonia . Nevertheless, phylogenetic relationships among genera within this subclass are still far from being resolved. Moreover, for several members of the group the characterization by molecular markers is still lacking, such as for Wenrichia, Clathrostoma, Paraclathrostoma, Didieria and, to date, also for Neobursaridium . The finding of one strain of Neobursaridium gigas from India led to the first molecular characterization of this uncommonly sampled ciliate. The 18S rDNA sequence and the COI sequence were obtained and used for phylogenetic analyses. Moreover, the partial mitochondrial genome of N. gigas was sequenced, annotated and employed for phylogenomics analysis. To increase the sampling effort for the Paramecium clade, several newly obtained 18S rDNA sequences of parameciids are herein presented. Unexpectedly, the inclusion of N. gigas's molecular data in phylogenetics/phylogenomics analyses did not help to solve the complex evolution relationships inside Peniculia. Conversely, it raised new and intriguing questions about Paramecium phylogeny, since N. gigas clustered inside Paramecium clade as sister species of Paramecium bursaria in all the performed analyses. A critical revision of past and present data led to rename N. gigas as Paramecium gigas (Balech, 1941) comb. nov., and triggered the revision of genus Paramecium , with the proposal of the new subgenus Gigaparamecium subgen. nov. Hypotheses on the evolution of giant morphologies in ciliates are also discussed.

Students exposure assessment towards PM number concentration while commuting from different transport modes during school timings - Sandeep Kumar Chaudhry; Suresh Pandian Elumalai (Stochastic Environmental Research and Risk Assessment, 2021)

Role of metallic pollutants in neurodegeneration: effects of aluminum, lead, mercury, and arsenic in mediating brain impairment events and autism spectrum disorder - Ishnoor Kaur; Tapan Behl; Lotfi Aleya; Md. Habibur Rahman; Arun Kumar; Sandeep Arora; Rokeya Akter (Environmental Science and Pollution Research, 2021)

Mitigation of indoor air pollutants using Areca palm potted plants in real-life settings - Bhavya Bhargava; Sandeep Malhotra; Anjali Chandel; Anjali Rakwal; Rachit Raghav Kashwap; Sanjay Kumar (Environmental Science and Pollution Research, 2021)

Modulation of mutagenicity in Salmonella typhimurium and antioxidant properties and antiproliferative effects of fractions from Cassia fistula L. on human cervical HeLa and breast MCF-7 cancer cells - Sandeep Kaur; Ajay Kumar; Kritika Pandit; Satwinderjeet Kaur (Environmental Science and Pollution Research, 2021)

Assessment of changes in land use, land cover, and land surface temperature in the mangrove forest of Sundarbans, northeast coast of India - Sandeep Thakur; Debapriya Maity; Ismail Mondal; Ganesh Basumatary; Phani Bhushan Ghosh; Papita Das; Tarun Kumar De (Environment, Development and Sustainability, 2021)

Delivery of siRNA to Endothelial Cells In Vivo Using Lysine/Histidine Oligopeptide-Modified Poly(β-amino ester) Nanoparticles - Pere Dosta; Catherine Demos; Victor Ramos; Dong Won Kang; Sandeep Kumar; Hanjoong Jo; Salvador Borrós (Cardiovascular Engineering and Technology, 2021)

Protein aggregation: in silico algorithms and applications - R. Prabakaran; Puneet Rawat; A. Mary Thangakani; Sandeep Kumar; M. Michael Gromiha (Biophysical Reviews, 2021)

In vitro tissue culture protocol of ancient einkorn (Triticum monococcum ssp. monococum) wheat via indirect shoot regeneration - Mehmet Örgeç; Sandeep Kumar Verma; Günce Şahin; Nusret Zencirci; Ekrem Gürel (In Vitro Cellular & Developmental Biology - Plant, 2021)

Spermidine, a caloric restriction mimetic, provides neuroprotection against normal and d-galactose-induced oxidative stress and apoptosis through activation of autophagy in male rats during aging - Sandeep Singh; Raushan Kumar; Geetika Garg; Abhishek Kumar Singh; Avnish Kumar Verma; Akalabya Bissoyi; Syed Ibrahim Rizvi (Biogerontology, 2021)

Complete mitogenome of Ganges river dolphin, Platanista gangetica gangetica and its phylogenetic relationship with other cetaceans - Ajit Kumar; Prabhaker Yadav; Aftab Usmani; Syed Ainul Hussian; Sandeep Kumar Gupta (Molecular Biology Reports, 2021)

A Review of IRS-1C Applications in Urban and Regional Studies, and Infrastructure Planning - Pramod Kumar; K. Venugopala Rao; Sudha Ravindranath; Sandeep Maithani; Asfa Siddiqui; B. D. Bharath; S. V. L. Bhavani (Journal of the Indian Society of Remote Sensing, 2021)

Analysis of Multimerin 1 (MMRN1) expression in ovarian cancer - Abhinav Saini; Kumari Binita Chandra; Vikrant Kumar; Sandeep R Mathur; J B Sharma; Sunesh Kumar; Savita Yadav (Molecular Biology Reports, 2020)

Complete mitogenome of Kashmir musk deer (Moschus cupreus) and its comparative phylogenetic relationships - Bhim Singh; Kumudani Bala Gautam; Subhashree Sahoo; Ajit Kumar; Sandeep Kumar Gupta (Molecular Biology Reports, 2020)

Role of site effect for the evaluation of attenuation characteristics of P, S and coda waves in Kinnaur region, NW Himalaya - Richa Kumari; Parveen Kumar; Naresh Kumar; Sandeep (Journal of Earth System Science, 2020)

Hydro-meteorological hazards and role of ICT during 2010-2019: A scientometric analysis - Mandeep Kaur; Sandeep Kumar Sood (Earth Science Informatics, 2020)

Therapeutic application of Carica papaya leaf extract in the management of human diseases - Surya P. Singh; Sanjay Kumar; Sivapar V. Mathan; Munendra Singh Tomar; Rishi Kant Singh; Praveen Kumar Verma; Amit Kumar; Sandeep Kumar; Rana P. Singh; Arbind Acharya (DARU Journal of Pharmaceutical Sciences, 2020)

Rapid Green Synthesis of Biogenic Silver Nanoparticles Using Cinnamomum tamala Leaf Extract and its Potential Antimicrobial Application Against Clinically Isolated Multidrug-Resistant Bacterial Strains - Shib Shankar Dash; Sovan Samanta; Sananda Dey; Biplab Giri; Sandeep Kumar Dash (Biological Trace Element Research, 2020)

Molecular and ecological perspectives of nitrous oxide producing microbial communities in agro-ecosystems - Amit Kumar; Kristina Medhi; Ram Kishor Fagodiya; Gangavarapu Subrahmanyam; Raju Mondal; Pushpanathan Raja; Sandeep Kumar Malyan; Dipak Kumar Gupta; Chandan Kumar Gupta; Himanshu Pathak (Reviews in Environmental Science and Bio/Technology, 2020)

Molecular and morphometric divergence of four species of butterflies (Nymphalidae and Pieridae) from the Western Himalaya, India - Vinaya Kumar Singh; Prakash Chandra Joshi; Sandeep Kumar Gupta (Molecular Biology Reports, 2020)

Morpho-genetic divergence and population structure in Indian Santalum album L. - Chandrashekar Sandeep; Amit Kumar; Vereena Rodrigues; Syam Viswanath; Ashutosh K. Shukla; Velusamy Sundaresan (Trees, 2020)

Hydrogeomorphic assessment of badlands in part of the Mandakini River watershed, Chitrakoot, India - Nikhilesh Singh; Sandeep Kumar Maddheshiya; Medha Jha; Sanjay Tignath; Bhola Nath Singh (Arabian Journal of Geosciences, 2020)

Whey protein concentrate protects against age-dependent alteration in redox biomarkers - Geetika Garg; Abhishek Kumar Singh; Sandeep Singh; Avnish Kumar Verma; Syed Ibrahim Rizvi (Biologia Futura, 2020)

Spatial variability studies of attenuation characteristics of Qα and Qβ in Kumaon and Garhwal region of NW Himalaya - Monika; Parveen Kumar; Sandeep; Sushil Kumar; A. Joshi; Sonia Devi (Natural Hazards, 2020)

Spatio-temporal modelling of shoreline migration in Sagar Island, West Bengal, India - Ismail Mondal; Sandeep Thakur; Mukhiddin Juliev; Jatisankar Bandyopadhyay; Tarun Kumar De (Journal of Coastal Conservation, 2020)

Multifaceted genome-wide study identifies novel regulatory loci in SLC22A11 and ZNF45 for body mass index in Indians - Anil K. Giri; Gauri Prasad; Khushdeep Bandesh; Vaisak Parekatt; Anubha Mahajan; Priyanka Banerjee; Yasmeen Kauser; Shraddha Chakraborty; Donaka Rajashekar; Abhay Sharma; Sandeep Kumar Mathur; Analabha Basu; et al. (Molecular Genetics and Genomics, 2020)

Glutathione Modified Fluorescent CdS QDs Synthesized Using Environmentally Benign Pathway for Detection of Mercury Ions in Aqueous Phase - Jaspreet Kaur; Komal; Renu; Vinod Kumar; K. B. Tikoo; Sandeep Bansal; Anupama Kaushik; Sonal Singhal (Journal of Fluorescence, 2020)

Strong ground motion simulation techniques—a review in world context - Sandeep Arora; A. Joshi; Pushpa Kumari; Parveen Kumar; Shashi Kant Sah; Sohan Lal; Nagendra Pratap Singh (Arabian Journal of Geosciences, 2020)

Spatial regionalisation of morphometric characteristics of mini watershed of Northern Foreland of Peninsular India - Sandeep Kumar Yadav; Alok Dubey; Sudhir Kumar Singh; Diwakar Yadav (Arabian Journal of Geosciences, 2020)

Development of polymorphic EST-SSR markers and their applicability in genetic diversity evaluation in Rhododendron arboreum - Himanshu Sharma; Pankaj Kumar; Abhishek Singh; Kanika Aggarwal; Joy Roy; Vikas Sharma; Sandeep Rawat (Molecular Biology Reports, 2020)

Spatial and seasonal distribution of multi-elements in suspended particulate matter (SPM) in tidally dominated Hooghly river estuary and their ecotoxicological relevance - Soumita Mitra; Mathummal Sudarshan; M.P. Jonathan; Santosh Kumar Sarkar; Sandeep Thakur (Environmental Science and Pollution Research, 2020)

Transcriptional Regulation of Zinc Transporters in Human Osteogenic Sarcoma (Saos-2) Cells to Zinc Supplementation and Zinc Depletion - Kiran Alluri; Krishna Pillay Madhavan Nair; Sandeep Kumar Kotturu; Sudip Ghosh (Biological Trace Element Research, 2020)

Application of Fracture Induced Electromagnetic Radiation (FEMR) technique to detect landslide-prone slip planes - Shreeja Das; Jyotirmoy Mallik; Sandeep Dhankhar; Neeraj Suthar; Amit K. Singh; Vikramjit Dutta; Uttam Gupta; Gopal Kumar; Riya Singh (Natural Hazards, 2020)

Chitin and chitosan-based support materials for enzyme immobilization and biotechnological applications - Madan L. Verma; Sandeep Kumar; Anamika Das; Jatinder S. Randhawa; Munusamy Chamundeeswari (Environmental Chemistry Letters, 2020)

Water 222Rn for evaluating the variation in groundwater inflows to discharge of the Big Sioux River in different flow periods - Ram P. Neupane; Sandeep Kumar (Sustainable Water Resources Management, 2020)

Effect of different elemental chlorine-free bleaching sequences on pulp, effluent properties and their impact on index of global pollution - Sandeep Kumar Tripathi; Nishi Kant Bhardwaj; Himadri Roy Ghatak (Environmental Science and Pollution Research, 2020)

Strength Characteristics and Stability Analysis of Ground Granulated Blast Furnace Slag (GGBFS) Stabilized Coal Mine Overburden-Pond Ash Mix - Tarun Kumar Rajak; Laxmikant Yadu; Sandeep Kumar Chouksey (Geotechnical and Geological Engineering, 2020)

Acetogenins as potential checkpoint-2 kinase inhibitors: an in silico analysis - P. Meghana; Jain R. Sandeep Kumar; Telkar Sandeep; N. Prashanth; H. M. Kumaraswamy (Journal of Proteins and Proteomics, 2019)

Strong motion generation area modelling of the 2008 Iwate earthquake, Japan using modified semi-empirical technique - Sandeep; A Joshi; Sonia Devi; Parveen Kumar; S K Sah; Sohan Lal; Kamal (Journal of Earth System Science, 2019)

Behavior of vertical and batter piles under lateral, uplift and combined loads in non-cohesive soil - Pankaj Bajaj; Laxmikant Yadu; Sandeep Kumar Chouksey (Innovative Infrastructure Solutions, 2019)

Application of potassium-solubilising Proteus mirabilis MG738216 inhabiting cattle dung in improving nutrient use efficiency of Foeniculum vulgare Mill. - Sandhya Dhiman; Ramesh Chand Dubey; Nitin Baliyan; Sandeep Kumar; Dinesh Kumar Maheshwari (Environmental Sustainability, 2019)

Improved production of lipid contents by cultivating Chlorella pyrenoidosa in heterogeneous organic substrates - Hesam Kamyab; Shreeshivadasan Chelliapan; Chew Tin Lee; Tayebeh Khademi; Ashok Kumar; Krishna Kumar Yadav; Shahabaldin Rezania; Sandeep Kumar; Shirin Shafiei Ebrahimi (Clean Technologies and Environmental Policy, 2019)

Correction to: Late Holocene palaeovegetational and environmental changes inferred from organic geochemical proxies in sediments from Pookot Lake, southern India - Sandeep Kizhur; Rajasekhariah Shankar; Anish Kumar Warrier; Madhusudan G. Yadava; Rengaswamy Ramesh; Rashmikant A. Jani (Arabian Journal of Geosciences, 2019)

Modeling of 2011 IndoNepal Earthquake and Scenario Earthquakes in the Kumaon Region and Comparative Attenuation Study Using PGA Distribution with the Garhwal Region - Sandeep; A. Joshi; S. K. Sah; Parveen Kumar; Sohan Lal; Sonia Devi; Monika (Pure and Applied Geophysics, 2019)

Charting oat (Avena sativa) embryo and endosperm transcription factor expression reveals differential expression of potential importance for seed development - Sandeep Kumar Kushwaha; Åsa Grimberg; Anders S. Carlsson; Per Hofvander (Molecular Genetics and Genomics, 2019)

Anomalous transients in GPS measurements due to induced changes in local site conditions - Sandeep Gupta; Paresh Nath Singharoy; Rajeev Kumar Yadav; Joshi K Catherine; Roland Burgmann; Vineet K Gahalaut (Journal of Earth System Science, 2019)

Late Holocene palaeovegetational and environmental changes inferred from organic geochemical proxies in sediments from Pookot Lake, southern India - Sandeep Kizhur; Rajasekhariah Shankar; Anish Kumar Warrier; Madhusudan G. Yadava; Rengaswamy Ramesh; Rashmikant A Jani (Arabian Journal of Geosciences, 2019)

Gene pyramiding for elite tomato genotypes against ToLCV (Begomovirus spp.), late blight (Phytophthora infestans) and RKN (Meloidogyne spp.) for northern India farmers - Ashish Kumar; Salesh Kumar Jindal; Major Singh Dhaliwal; Abhishek Sharma; Sukhjeet Kaur; Sandeep Jain (Physiology and Molecular Biology of Plants, 2019)

Foliar Application of Iron Fortified Bacteriosiderophore Improves Growth and Grain Fe Concentration in Wheat and Soybean - Sandeep Sharma; Subhash Chandra; Arun Kumar; Prem Bindraban; Anil Kumar Saxena; Veena Pande; Renu Pandey (Indian Journal of Microbiology, 2019)

Response of Soil Greenhouse Gas Fluxes and Soil Properties to Nitrogen Fertilizer Rates under Camelina and Carinata Nonfood Oilseed Crops - Ning Li; Pardeep Kumar; Liming Lai; Gandura Omar Abagandura; Sandeep Kumar; Thandiwe Nleya; Heidi L. Sieverding; James J. Stone; William Gibbons (BioEnergy Research, 2019)

Hydrochemical investigations of groundwater quality for drinking and irrigational purposes: two case studies of Koprivnica-Križevci County (Croatia) and district Allahabad (India) - Jasna Nemčić-Jurec; Sudhir Kumar Singh; Anamarija Jazbec; Sandeep Kumar Gautam; Ivan Kovač (Sustainable Water Resources Management, 2019)

Modelling of strong motion generation areas for a great earthquake in central seismic gap region of Himalayas using the modified semi-empirical approach - Sandeep; A Joshi; S K Sah; Parveen Kumar; Sohan Lal; Kamal (Journal of Earth System Science, 2019)

Mapping human health risk by geostatistical method: a case study of mercury in drinking groundwater resource of the central ganga alluvial plain, northern India - Ashwani Raju; Anjali Singh; Nupur Srivastava; Sandeep Singh; Dharmendra Kumar Jigyasu; Munendra Singh (Environmental Monitoring and Assessment, 2019)

Genetic variant rs10937405 of TP63 and susceptibility to lung cancer risk in north Indian population - GH. Rasool Bhat; Amrita Bhat; Sonali Verma; Itty Sethi; Ruchi Shah; Varun Sharma; S. Minerva; Divya Bakshi; Bhanu Sharma; Sandeep Koul; Deepak Abrol; Audesh Bhat; et al. (Journal of Genetics, 2019)

Recent advances and opportunities in the treatment of hydrocarbons and oils: Metal-organic frameworks-based approaches - Vanish Kumar; Kowsalya Vellingiri; Deepak Kukkar; Sandeep Kumar; Ki-Hyun Kim (Critical Reviews in Environmental Science and Technology, 2019)

Role of Reactive Oxygen Species in Cancer Progression - Dharambir Kashyap; Hardeep Singh Tuli; Katrin Sak; Vivek Kumar Garg; Neelam Goel; Sandeep Punia; Ashun Chaudhary (Current Pharmacology Reports, 2019)

Response of alley cropping-grown sesame to lime and sulphur on yield and available nutrient status in an acidic soil of Eastern India - Ram Swaroop Meena; Sandeep Kumar; Jitendra Singh Bohra; Rattan Lal; Gulab Singh Yadav; Achyutanand Pandey (Energy, Ecology and Environment, 2019)

Foliar application of organic and inorganic iron formulation induces differential detoxification response to improve growth and biofortification in soybean - Sandeep Sharma; Hina Malhotra; Priyanka Borah; Mukesh Kumar Meena; Prem Bindraban; Subhash Chandra; Veena Pande; Renu Pandey (Plant Physiology Reports, 2019)

Pollution tolerance assessment of temperate woody vegetation growing along the National Highway-5 in Himachal Pradesh, India - Bhavika Sharma; Satish Kumar Bhardwaj; Sandeep Sharma; Raman Nautiyal; Lakhvinder Kaur; N. M. Alam (Environmental Monitoring and Assessment, 2019)

Complete mitochondrial genome of northern Indian red muntjac (Muntiacus vaginalis) and its phylogenetic analysis - Bhim Singh; Ajit Kumar; Virendra Prasad Uniyal; Sandeep Kumar Gupta (Molecular Biology Reports, 2019)

Beneficial effects of fenofibrate in pulmonary hypertension in rats - Palak Galhotra; Pankaj Prabhakar; Himanshu Meghwani; Soheb A. Mohammed; Sanjay Kumar Banerjee; Sandeep Seth; Milind P. Hote; K. H. Reeta; Ruma Ray; Subir Kumar Maulik (Molecular and Cellular Biochemistry, 2018)

Genome-wide identification, classification and expression of lipoxygenase gene family in pepper - Sandeep J. Sarde; Abhishek Kumar; Rahima N. Remme; Marcel Dicke (Plant Molecular Biology, 2018)

Assessing coastal landscape vulnerability using geospatial techniques along Vizianagaram–Srikakulam coast of Andhra Pradesh, India - Meenu Rani; Sufia Rehman; Haroon Sajjad; B. S. Chaudhary; Jyoti Sharma; Sandeep Bhardwaj; Pavan Kumar (Natural Hazards, 2018)

In Silico Prediction of Diffusion Interaction Parameter (kD), a Key Indicator of Antibody Solution Behaviors - Dheeraj S. Tomar; Satish K. Singh; Li Li; Matthew P. Broulidakis; Sandeep Kumar (Pharmaceutical Research, 2018)

Development of immunodiagnostics for the detection of Grapevine leafroll-associated virus 3 (GLRaV-3) in grapevine using in vitro expression and purification of its coat protein gene - Sandeep Kumar; Priyanka Singh; Richa Rai; Virendra Kumar Baranwal (Journal of Plant Biochemistry and Biotechnology, 2018)

Identification of bioactive constituents from different fractions of stems of Cuscuta reflexa Roxb. using GC-MS - Diptirani Rath; Sandeep Kumar Panigrahi; Durga Madhab Kar; Laxmidhar Maharana (Natural Product Research, 2018)

Sugarcane ratoon discrimination using LANDSAT NDVI temporal data - Sandeep Kumar Singla; Rahul Dev Garg; Om Prakash Dubey (Spatial Information Research, 2018)

Modeling of the strong ground motion of 25th April 2015 Nepal earthquake using modified semi-empirical technique - Sohan Lal; A. Joshi; Sandeep; Monu Tomer; Parveen Kumar; Chun-Hsiang Kuo; Che-Min Lin; Kuo-Liang Wen; M. L. Sharma (Acta Geophysica, 2018)

Mechanosensitive microRNA-181b Regulates Aortic Valve Endothelial Matrix Degradation by Targeting TIMP3 - Jack M. Heath; Joan Fernandez Esmerats; Lucky Khambouneheuang; Sandeep Kumar; Rachel Simmons; Hanjoong Jo (Cardiovascular Engineering and Technology, 2018)

Seven-Year Impact of Cover Crops on Soil Health When Corn Residue Is Removed - Brianna R. Wegner; Shannon L. Osborne; R. Michael Lehman; Sandeep Kumar (BioEnergy Research, 2018)

Determination of site effect and anelastic attenuation at Kathmandu, Nepal Himalaya region and its use in estimation of source parameters of 25 April 2015 Nepal earthquake Mw = 7.8 and its aftershocks including the 12 May 2015 Mw = 7.3 event - Parveen Kumar; A. Joshi; Sushil Kumar; Sandeep; Sohan Lal (Natural Hazards, 2018)

Yorkie Regulates Neurodegeneration Through Canonical Pathway and Innate Immune Response - Sandeep Kumar Dubey; Madhu G. Tapadia (Molecular Neurobiology, 2018)

Simulation of Strong Ground Motion of the 2009 Bhutan Earthquake Using Modified Semi-Empirical Technique - Sandeep; A. Joshi; Sohan Lal; Parveen Kumar; S. K. Sah; Vandana; Kamal (Pure and Applied Geophysics, 2017)

Genetic Diversity Among Indigenous Germplasm of Brassica juncea (L.) Czern and Coss, Using Agro-Morphological and Phenological Traits - Rashmi Yadav; Ranbir Singh; Sandeep Kumar; T. V. Prasad; Rakesh Bharadwaj; Vikender Kaur; Anitha Petapadi; Ashok Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Multiyear observations of deposition-mode ice nucleating particles at two high-altitude stations in India - Sandeep D. Wagh; Baban Nagare; Sanjay D. More; P. Pradeep Kumar (Advances in Atmospheric Sciences, 2017)

A Dual-Signaling Ferrocene-Pyrene Dyad: Triple-Mode Recognition of the Cu(II) Ions in Aqueous Medium - Manzoor Ahmad Wani; Mrituanjay D. Pandey; Rampal Pandey; Sandeep Kumar Maurya; Debabrata Goswami (Journal of Fluorescence, 2017)

Expanding the spectrum of germline variants in cancer - Abdul K. Siraj; Tariq Masoodi; Rong Bu; Sandeep Kumar Parvathareddy; Ismail A. Al-Badawi; Nasser Al-Sanea; Luai H. Ashari; Alaa Abduljabbar; Samar Alhomoud; Saif S. Al-Sobhi; Asma Tulbah; Dahish Ajarim; et al. (Human Genetics, 2017)

Studies on Core-Shell Nanocapsules of Felodipine: In Vitro-In Vivo Evaluations - Jerome K. Geroge; Priya Ranjan Prasad Verma; Jayachandran Venkatesan; Jin-Young Lee; Dong-Han Yoon; Se-Kwon Kim; Sandeep Kumar Singh (AAPS PharmSciTech, 2017)

Response of Winter Manure Application on Surface Runoff Water Quantity and Quality from Small Watersheds in South Dakota - Shikha Singh; Nathan Brandenburg; Laurent Ahiablame; Arturo Gonzalez; Jeppe Kjaersgaard; Todd P. Trooien; Sandeep Kumar (Water, Air, & Soil Pollution, 2017)

Neuroprotection Through Rapamycin-Induced Activation of Autophagy and PI3K/Akt1/mTOR/CREB Signaling Against Amyloid-β-Induced Oxidative Stress, Synaptic/Neurotransmission Dysfunction, and Neurodegeneration in Adult Rats - Abhishek Kumar Singh; Mahendra Pratap Kashyap; Vinay Kumar Tripathi; Sandeep Singh; Geetika Garg; Syed Ibrahim Rizvi (Molecular Neurobiology, 2017)

Use of geochemical tracers for estimating groundwater influxes to the Big Sioux River, eastern South Dakota, USA - Ram P. Neupane; Sushant Mehan; Sandeep Kumar (Hydrogeology Journal, 2017)

A synthetic approach and molecular docking study of hybrids of quinazolin-4-ones and thiazolidin-4-ones as anticancer agents - Samridhi Thakral; Deepika Saini; Ashwani Kumar; Neelam Jain; Sandeep Jain (Medicinal Chemistry Research, 2017)

RETRACTED ARTICLE: Surface modification minimizes the toxicity of silver nanoparticles: an in vitro and in vivo study - Balaram Das; Satyajit Tripathy; Jaydeep Adhikary; Sourav Chattopadhyay; Debasis Mandal; Sandeep Kumar Dash; Sabyasachi Das; Aditi Dey; Sankar Kumar Dey; Debasis Das; Somenath Roy (JBIC Journal of Biological Inorganic Chemistry, 2017)

Physical and biochemical aspects of host plant resistance to mustard aphid, Lipaphis erysimi (Kaltenbach) in rapeseed-mustard - Sandeep Kumar; Y. P. Singh; S. P. Singh; Ram Singh (Arthropod-Plant Interactions, 2017)

Amino acid profiling of Sorghum bicolor vis-à-vis Chilo partellus (Swinhoe) for biochemical interactions and plant resistance - Mukesh K. Dhillon; Sandeep Kumar (Arthropod-Plant Interactions, 2017)

Concentration Dependent Approach for Accurate Determination of Two-Photon Absorption Cross-Section of Fluorescent dye Molecule - Sandeep Kumar Maurya; Chayan Dutta; Debabrata Goswami (Journal of Fluorescence, 2017)

Syntrophic association and performance of Clostridium, Desulfovibrio, Aeromonas and Tetrathiobacter as anodic biocatalysts for bioelectricity generation in dual chamber microbial fuel cell - Smita S. Kumar; Sandeep K. Malyan; Suddhasatwa Basu; Narsi R Bishnoi (Environmental Science and Pollution Research, 2017)

Source Parameters and High Frequency Characteristics of Local Events (0.5 ≤ M L ≤ 2.9) Around Bilaspur Region of the Himachal Himalaya - Vandana; Ashwani Kumar; S. C. Gupta; O. P. Mishra; Arjun Kumar; Sandeep (Pure and Applied Geophysics, 2017)

National Inventory of Rabi Pulses in India Using Remotely Sensed Data - Nita Bhagia; G. D. Bairagi; Sandeep Pandagre; Gajendra Patel; S. P. Vyas; G. N. Naveen Kumar; Indal Ramteke; Pritam Mesharam (Journal of the Indian Society of Remote Sensing, 2017)

Oxidative Stress Markers in Vitamin B12 Deficiency - Usha Kant Misra; Jayantee Kalita; Sandeep Kumar Singh; Sushil Kumar Rahi (Molecular Neurobiology, 2017)

Mitochondrial and Nuclear DNA Based Genetic Assessment Indicated Distinct Variation and Low Genetic Exchange Among the Three Subspecies of Swamp Deer (Rucervus duvaucelii) - Ajit Kumar; Mirza Ghazanfar Ullah Ghazi; Syed Ainul Hussain; Dinesh Bhatt; Sandeep Kumar Gupta (Evolutionary Biology, 2017)

Preparation, characterization, and bio-efficacy evaluation of controlled release carbendazim-loaded polymeric nanoparticles - Sandhya; Sandeep Kumar; Dinesh Kumar; Neeraj Dilbaghi (Environmental Science and Pollution Research, 2017)

An Improved Micropropagation and Assessment of Genetic Fidelity in Multipurpose Medicinal Tree, Acacia auriculiformis - Rakesh Yadav; Neha Yadav; Sandeep Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

The Dual Role of Lipids of the Lipoproteins in Trumenba, a Self-Adjuvanting Vaccine Against Meningococcal Meningitis B Disease - Yin Luo; Olga V. Friese; Herbert A. Runnels; Lakshmi Khandke; Gary Zlotnick; Ann Aulabaugh; Thomas Gore; Eugene Vidunas; Stephen W. Raso; Elena Novikova; Emilia Byrne; Michael Schlittler; et al. (The AAPS Journal, 2016)

A trait stacking system via intra-genomic homologous recombination - Sandeep Kumar; Andrew Worden; Stephen Novak; Ryan Lee; Joseph F. Petolino (Planta, 2016)

Cryopreservation of adult primate testes - Lavanya Pothana; Naresh Kumar Venna; Lalitha Devi; Anju Singh; Ipsita Chatterjee; Sandeep Goel (European Journal of Wildlife Research, 2016)

New frontiers in chemical energy and environmental engineering - Srinath Suranani; Sandeep Kumar; Sundergopal Sridhar (Environmental Science and Pollution Research, 2016)

Wintertime precipitation variability over the Arabian Peninsula and its relationship with ENSO in the CAM4 simulations - K. Niranjan Kumar; T. B. M. J. Ouarda; S. Sandeep; R. S. Ajayamohan (Climate Dynamics, 2016)

Investigating Two-Photon-Induced Fluorescence in Rhodamine-6G in Presence of Cetyl-Trimethyl-Ammonium-Bromide - Sandeep Kumar Maurya; Dheerendra Yadav; Debabrata Goswami (Journal of Fluorescence, 2016)

Investigation of dominant modes of monsoon ISO in the northwest and eastern Himalayan region - Sandipan Mukherjee; Srabanti Ballav; Sandeep Soni; Kireet Kumar; Utpal Kumar De (Theoretical and Applied Climatology, 2016)

Development and evaluation of film coated aceclofenac and chlorzoxazone tablet with enhanced dissolution rate - Shaila Jain; Aakankchha Jain; Ashay Jain; Sandeep Shrivastava; Amit Kumar Jain (Journal of Pharmaceutical Investigation, 2016)

Pan-genome analysis of Aeromonas hydrophila, Aeromonas veronii and Aeromonas caviae indicates phylogenomic diversity and greater pathogenic potential for Aeromonas hydrophila - Sandeep Ghatak; Jochen Blom; Samir Das; Rajkumari Sanjukta; Kekungu Puro; Michael Mawlong; Ingudam Shakuntala; Arnab Sen; Alexander Goesmann; Ashok Kumar; S. V. Ngachan (Antonie van Leeuwenhoek, 2016)

Ferulic acid amide derivatives as anticancer and antioxidant agents: synthesis, thermal, biological and computational studies - Naresh Kumar; Sandeep Kumar; Sheenu Abbat; Kumar Nikhil; Sham M. Sondhi; Prasad V. Bharatam; Partha Roy; Vikas Pruthi (Medicinal Chemistry Research, 2016)

Convenient synthesis, anticancer evaluation and QSAR studies of some thiazole tethered indenopyrazoles - Satbir Mor; Savita Nagoria; Ashwani Kumar; Jitender Monga; Sandeep Lohan (Medicinal Chemistry Research, 2016)

Interpolation study on ambient gamma levels in parts of Khasi Hills, Meghalaya (India): Preliminary findings for U exploration - B M KUKRETI; G K SHARMA; PRAMOD KUMAR; SANDEEP HAMILTON (Journal of Earth System Science, 2016)

Pharmacokinetic evaluation of cefdinir-loaded floating alginate beads in rabbits using LC–MS/MS - Praveen R; Sandeep Kumar Singh; Priya Ranjan Prasad Verma (Journal of Pharmaceutical Investigation, 2016)

Adsorptive desulfurization by zinc-impregnated activated carbon: characterization, kinetics, isotherms, and thermodynamic modeling - Sandeep Kumar Thaligari; Vimal Chandra Srivastava; Basheswar Prasad (Clean Technologies and Environmental Policy, 2016)

Anti-skin ageing activity of napthoquinones from Arnebia nobilis Reichb.f. - Satyabrata Mohapatra; R. Sandeep Varma; L.M. Sharath Kumar; O.S. Thiyagarajan; M. Vijaykumar; K. Dilmel; M. Nishant; U.V. Babu; P.S. Patki (Natural Product Research, 2016)

Microbiological Analyses of Traditional Alcoholic Beverage (Chhang) and its Starter (Balma) Prepared by Bhotiya Tribe of Uttarakhand, India - Kailash N. Bhardwaj; Kavish Kumar Jain; Sandeep Kumar; Ramesh Chander Kuhad (Indian Journal of Microbiology, 2016)

Possible vasculoprotective role of linagliptin against sodium arsenite-induced vascular endothelial dysfunction - Uma Jyoti; Sunil Kumar Kansal; Puneet Kumar; Sandeep Goyal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

In vitro plant regeneration of Ocimum basilicum L. is accelerated by zinc sulfate - Sandeep Kumar Verma; Gunce Sahin; Ashok Kumar Das; Ekrem Gurel (In Vitro Cellular & Developmental Biology - Plant, 2016)

Evidences for anti-mycobacterium activities of lipids and surfactants - Afzal Hussain; Sandeep Kumar Singh (World Journal of Microbiology and Biotechnology, 2016)

Morphological and in vitro investigation of core–shell nanostructures of carvedilol using quality by design - Jerome K. George; Sandeep Kumar Singh; Priya Ranjan Prasad Verma (Journal of Pharmaceutical Investigation, 2015)

Mutational landscape of the human Y chromosome-linked genes and loci in patients with hypogonadism - DEEPALI PATHAK; SANDEEP KUMAR YADAV; LEENA RAWAL; SHER ALI (Journal of Genetics, 2015)

Development and Optimization of Gastro-Retentive Controlled-Release Tablet of Calcium-Disodium Edentate and its In Vivo Gamma Scintigraphic Evaluation - Neeraj Kumar; Sandeep Soni; Thakuri Singh; Amit Kumar; Farhan Jalees Ahmad; Aseem Bhatnagar; Gaurav Mittal (AAPS PharmSciTech, 2015)

Identification of globally threatened cervids from problematic samples using cytochrome b and control region genes - Sangeeta Angom; Sandeep Kumar Gupta; Ajit Kumar; Syed Ainul Hussain (Conservation Genetics Resources, 2015)

Major ion chemistry of the Son River, India: Weathering processes, dissolved fluxes and water quality assessment - Chinmaya Maharana; Sandeep Kumar Gautam; Abhay Kumar Singh; Jayant K Tripathi (Journal of Earth System Science, 2015)

Preformulation and physicochemical interaction study of furosemide with different solid lipids - Hasan Ali; Sandeep Kumar Singh; Priya Ranjan Prasad Verma (Journal of Pharmaceutical Investigation, 2015)

Development of an immunocapture–reverse transcription–polymerase chain reaction (IC-RT-PCR) using modified viral RNA release protocol for the detection of Grapevine leafroll-associated virus 3 (GLRaV-3) - Sandeep Kumar; Richa Rai; V. K. Baranwal (Phytoparasitica, 2015)

Inter specific hybridization (Brassica carinata × Brassica oleracea) for introgression of black rot resistance genes into Indian cauliflower (B. oleracea var. botrytis L.). - S. S. Dey; Kanika Sharma; R. Bhatia Dey; G. M. Sandeep Kumar; Dinesh Singh; Raj Kumar; Chander Parkash (Euphytica, 2015)

Effect of zinc supplements in the attenuated cardioprotective effect of ischemic preconditioning in hyperlipidemic rat heart - Sunil Kumar Kansal; Uma Jyoti; Samridhi Sharma; Arun Kaura; Rahul Deshmukh; Sandeep Goyal (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Modeling of strong motion generation areas of the Niigata, Japan, earthquake of 2007 using modified semi-empirical technique - Sandeep; A. Joshi; Kamal; Parveen Kumar; Ashvini Kumar; Piu Dhibar (Natural Hazards, 2015)

In-silico search of virus-specific host microRNAs regulating avian influenza virus NS1 expression - V. N. Muhasin Asaf; Amod Kumar; Ashwin Ashok Raut; Sandeep Bhatia; Anamika Mishra (Theory in Biosciences, 2015)

Evidence for bactericidal activities of lipidic nanoemulsions against Pseudomonas aeruginosa - Neeru Singh; Saurabh Manaswita Verma; Sandeep Kumar Singh; Priya Ranjan Prasad Verma (Antonie van Leeuwenhoek, 2015)

Denitrification kinetics in biomass- and biochar-amended soils of different landscape positions - Rajesh Chintala; Rachel K Owen; Thomas E Schumacher; Kurt A Spokas; Louis M McDonald; Sandeep Kumar; David E Clay; Douglas D Malo; Bruce Bleakley (Environmental Science and Pollution Research, 2015)

Cross linked alginate gel beads as floating drug delivery system for cefdinir: optimization using Box–Behnken design - Radhakrishnan Praveen; Priya Ranjan Prasad Verma; Sandeep Kumar Singh; Jerome Karippamattom George (Journal of Pharmaceutical Investigation, 2015)

Cryosurgical Treatment of Equine Maxillo-Facial Sarcoids and Vulvar Leiomyomas - Swapan Kumar Maiti; Naveen Kumar; Dayamon Mathew; Sandeep Kumar; Ninu Ajantha Ravindran (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2015)

A combinatorial bidirectional and bicistronic approach for coordinated multi-gene expression in corn - Sandeep Kumar; Diaa AlAbed; John T. Whitteck; Wei Chen; Sara Bennett; Andrew Asberry; Xiujuan Wang; Daniel DeSloover; Murugesan Rangasamy; Terry R. Wright; Manju Gupta (Plant Molecular Biology, 2015)

Estrogenic and Anti-Alzheimer’s studies of Zingiber officinalis as well as Amomum subulatum Roxb.: the success story of dry techniques - Ashwani Kumar; Ruchika Goyal; Sunil Kumar; Sandeep Jain; Neelam Jain; Parvin Kumar (Medicinal Chemistry Research, 2015)

Three-Dimensional Attenuation Structure of the Kumaon Himalayas, India, Based on Inversion of Strong Motion Data - Parveen Kumar; A. Joshi; Sandeep; Ashvini Kumar (Pure and Applied Geophysics, 2015)

Modeling groundwater quality over a humid subtropical region using numerical indices, earth observation datasets, and X-ray diffraction technique: a case study of Allahabad district, India - Sudhir Kumar Singh; Prashant K. Srivastava; Dharmveer Singh; Dawei Han; Sandeep Kumar Gautam; A. C. Pandey (Environmental Geochemistry and Health, 2015)

ABA-dependent sucrose regulation of antioxidant metabolism in wheat cultivars varying in ABA-sensitivity - Sandeep Kaur; Anil Kumar Gupta; Vikramjit Kaur Zhawar (Biologia, 2015)

Coda wave attenuation characteristics for Kumaon and Garhwal Himalaya, India - Ashvini Kumar; A. Sinvhal; A. Joshi; D. Kumar; Sandeep; Parveen Kumar (Natural Hazards, 2015)

Phosphonomethyl iminodiacetic acid-conjugated cobalt oxide nanoparticles liberate Co++ ion-induced stress associated activation of TNF-α/p38 MAPK/caspase 8-caspase 3 signaling in human leukemia cells - Sourav Chattopadhyay; Sandeep Kumar Dash; Satyajit Tripathy; Panchanan Pramanik; Somenath Roy (JBIC Journal of Biological Inorganic Chemistry, 2015)

Embryogenesis, plant regeneration and cardiac glycoside determination in Digitalis ferruginea subsp. ferruginea L - Sandeep Kumar Verma; Buhara Yucesan; Gunce Sahin; Ekrem Gurel (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Synthesis and antibacterial activity of novel fluoroquinolone analogs - Sandeep Kumar Dixit; Neesha Yadav; Satyanand Kumar; Liam Good; Satish K. Awasthi (Medicinal Chemistry Research, 2014)

Quantitative structure–activity relationship (QSAR) studies as strategic approach in drug discovery - Harun M. Patel; Malleshappa N. Noolvi; Poonam Sharma; Varun Jaiswal; Sumit Bansal; Sandeep Lohan; Suthar Sharad Kumar; Vikrant Abbot; Saurabh Dhiman; Varun Bhardwaj (Medicinal Chemistry Research, 2014)

Sustained delivery of cefdinir to upper gastrointestinal tract using calcium alginate beads: a formulation by design - Radhakrishnan Praveen; Sandeep Kumar Singh; Priya Ranjan Prasad Verma; Jerome Karippamattom George (Journal of Pharmaceutical Investigation, 2014)

Concentration Dependent Viscosity of Monoclonal Antibody Solutions: Explaining Experimental Behavior in Terms of Molecular Properties - Li Li; Sandeep Kumar; Patrick M. Buck; Christopher Burns; Janelle Lavoie; Satish K. Singh; Nicholas W. Warne; Pilarin Nichols; Nicholas Luksha; Davin Boardman (Pharmaceutical Research, 2014)

The Flavonoid Derivative 2-(4′ Benzyloxyphenyl)-3-hydroxy-chromen-4-one Protects Against Aβ42-Induced Neurodegeneration in Transgenic Drosophila: Insights from In Silico and In Vivo Studies - Sandeep Kumar Singh; Ruchi Gaur; Akhil Kumar; Roshan Fatima; Lallan Mishra; Saripella Srikrishna (Neurotoxicity Research, 2014)

Catecholase activity, DNA cleavage and cytotoxicity of six Zn(II) complexes synthesized from designed Mannich ligands: higher reactivity of mononuclear over dinuclear - Ria Sanyal; Sandeep Kumar Dash; Sudhanshu Das; Sourav Chattopadhyay; Somenath Roy; Debasis Das (JBIC Journal of Biological Inorganic Chemistry, 2014)

In vitro and in vivo pathogenicity studies of Pasteurella multocida strains harbouring different ompA - Shailja Katoch; Mandeep Sharma; R. D. Patil; Sandeep Kumar; Subhash Verma (Veterinary Research Communications, 2014)

Modeling of strong motion generation area of the Uttarkashi earthquake using modified semiempirical approach - Sandeep; A. Joshi; Kamal; Parveen Kumar; Pushpa Kumari (Natural Hazards, 2014)

Effect of frequency-dependent radiation pattern in the strong motion simulation of the 2011 Tohoku earthquake, Japan, using modified semi-empirical method - Sandeep; A. Joshi; Kamal; Parveen Kumar; Ashvini Kumar (Natural Hazards, 2014)

Efficient synthesis of heterocyclic compounds derived from 2,6-dioxopiperazine derivatives and their evaluation for anti-inflammatory and anticancer activities - Sandeep Kumar; Nikhil Kumar; Partha Roy; Sham M. Sondhi (Medicinal Chemistry Research, 2014)

Novel primers for sequencing of the complete mitochondrial cytochrome b gene of ungulates using non-invasive and degraded biological samples - Sandeep Kumar Gupta; Ajit Kumar; Syed Aniul Hussain (Conservation Genetics Resources, 2014)

Detection and molecular characterization of naturally transmitted sheep associated malignant catarrhal fever in cattle in India - Richa Sood; Rekha Khandia; Sandeep Bhatia; Divakar Hemadri; Manoj Kumar; Sharan S. Patil; Atul K. Pateriya; Arshi Siddiqui; Malkanna Sanjeev Kumar; Mudalagiri Dasappa Venkatesha; Diwakar D. Kulkarni (Tropical Animal Health and Production, 2014)

Identification of genes involved in carbon metabolism from Eleusine coracana (L.) for understanding their light-mediated entrainment and regulation - Pooja Kanwal; Supriya Gupta; Sandeep Arora; Anil Kumar (Plant Cell Reports, 2014)

Electrostatic effects control the stability and iron release kinetics of ovotransferrin - Sandeep Kumar; Deepak Sharma; Rajesh Kumar; Rajesh Kumar (JBIC Journal of Biological Inorganic Chemistry, 2014)

Application of isolated bacterial consortium in UMBR for detoxification of textile effluent: comparative analysis of resultant oxidative stress and genotoxicity in catfish (Heteropneustes fossilis) exposed to raw and treated effluents - Priya Banerjee; Sandeep Sarkar; Tanmoy Kumar Dey; Madhurima Bakshi; Snehasikta Swarnakar; Aniruddha Mukhopadhayay; Sourja Ghosh (Ecotoxicology, 2014)

Genetic studies on morpho-phenological traits in lentil (Lens culinaris Medikus) wide crosses - MOHAR SINGH; ISHWARI SINGH BISHT; MANORANJAN DUTTA; KRISHNA KUMAR; SANDEEP KUMAR; KAILASH CHANDER BANSAL (Journal of Genetics, 2014)

Assessment of Physical Stability of an Antibody Drug Conjugate by Higher Order Structure Analysis: Impact of Thiol- Maleimide Chemistry - Jianxin Guo; Sandeep Kumar; Amarnauth Prashad; Jason Starkey; Satish K. Singh (Pharmaceutical Research, 2014)

Immunophenotypic characterization and tenogenic differentiation of mesenchymal stromal cells isolated from equine umbilical cord blood - Niharika Mohanty; Baldev R. Gulati; Rajesh Kumar; Sandeep Gera; Pawan Kumar; Rajesh K. Somasundaram; Sandeep Kumar (In Vitro Cellular & Developmental Biology - Animal, 2014)

Molecular identification of man-eating carnivores from scat samples - Sandeep Kumar Gupta; Ajit Kumar (Conservation Genetics Resources, 2014)

Perylene Diimide Appended with 8-Hydroxyquinoline for Ratiometric Detection of Cu2+ Ions and Metal Displacement Driven “Turn on” Cyanide Sensing - Prabhpreet Singh; Lalit Singh Mittal; Sandeep Kumar; Gaurav Bhargava; Subodh Kumar (Journal of Fluorescence, 2014)

Earthquake damage identification: a case study using soft classification approach - Sandeep Singh Sengar; Sanjay Kumar Ghosh; Anil Kumar; Hans Raj Wason (Natural Hazards, 2014)

Chitosan-modified cobalt oxide nanoparticles stimulate TNF-α-mediated apoptosis in human leukemic cells - Sourav Chattopadhyay; Sandeep Kumar Dash; Santanu Kar Mahapatra; Satyajit Tripathy; Totan Ghosh; Balaram Das; Debasis Das; Panchanan Pramanik; Somenath Roy (JBIC Journal of Biological Inorganic Chemistry, 2014)

Modeling the Effect of Temperature and Precipitation on Crop Residue Potential for the North Central Region of the United States - Rajesh Chintala; Gemechis D Djira; Mitra L Devkota; Rishi Prasad; Sandeep Kumar (Agricultural Research, 2014)

Use of site amplification and anelastic attenuation for the determination of source parameters of the Sikkim earthquake of September 18, 2011, using far-field strong-motion data - A. Joshi; Parveen Kumar; Sandeep Arora (Natural Hazards, 2014)

The South India Precambrian crust and shallow lithospheric mantle: Initial results from the India Deep Earth Imaging Experiment (INDEX) - S S RAI; KAJALJYOTI BORAH; RITIMA DAS; SANDEEP GUPTA; SHALIVAHAN SRIVASTAVA; K S PRAKASAM; K SIVARAM; SUDESH KUMAR; RISHIKESH MEENA (Journal of Earth System Science, 2013)

Expression of drought responsive genes in pigeonpea and in silico comparison with soybean cDNA library - Nagaraja Deeplanaik; Ramesh Chapeyil Kumaran; Krishna Venkatarangaiah; Santosh Kumar Hulikal Shivashankar; Dadakhalandar Doddamani; Sandeep Telkar (Journal of Crop Science and Biotechnology, 2013)

Anticancer and immunostimulatory role of encapsulated tumor antigen containing cobalt oxide nanoparticles - Sourav Chattopadhyay; Sandeep Kumar Dash; Totan Ghosh; Sabyasachi Das; Satyajit Tripathy; Debasis Mandal; Debasis Das; Panchanan Pramanik; Somenath Roy (JBIC Journal of Biological Inorganic Chemistry, 2013)

Synthesis, anti-inflammatory, and antiproliferative activity evaluation of isoindole, pyrrolopyrazine, benzimidazoisoindole, and benzimidazopyrrolopyrazine derivatives - Sandeep Kumar; Nikhil Kumar; Partha Roy; Sham M. Sondhi (Molecular Diversity, 2013)

Study of binding of pyridoacridine alkaloids on topoisomerase II using in silico tools - Ashwani Kumar; Sunil Kumar; Sandeep Jain; Parvin Kumar; Ruchika Goyal (Medicinal Chemistry Research, 2013)

Efficient Entrapment of Dye in Hollow Silica Nanoparticles: Direct Evidence Using Fluorescence Spectroscopy - Arabinda Baruah; Sandeep Kumar; Sonalika Vaidya; Ashok K. Ganguli (Journal of Fluorescence, 2013)

Genotyping and subtyping of mumps virus isolates from the Indian subcontinent - Baijayantimala Mishra; Sujit Kumar Pujhari; Vandana Dhiman; P. MahaLakshmi; Abhinav Bharadwaj; Sandeep Pokhrel; Deepak Sharma; Mirnalini Sharma; Deepak Bhatia; Radha Kanta Ratho (Archives of Virology, 2013)

Efficient synthesis of piperazine-2,6-dione and 4-(1H-indole-2-carbonyl)piperazine-2,6-dione derivatives and their evaluation for anticancer activity - Sandeep Kumar; Nikhil Kumar; Partha Roy; Sham M. Sondhi (Medicinal Chemistry Research, 2013)

Characterization of released and elite genotypes of guar [Cyamopsis tetragonoloba (L.) Taub.] from India proves unrelated to geographical origin - Sandeep Kumar; U. N. Joshi; Vikram Singh; J. V. Singh; M. L. Saini (Genetic Resources and Crop Evolution, 2013)

Assessment of functional and genetic diversity of aerobic endospore forming Bacilli from rhizospheric soil of Phyllanthus amarus L. - Sangeeta Kadyan; Manju Panghal; Sandeep Kumar; Khushboo Singh; Jaya Parkash Yadav (World Journal of Microbiology and Biotechnology, 2013)

Integrated Assessment of Groundwater Influenced by a Confluence River System: Concurrence with Remote Sensing and Geochemical Modelling - Sudhir Kumar Singh; Prashant Kumar Srivastava; Avinash Chandra Pandey; Sandeep Kumar Gautam (Water Resources Management, 2013)

Synthesis, anti-inflammatory, and cytotoxicity evaluation of 9,10-dihydroanthracene-9,10-α,β-succinimide and bis-succinimide derivatives - Surbhi Arya; Sandeep Kumar; Reshma Rani; Nikhil Kumar; Partha Roy; Sham M. Sondhi (Medicinal Chemistry Research, 2013)

The Effect of N-Alkyl Substituents on the Usability of Imidazolium Cation-Based Ionic Liquids in Microemulsion Systems: A Technical Note - Neeraj Kumar; Shishu Goindi; Sandeep Kumar; Asim Kumar Jana (AAPS PharmSciTech, 2013)

Investigation on the hydrodynamics of Ganga Alluvial Plain using environmental isotopes: a case study of the Gomati River Basin, northern India - Munendra Singh; Sudhir Kumar; Bhishm Kumar; Sandeep Singh; Indra Bir Singh (Hydrogeology Journal, 2013)

Crustal Heterogeneity and Seismotectonics of the National Capital Region, Delhi, India - Sandeep Gupta; William K. Mohanty; Rajesh Prakash; Atindra Kumar Shukla (Pure and Applied Geophysics, 2013)

Circulating miRNA as novel markers for diastolic dysfunction - Nandini Nair; Sandeep Kumar; Enrique Gongora; Sudhiranjan Gupta (Molecular and Cellular Biochemistry, 2013)

Estimating the spatial distribution of organic carbon density for the soils of Ohio, USA - Sandeep Kumar; Rattan Lal; Desheng Liu; Rashid Rafiq (Journal of Geographical Sciences, 2013)

Profiling of virulence associated genes of Pasteurella multocida isolated from cattle - Subhash Verma; Mandeep Sharma; Shailja Katoch; Lovit Verma; Sandeep Kumar; Vishal Dogra; Rajesh Chahota; Prasenjit Dhar; Geetanjali Singh (Veterinary Research Communications, 2013)

Wavelet Based Post Classification Change Detection Technique for Urban Growth Monitoring - R. A. Alagu Raja; V. Anand; A. Senthil Kumar; Sandeep Maithani; V. Abhai Kumar (Journal of the Indian Society of Remote Sensing, 2013)

Extraction of PCR-amplifiable DNA from a variety of biological samples with uniform success rate - Sandeep Kumar Gupta; Ajit Kumar; Syed Ainul Hussain (Conservation Genetics Resources, 2013)

Identification and expression analysis of group 3 LEA family genes in sorghum [Sorghum bicolor (L.) Moench] - Monika Dalal; G. Sandeep Kumar; Karthikeyan Mayandi (Acta Physiologiae Plantarum, 2013)

Geomorphology Based Semi-Distributed Approach for Modelling Rainfall-Runoff Process - Rajib Kumar Bhattacharjya; Sandeep Chaurasia (Water Resources Management, 2013)

The October 20, 2011 Mw 5.1 Talala earthquake in the stable continental region of India - B. K. Rastogi; Santosh Kumar; Sandeep K. Aggrawal; Kapil Mohan; Nagabhushan Rao; N. Purnachandra Rao; Girish Ch. Kothyari (Natural Hazards, 2013)

Triggered/migrated seismicity due to the 2001 M w7.7 Bhuj earthquake, Western India - B. K. Rastogi; Sandeep Kumar Aggrawal; Nagabhushan Rao; Pallabee Choudhury (Natural Hazards, 2013)

Seismicity of Gujarat - B. K. Rastogi; Santosh Kumar; Sandeep Kumar Aggrawal (Natural Hazards, 2013)

DEM Generation for Lunar Surface using Chandrayaan-1 TMC Triplet Data - V. Sivakumar; Binay Kumar; Sandeep Kumar Srivastava; B. Gopala Krishna; Pradeep Kumar Srivastava; A. S. Kiran Kumar (Journal of the Indian Society of Remote Sensing, 2012)

Integrated approach for disease management and growth enhancement of Sesamum indicum L. utilizing Azotobacter chroococcum TRA2 and chemical fertilizer - D. K. Maheshwari; R. C. Dubey; Abhinav Aeron; Bhavesh Kumar; Sandeep Kumar; Sakshi Tewari; Naveen Kumar Arora (World Journal of Microbiology and Biotechnology, 2012)

Synthesis anti-inflammatory and anticancer activity evaluation of some pyrazole and oxadiazole derivatives - Sham M. Sondhi; Sandeep Kumar; Nikhil Kumar; Partha Roy (Medicinal Chemistry Research, 2012)

Ditosylate Salt of Itraconazole and Dissolution Enhancement Using Cyclodextrins - Neeraj Kumar; Shishu; Gulshan Bansal; Sandeep Kumar; Asim Kumar Jana (AAPS PharmSciTech, 2012)

Rock Mass Classification and Slope Stability Assessment of Road Cut Slopes in Garhwal Himalaya, India - S. Sarkar; D. P. Kanungo; Sandeep Kumar (Geotechnical and Geological Engineering, 2012)

Letter to the Editor: Characterization of a Grapevine leafroll-associated virus 3 from India showing incongruence in its phylogeny - Sandeep Kumar; Virendra K. Baranwal; Priyanka Singh; Rakesh K. Jain; Sanjay D. Sawant; Sanjay K. Singh (Virus Genes, 2012)

Erratum to: Seismicity of Gujarat - B. K. Rastogi; Santosh Kumar; Sandeep Kumar Aggrawal (Natural Hazards, 2012)

Tight controlled expression and secretion of Lactobacillus brevis SlpA in Lactococcus lactis - Axel Hollmann; Mariano Saviello; Lucrecia Delfederico; Tessália Diniz Luerce Saraiva; Debmalya Barh; Neha Jain; Sandeep Tiwari; Sudha Chandra; Krishnakant Gupta; Vasudeo Zambare; Anil Kumar; Lew Christopher; et al. (Biotechnology Letters, 2012)

Assessing spatial variability in soil characteristics with geographically weighted principal components analysis - Sandeep Kumar; Rattan Lal; Christopher D. Lloyd (Computational Geosciences, 2012)

Recent Advances in Biopolymers and Biopolymer-Based Nanocomposites for Food Packaging Materials - X. Z. Tang; P. Kumar; S. Alavi; K. P. Sandeep (Critical Reviews in Food Science and Nutrition, 2012)

Lenalidomide induced intrahepatic cholestasis in newly diagnosed patients of multiple myeloma - Rabindra Kumar Jena; Trupti Rekha Swain; Sandeep Sadashivrao Kansurkar; Manorama Swain (European Journal of Clinical Pharmacology, 2012)

Estimation of urban population in Indo-Gangetic Plains using night-time OLS data - Pranab Kanti Roy Chowdhury; Sandeep Maithani; Vinay Kumar Dadhwal (International Journal of Remote Sensing, 2012)

Water infiltration influenced by agroforestry and grass buffers for a grazed pasture system - Sandeep Kumar; Stephen H. Anderson; Ranjith P. Udawatta; Robert L. Kallenbach (Agroforestry Systems, 2012)

Distinct Aggregation Mechanisms of Monoclonal Antibody Under Thermal and Freeze-Thaw Stresses Revealed by Hydrogen Exchange - Aming Zhang; Satish K. Singh; Michael R. Shirts; Sandeep Kumar; Erik J. Fernandez (Pharmaceutical Research, 2012)

Monitoring of multiple drug-resistant pathogens in a selected stretch of Bay of Bengal, India - Sandeep Kumar Panda; Ajit Kumar Patra; Rabi Narayan Kar (Environmental Monitoring and Assessment, 2012)

Disulfide Scrambling in IgG2 Monoclonal Antibodies: Insights from Molecular Dynamics Simulations - Xiaoling Wang; Sandeep Kumar; Satish K. Singh (Pharmaceutical Research, 2011)

Genetic characterization of swine influenza viruses (H3N2) isolated from Minnesota in 2006–2007 - Sandeep R. P. Kumar; Laure Deflube; Moanaro Biswas; Raghunath Shobana; Subbiah Elankumaran (Virus Genes, 2011)

Antioxidant activity of organic and aqueous leaf extracts of Cassia occidentalis L. in relation to their phenolic content - Vedpriya Arya; Sanjay Yadav; Sandeep Kumar; Jaya Parkash Yadav (Natural Product Research, 2011)

APEX model simulation of runoff and sediment losses for grazed pasture watersheds with agroforestry buffers - Sandeep Kumar; Ranjith P. Udawatta; Stephen H. Anderson; Ashish Mudgal (Agroforestry Systems, 2011)

3-Aryl-2-{4-[4-(2,4-dioxothiazolidin-5-ylmethyl)phenoxy]-phenyl}-acrylic acid alkyl ester: synthesis and antihyperglycemic evaluation - Ashwani Kumar; Amit Chawla; Sandeep Jain; Parvin Kumar; Sunil Kumar (Medicinal Chemistry Research, 2011)

UCHL-1 protein expression specifically marks spermatogonia in wild bovid testis - Sandeep Goel; Ranjeet Singh Mahla; Sanjay Kumar Suman; Niranjan Reddy; Hiroshi Imai (European Journal of Wildlife Research, 2011)

Coupling of Aggregation and Immunogenicity in Biotherapeutics: T- and B-Cell Immune Epitopes May Contain Aggregation-Prone Regions - Sandeep Kumar; Satish K. Singh; Xiaoling Wang; Bonita Rup; Davinder Gill (Pharmaceutical Research, 2011)

Characterization of Brassica juncea antioxidant potential under salinity stress - Pankaj Kumar Joshi; Saurabh Chandra Saxena; Sandeep Arora (Acta Physiologiae Plantarum, 2011)

Effect of U50,488H, a κ-opioid receptor agonist on myocardial α-and β-myosin heavy chain expression and oxidative stress associated with isoproterenol-induced cardiac hypertrophy in rat - Amardeep Jaiswal; Santosh Kumar; Sandeep Seth; Amit Kumar Dinda; Subir Kumar Maulik (Molecular and Cellular Biochemistry, 2010)

Perspectives for genetic engineering of poplars for enhanced phytoremediation abilities - Rakesh Yadav; Pooja Arora; Sandeep Kumar; Ashok Chaudhury (Ecotoxicology, 2010)

Co-inoculation of Urea and DAP Tolerant Sinorhizobium meliloti and Pseudomonas aeruginosa as Integrated Approach for Growth Enhancement of Brassica juncea - Dinesh K. Maheshwari; Sandeep Kumar; Bhavesh Kumar; Piyush Pandey (Indian Journal of Microbiology, 2010)

Root length density and carbon content of agroforestry and grass buffers under grazed pasture systems in a Hapludalf - Sandeep Kumar; Ranjith P. Udawatta; Stephen H. Anderson (Agroforestry Systems, 2010)

Potential Aggregation-Prone Regions in Complementarity-Determining Regions of Antibodies and Their Contribution Towards Antigen Recognition: A Computational Analysis - Xiaoling Wang; Satish K. Singh; Sandeep Kumar (Pharmaceutical Research, 2010)

Conductometric behaviour of salts in sugar solution - Sandeep K. Mitra; Vikesh Kumar; P. Sanyal (Sugar Tech, 2010)

Trends and Perspectives of Biosensors for Food and Environmental Virology - Rakesh Yadav; Sadhana Dwivedi; Sandeep Kumar; Ashok Chaudhury (Food and Environmental Virology, 2010)

CT-measured macropores as affected by agroforestry and grass buffers for grazed pasture systems - Sandeep Kumar; Stephen H. Anderson; Ranjith P. Udawatta; Clark J. Gantzer (Agroforestry Systems, 2010)

Relative efficiency of diammonium phosphate and mussoorie rock phosphate on productivity and phosphorus balance in a rice–rapeseed–mungbean cropping system - S. N. Sharma; R. Prasad; Y. S. Shivay; M. K. Dwivedi; Sandeep Kumar; M. R. Davari; Moola Ram; Dinesh Kumar (Nutrient Cycling in Agroecosystems, 2010)

Conductometric studies and its significance during cane sugar manufacture - Sandeep K. Mitra; Vikesh Kumar; P. Sanyal (Sugar Tech, 2009)

Effects of 24-epibrassinolide and 28-homobrassinolide on the growth and antioxidant enzyme activities in the seedlings of Brassica juncea L. - Geetika Sirhindi; Sandeep Kumar; Renu Bhardwaj; Manish Kumar (Physiology and Molecular Biology of Plants, 2009)

The role of GABAA receptors in the acute and chronic effects of ethanol: a decade of progress - Sandeep Kumar; Patrizia Porcu; David F. Werner; Douglas B. Matthews; Jaime L. Diaz-Granados; Rebecca S. Helfand; A. Leslie Morrow (Psychopharmacology, 2009)

Bio-sequestration of carbon dioxide using carbonic anhydrase enzyme purified from Citrobacter freundii - Rishiram Ramanan; Krishnamurthi Kannan; Saravana Devi Sivanesan; Sandeep Mudliar; Simarjot Kaur; Anil Kumar Tripathi; Tapan Chakrabarti (World Journal of Microbiology and Biotechnology, 2009)

Simultaneous excision of two transgene flanking sequences and resolution of complex integration loci - Sandeep Kumar; William F. Thompson (Plant Molecular Biology, 2009)

Reserpine can confer stress tolerance and lifespan extension in the nematode C. elegans - Deepti Srivastava; Upasna Arya; Thangavelu SoundaraRajan; Hemalata Dwivedi; Sandeep Kumar; Jamuna R. Subramaniam (Biogerontology, 2008)

NAD+-dependent DNA ligase (Rv3014c) from M. tuberculosis: Strategies for inhibitor design - Divya Dube; Vandna Kukshal; Sandeep Kumar Srivastava; Rama Pati Tripathi; Ravishankar Ramachandran (Medicinal Chemistry Research, 2008)

Development and evaluation of an in vivo assay in Caenorhabditis elegans for screening of compounds for their effect on cytochrome P450 expression - Baby P. S. Chakrapani; Sandeep Kumar; Jamuna R. Subramaniam (Journal of Biosciences, 2008)

Measurement of genetic dissimilarity in fieldpea (Pisum sativum L.) genotypes using RAPD markers - Vinod Kumar Yadav; Sandeep Kumar; Ravindra K. Panwar (Genetic Resources and Crop Evolution, 2007)

Intrinsic rate of natural increase of Brueelia amandavae (Ischnocera, Phthiraptera) populations infesting Indian red avadavat - Nidhi Gupta; Sandeep Kumar; Arun Kumar Saxena (Biologia, 2007)

Analysis of most common mutations R778G, R778L, R778W, I1102T and H1069Q in Indian Wilson disease patients: Correlation between genotype/phenotype/copper ATPase activity - Sandeep Kumar; Baburam Thapa; Gurjit Kaur; Rajendra Prasad (Molecular and Cellular Biochemistry, 2007)

Demonstration of a new biosensing concept for immunodiagnostic applications based on change in surface conductance of antibodies after biomolecular interactions - Sandeep Kumar Vashist; Inderpreet Kaur; Ram Prakash Bajpai; Lait Mohan Bharadwaj; Rupinder Tewari; Roberto Raiteri (Journal of Zhejiang University-SCIENCE B, 2006)

Image representation, scaling and cognitive model of object perception - Sandeep Kumar Ganji; Indu Potula; Venkata Naga Pradeep Ambati; Bhujanga Rao; Sandhya Kumari Ganji; Shwetha Kumari Ganji (Cognitive Processing, 2006)

Radioprotective properties of apple polyphenols: An in vitro study - Pankaj Chaudhary; Sandeep Kumar Shukla; I. Prem Kumar; I. Namita; Farhat Afrin; Rakesh Kumar Sharma (Molecular and Cellular Biochemistry, 2006)

Evaluation of copper toxicity in isolated human peripheral blood mononuclear cells and it's attenuation by zinc: ex vivo - Rashim Pal Singh; Sandeep Kumar; Ritambra Nada; Rajendra Prasad (Molecular and Cellular Biochemistry, 2006)

Regulation of native GABAA receptors by PKC and protein phosphatase activity - Sandeep Kumar; Rahul T. Khisti; A. Leslie Morrow (Psychopharmacology, 2005)

Antioxidant activity of fractionated extracts of rhizomes of high-altitude Podophyllum hexandrum: Role in radiation protection - Raman Chawla; Rajesh Arora; Raj Kumar; Ashok Sharma; Jagdish Prasad; Surendar Singh; Ravinder Sagar; Pankaj Chaudhary; Sandeep Shukla; Gurpreet Kaur; Rakesh Kumar Sharma; Satish Chander Puri; et al. (Molecular and Cellular Biochemistry, 2005)

Biosensor based on Langmuir–Blodgett films of poly(3-hexyl thiophene) for detection of galactose in human blood - Sandeep K. Sharma; Rahul Singhal; B.D. Malhotra; Neeta Sehgal; Ashok Kumar (Biotechnology Letters, 2004)

Vegetative and generative dispersal capacity of field released transgenic aspen trees - Matthias Fladung; Olaf Nowitzki; Birgit Ziegenhagen; Sandeep Kumar (Trees, 2003)

Labour saving and cost reduction machinery for sugarcane cultivation - R. N. S. Yadav; Sandeep Yadav; Raj Kumar Tejra (Sugar Tech, 2003)

Somatic mobility of the maize element Ac and its utility for gene tagging in aspen - Sandeep Kumar; Matthias Fladung (Plant Molecular Biology, 2003)

A new gene for resistance in rice to Asian rice gall midge (Orseolia oryzae Wood Mason) biotype 1 population at Raipur, India - M. N. Shrivastava; Arvind Kumar; Sandeep Bhandarkar; B. C. Shukla; K. C. Agrawal (Euphytica, 2003)

A quick and simple biostrip technique for detection of lactose - Sandeep K. Sharma; Neeta Sehgal; Ashok Kumar (Biotechnology Letters, 2002)

Performance evaluation of sugarcane chopper harvester - R. N. S. Yadav; M. P. Sharma; S. D. Kamthe; A. Tajuddin; Sandeep Yadav; Raj Kumar Tejra (Sugar Tech, 2002)

Gene stability in transgenic aspen ( Populus ). II. Molecular characterization of variable expression of transgene in wild and hybrid aspen - Sandeep Kumar; Matthias Fladung (Planta, 2001)

In vitro and in vivo evaluations of biodegradable implants for hormone replacement therapy: Effect of system design and PK-PD relationship - Senshang Lin; Pi-Yun Chao; Yie W. Chien; Amyn Sayani; Sandeep Kumar; Michelle Mason; Thomas West; Alice Yang; Donald Monkhouse (AAPS PharmSciTech, 2001)

In vitro plantlet production system for Kaempferia galanga, a rare Indian medicinal herb - Fatima Shirin; Sandeep Kumar; Yogeshwar Mishra (Plant Cell, Tissue and Organ Culture (PCTOC), 2000)

Folding funnels and conformational transitions via hinge-bending motions - Sandeep Kumar; Buyong Ma; Chung-Jung Tsai; Haim Wolfson; Ruth Nussinov (Cell Biochemistry and Biophysics, 1999)

Regeneration of plants from leaflet explants of tissue culture raised safed siris (Albizia procera) - Sandeep Kumar; A.K. Sarkar; C. Kunhikannan (Plant Cell, Tissue and Organ Culture (PCTOC), 1998)

Genetic transformation of Populus genotypes with different chimaeric gene constructs: transformation efficiency and molecular analysis - Matthias Fladung; Sandeep Kumar; M. Raj Ahuja (Transgenic Research, 1997)